Deep neural network-based prediction of sauce-flavor Baijiu fermentation process and regulation of flavor compound synthesis - Shiyuan Ma; Wei Cheng; Zhongfu Duan; Dan Huang; Ping Huang; Qiuxia Li; Siyuan Zeng; Rongqing Zhou; Yadong Zhang; Jiao Niu; Chongde Wu; Yi Shen (Bioresource Technology, 2026)

Seasonally driven ecological adaptation in sea cucumbers Apostichopus japonicus: dynamic coupling of nutrient metabolism and gut microbial network reconfiguration - Ping Li; Jia-Ming Zhang; Cheng-Zhuang Chen; Bin Liu; Ling Liu; Zhi-Hua Li (Reviews in Fish Biology and Fisheries, 2026)

PSMG3 enhances the proliferation and metastasis of hepatocellular carcinoma via inhibiting HDAC6 - Shuaihui Wu; Caiyan Wu; Huibin Wang; Yang Shi; Ping Jiang; Dilinigeer Tayier; Kunlei Wang; Qian Cheng; Xinyin Li; Qifeng Wei; Zhixiang Cheng; Bo Liao; et al. (Functional & Integrative Genomics, 2026)

Correction to: Sequence dynamics and plastome evolution: decoding the complete chloroplast genome of Oenothera drummondii and comparative analysis within Oenothera (Onagraceae) - Chang An; Wenbo Xu; Yixin Yao; Min Li; Yanxiang Lin; S. V. G. N. Priyadarshani; Aya Elderini; Yan Cheng; Site Luo; Yuan Qin; Ping Zheng (Functional & Integrative Genomics, 2026)

Sequence dynamics and plastome evolution: decoding the complete chloroplast genome of Oenothera drummondii and comparative analysis within Oenothera (Onagraceae) - Chang An; Wenbo Xu; Yixin Yao; Min Li; Yanxiang Lin; S. V. G. N. Priyadarshani; Aya Elderini; Yan Cheng; Site Luo; Yuan Qin; Ping Zheng (Functional & Integrative Genomics, 2026)

Distinct soil microbial community composition and structure: evidence from soil inside and outside the cattle farm - Qi Ding; Jiayi Li; Fengling Xue; Wenjun Cui; Shiguang Hu; Lingfeng Yu; Wanyue Huang; Lin Li; Ping Cheng (Brazilian Journal of Microbiology, 2026)

Genome-wide identification and functional validation of asparagine synthetase genes (NtASNs) in Nicotiana tabacum - Yan-Qun Zhang; Xin-Yao Huang; Wu-Xia Xi; Pei-Song Yang; Jia-Rong Wu; Jian-Cheng Wu; Shao-Ming Zhao; Hang Li; Rong Zhang; Shi-Ping Zhou; Wei-Guang Wang; Qiu-Fen Hu; et al. (Plant Science, 2026)

lnc5714 participates in silkworm resistance to Nosema bombycis infection by regulating MRPL4-related host energy metabolism - Li Sui; Qiong Yu; Wangbin Qin; Yujia Fang; Pingyang Wang; Jie Cheng; Xudong Tang; Ping Qian (Journal of Invertebrate Pathology, 2026)

New perspectives on the role of oil-gas in mineralization of sandstone-hosted uranium deposits: Carbonate evidence from Yuejin Ⅱ, Qaidam Basin, China - Yi-Han Lin; Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Jun-Ying Ding; Zhi-Lin Cheng; Zhao-Hui Li; Xue-Feng Gao; Ping Feng (Journal of Asian Earth Sciences, 2026)

Functions of tandem-repeat galectins and domain coordination governs galectin-4 activity in grass carp (Ctenopharyngodon idella) - Hongzhou Xu; Tian Yang; Haixia Liu; Huanjie Li; Ping Cheng; Yuxin Shen; Di Wang; Zijun Fan; Heyi Liu (Fish & Shellfish Immunology, 2026)

Constructing structure-charge dual-regulated nanofiltration membranes via swelling embedding strategy for efficient separation - Ping Li; Yuan Zhou; Chunxi Hai; Wenjie Liu; Ying Cheng; Yu Tang; Yanxia Sun; Shengde Dong; Luxiang Ma; Xin He; Qi Xu (Desalination, 2026)

Antibiotics affect the water purification performance and greenhouse gases emission mode in modular moving bed constructed wetland - Ping Deng; Hongyun Ma; Zhihao Luo; Lingwei Kong; Lei Zhou; Xueqi Zhang; Jianshi Huang; Yiqian Chen; Yiyang Li; Yuefang He; Shaole Yu; Shuiping Cheng (Chemical Engineering Journal, 2026)

Lignin-first depolymerization of softwood over a NiCu/TiO2 catalyst for the sustainable production of dihydroconiferyl alcohol - Peng Zhu; Yu-Xin Zhang; Qiang Wang; Guo-Hui Cheng; Jun-Li Ren; Ling-Ping Xiao; Run-Cang Sun (Bioresource Technology, 2026)

Molecular-level analysis of atmospheric particulate organic compounds using HPLC-Orbitrap MS/MS: effects of solvents - Shan Xu; Minghui Lu; Ping Zeng; Meng Chang; Haoqian Wang; Xuehui He; Baode Xue; Xinyu Ji; Kuai Yu; Jingkun Jiang; Hairong Cheng; Xiaoxiao Li (ENGINEERING Environment, 2026)

Effects of dietary chitosan oligosaccharides on the laying performance, egg quality and serum biochemical parameters of aged laying hens - Zhilan Yao; Cheng Li; Ping Wu; Ping Liu (Theriogenology, 2026)

Tracking sedimentation process under progressive mangrove propagation in low-energy bays - Weiming Li; Zhijun Dai; Xuefei Mei; Jiejun Luo; Wenjun Zeng; Ping Zhang; Ran Chen; Jinping Cheng (Marine Geology, 2026)

Phosphorus fate and recovery potential during anaerobic lactic acid fermentation of food and kitchen wastes - Wei Wang; Ruizhe Zhang; Suqin Cheng; Nan Jiang; Qian Ping; Yongmei Li (Journal of Environmental Chemical Engineering, 2026)

Avermectin induces developmental toxicity and immunotoxicity in zebrafish larvae - Wei-Guo Wang; Shou-Lin Li; Da-Wei Yan; Yun-Fei Sha; Wen-Ping Xu; Jia-Gao Cheng; Zhong Li; Li-Ming Tao; Yang Zhang (Journal of Environmental Sciences, 2026)

Boosting lattice oxygen activation and active sites generation via an Mn-O electron bridge for efficient simultaneous oxidation of toluene and NO over Mn5Co4Ce3Ox catalyst - Lei Gao; Yukai Quan; Ping Fang; Dong Xie; Caiting Li; Cheng Sun; Jiahao Zhang; Ruotao Bai; Jingshuo Zhang (Fuel, 2026)

Metal-organic frameworks nanozyme-integrated portable microneedle patch for visual bacterial monitoring in meat - Jiayu Cheng; Heng An; Xiangdan Meng; Li-Ping Xu (Food Chemistry, 2026)

Assessment of a farmland-constrained deep learning framework for fine-scale extraction of farmland shelterbelts from Sentinel-2 - Yingqi Xu; Ping Lv; Zhuo Zhang; Lanjie Li; Zheng Chai; Cheng Tang; Yuanyuan Li (Agroforestry Systems, 2026)

Phylogenomics, reticulate evolution, and taxonomic revision of East Asian Cardamine (Brassicaceae) in the Hengduan biodiversity hotspot - Jia-lu Li; Dan-hui Liu; Jiang-lin Miao; Yi He; Liao-cheng Zhao; Di Zhang; Ke-ping Ma; Quan-ru Liu (Molecular Phylogenetics and Evolution, 2026)

Early Fibroblast Remodeling Associated with Lung Tissue Preservation After FLASH Irradiation - Caihui Li; Luhao Tan; Qixiang Liu; Zhihui Li; Menghua Li; Xuefeng Yang; Guofu Dong; Cheng Quan; Jie Ping; Changzhen Wang; Hao Lu (Phenomics, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Fungal community succession drives the decay of jujube fruit (Ziziphus jujuba Mill. cv. Jingcang 1) during ambient storage - Jian-Yu Wang; Ke-Xin Jiao; Min-Xin Mao; Cheng-Gang Li; Jian-Ping Qu; Bo Zhou; Qian Zhang; Qing Hao (Postharvest Biology and Technology, 2026)

Unraveling the impact of food processing technologies on postbiotic bioactivity, food matrix interactions, and human health outcomes - Junxin Zhao; Mengfei Duan; Ruiying Xu; Yumeng Cheng; Jinheng Li; Deguo Wang; Xianghui Yan; Ping Yu; Zheling Zeng; Yunzhi Lin; Yoshimitsu Masuda; Ken-ichi Honjoh; et al. (Food Bioscience, 2026)

Methane production in the stems of living trees in subtropical forests - Zhi-Ping Wang; Josep Barba; Jian-Guo Xue; Xiang-Cheng Mi; Ang Li; Zhen-Ying Huang; Shi-Jie Han (Planta, 2026)

Calculation of hydrogeological parameters based on a high-flow long-duration water release test of multiple deep boreholes, Xiadian coalfield, North China - Fang Li; Rui Luo; Zhijia Yu; Wubin Gao; Jianggen He; Yu Ping; Shiyuan Tian; Zihan Wang; Tao Cheng; Colin G. Farquharson; Xinyi Wang (Hydrogeology Journal, 2026)

A universal geometric model of egg shape with sine-based deformation - Ching-Wei Cheng; Chia-Chun Lai; Ping-Kun Tsai; Ko-Jung Huang; Cheng-Han Li (Biosystems Engineering, 2026)

n-butanol treatment alleviates chilling injury of mango fruit by regulating membrane lipid metabolism - Hao Dong; Ping Yi; Lihong Xie; Qi Wei; Yuhan Long; Min Huang; Ting Gan; Qiuyu Cheng; Lan Zhang; Li Li; Jian Sun (Postharvest Biology and Technology, 2026)

H3K18 lactylation-regulated ATG10 is involved in the acute respiratory distress syndrome induced by acute exposure to hydrogen sulfide through activation of autophagy in lung epithelial cells - Bingyu Ling; Ping Geng; Bowen Fan; Xiaolong Wu; Yi Yang; Jiaheng Lin; Wenjie Li; Qizhan Liu; Cheng Cheng; Jinsong Zhang; Hao Wu (Journal of Hazardous Materials, 2026)

Corrigendum to Avermectin induces developmental toxicity and immunotoxicity in zebrafish larvae. Journal of Environmental Sciences (2026), doi: https://doi.org/10.1016/j.jes.2026.03.02 - Wei-Guo Wang; Shou-Lin Li; Da-Wei Yan; Yun-Fei Sha; Wen-Ping Xu; Jia-Gao Cheng; Zhong Li; Li-Ming Tao; Yang Zhang (Journal of Environmental Sciences, 2026)

Ion trapping as an intrinsic physicochemical barrier limiting plant translocation and phytotoxicity of ionizable contaminants - Zhi-Yu Lu; Jia-Heng Zhao; Li Yuan; Yan-Yun Hu; Yi Hu; Cheng-Yuan Liu; Yang Pan; Chun-Chun Lv; Ke-Ke Qi; Wei Zhi; Guo-Ping Sheng (Journal of Environmental Sciences, 2026)

Direct visual evidence of S-scheme charge transfer: CeO2 quantum dots anchored on CdS nanosheets for synergistically enhanced photocatalysis - Yaodi Fu; Ke Wen; Shimei Liu; Ping Li; Banpeng Cao; Lihong Cheng; Jingjing Liu; Yi Tang; Xiangshu Chen; Hidetoshi Kita; Lingfang Qiu; Shuwang Duo (Environmental Research, 2026)

Integrating microbial functional traits to evaluate responses of soil quality to organic amendments in newly reclaimed farmland - Luotong Wang; Hanqin Yin; Chunlei Huang; Guifang Li; Cheng Zhu; Ping Li (Plant and Soil, 2026)

Independent and joint effects of ambient temperature and relative humidity on fetal distress: effect modification by air pollutants - Hua Xiao; Yi Wang; Zongli Qi; Ziwei Ye; Liping Li; Li Mao; Peng Hu; Yuefei Li; Haoyun Zhang; Yao Cheng; Hao Wang; Ping Chen; et al. (International Journal of Biometeorology, 2026)

Facile preparation of new bidentate quaternary ammonium-type stationary phase for the separation of versatile analytes in hydrophilic interaction liquid chromatography - Xiao-dong Cheng; Kai-feng Tan; Cai-yong Lin; Yun-ping Li; Xue-xin Dai (Analytica Chimica Acta, 2026)

Oral co-exposure to Clostridioides difficile toxin A and ovalbumin disrupts intestinal homeostasis and predisposes to food allergy in mice - Xiaoqian Xu; Xiang Zeng; Youdou Cheng; Ping Yang; Jinyan Gao; Xuanyi Meng; Yong Wu; Xin Li; Ping Tong; Hongbing Chen (Toxicon, 2026)

Non-equilibrium criticality-enhanced quantum sensing with superconducting qubits - Hao Li; Yaoling Yang; Yun-Hao Shi; Zheng-An Wang; Ziting Wang; Jintao Li; Yipeng Zhang; Kui Zhao; Yueshan Xu; Cheng-Lin Deng; Yu Liu; Wei-Guo Ma; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Avermectin disrupts blood-brain barrier integrity in zebrafish larvae via the Wnt/β-catenin signaling pathway - Wei-Guo Wang; Lin-Jing Du; Huan-Ou Ma; Wen-Ping Xu; Li-Ming Tao; Zhong Li; Jia-Gao Cheng; Li Zhao; Yang Zhang (Pesticide Biochemistry and Physiology, 2026)

Metabolites from Trichoderma amazonicum AF2115A by monoculture and coculture with Fusarium oxysporum A11F(B) - Wei-Cheng Xu; Yin-Ping Song; Ji-Xue Zou; Xiu-Li Yin; Nai-Yun Ji (Phytochemistry, 2026)

Ganoderma lucidum spore lipid extract synergizes with chemotherapy to alleviate tumor progression by enhancing macrophage phagocytosis of dying tumor cells - Guan-Di Xiao; Zi-Xuan Li; Yi-Fang Li; Lei Liang; Cheng Yuan; Wen-Dong Xu; Ju-Yan Liu; Yan-Ping Wu; Rong-Rong He (PharmaNutrition, 2026)

Combined effects of chitosan–peppermint oil coating on germination, antioxidant enzymes, and antifungal activity in stored soybean seeds - Huanxin Zhang; Cheng Li; Ping Liu; Ping Wu; Minqi Lv (Journal of Stored Products Research, 2026)

Splicing factor SC35 inhibits Nosema bombycis proliferation by regulating the alternative splicing of Bmupp1 - Qiong Yu; Qingsheng Qu; Shiyi Lu; Pingyang Wang; Li Sui; Jie Cheng; Xudong Tang; Ping Qian (Journal of Invertebrate Pathology, 2026)

Metabolic reconstruction and microbial network assembly immobilised heavy metals during soil function recovery in coal gangue - Pan Wang; Cheng Chen; Yubo Zhang; Chaosheng Liao; Lin Li; Xiaolong Tang; Mingjie Zhang; Guangrou Lu; Xiaokang Huang; Ping Li; Chao Chen (Journal of Hazardous Materials, 2026)

Swelling-thermal crosslinking engineered polyamide nanofiltration membranes for high-performance Mg2+/Li+ separation - Yu Tang; Shengde Dong; Ping Li; Ying Cheng; Wenjie Liu; Chuanjiang Cheng; Yanxia Sun; Qi Xu; Chunxi Hai; Yuan Zhou (Journal of Environmental Chemical Engineering, 2026)

Effects of exogenous N-acyl-homoserine lactones on biofilm formation by denitrifying bacteria and denitrification start-up in sequencing batch biofilm reactors - Zhi-fei Li; Meng-yuan Yu; Jun-lin Li; Jun Xie; Xiang-ju Cheng; Wang-bao Gong; Kai Zhang; Guang-jun Wang; Yun Xia; Wen-ping Xie; Quan-fa Zhong; Hong-yan Li; et al. (Journal of Environmental Chemical Engineering, 2026)

Mg–K isotopic compositions deciphering mantle heterogeneity beneath southeast Tibet - Qiong Chen; Hao Cheng; Guo-Chun Zhao; Mei-Fu Zhou; Ping-Ping Liu; Wen-Jun Li; Min Sun (Geochimica et Cosmochimica Acta, 2026)

Strategic ultrasonic regulation of Saccharomyces cerevisiae fermentation for enhanced anthocyanin production and wine quality - Jiaqi Wang; Jianing Li; Jiming Li; Ping Wang; Guoli Cheng; Binsheng Wei; Tingting Ma; Yulin Fang; Xiangyu Sun (Food Research International, 2026)

Associations between antibiotic and metal resistance genes in geothermal springs - Zhipeng Yin; Hua Ping; Cheng Li (Environmental Research, 2026)

Graphitization of marine kerogen and its effects on nanopores and adsorption performance - Guangming Meng; Xianming Xiao; Haifeng Gai; Yanming Zhao; Yijie Xing; Kun Zhang; Yu Liu; Qin Zhou; Tengfei Li; Wei Liu; Peng Cheng; Ping Gao (Science China Earth Sciences, 2026)

Root morphological strategies enhance growth of Cunninghamia lanceolata and Schima superba under nitrogen stress in intercropping systems - Xiao-Li Yan; Cong Cheng; Yunhao Xu; Jiaxiang Yu; Zhaozhao Wang; Yanru Wang; Xinghao Tang; Pengfei Wu; Xiangqing Ma; Lu-Ping Qu (Plant and Soil, 2026)

The “Last-mile Efforts” of Subseasonal Prediction and Services for Climate Resilience and Sustainability: Review and Outlook - Jing Yang; Mengqian Lu; Anling Liu; Tat Fan Cheng; Yuxian Pan; Miaoni Gao; Lun Dai; Shentong Li; Wen Deng; Xinyao Feng; Shiyu Zhang; Lu Tang; et al. (Advances in Atmospheric Sciences, 2026)
Subseasonal predictions from 2 weeks to 2 months have made significant advancements over the past decade, driven by progress in physical understanding, climate modeling, computational capabilities, and artificial intelligence (AI). These predictions are increasingly in demand due to their potential to provide stakeholders with adequate lead time for effective disaster adaptation, mitigation, and resource management. However, there remain critical gaps in the engagement between prediction providers and service users. Providers often lack insight into the specific needs of users and do not have transferrable strategies to build trust through tailored evaluations and clear confidence levels, which often results in repeatedly devising approaches for each provider–user interaction. Further, users frequently struggle to interpret predictions and are hesitant to make decisions based on these uncertain outcomes. This paper attempts to make “last-mile efforts” by reviewing relevant literature, operational systems, and the most informative communications and engagement strategies with key sectors. It proposes a preliminary framework to standardize the approach for provider–user interaction in the context of subseasonal prediction and services, with potential applicability and extension to seamless prediction systems in the future. Lastly, we underscore future directions for subseasonal predictions, emphasizing the integration of dynamic climate modeling and AI-driven enhancements with large ensemble techniques to improve both reliability and confidence. This review is part of the United Nations Educational Scientific and Cultural Organization (UNESCO) International Decade of Sciences for Sustainable Development (2024–33) and contributes to the Seamless Prediction and Services for Sustainable Natural and Built Environment (SEPRESS) Program (2025–32), an initiative endorsed under this global framework.

Intermittent Theta-Burst Stimulation (iTBS) Improves Motor Coordination and Modulates Neuroinflammation and Autophagy in SCA3/MJD Mice - Le-Wen Chen; Yan-Hua Lian; Xiao-Lei Dong; Kai-Liang Luo; Li-Qiong Zhan; Li-Li Xie; Qi-Kui Sun; Wei Lin; Shi-Rui Gan; Xiao-Ping Cheng; Jun Ni; Xin-Yuan Chen (The Cerebellum, 2026)

Shorter to be effective: subanesthetic-dose ketamine infusion reduces the global and regional path length of brain functional connectivity in patients with treatment-resistant depression and suicidal ideation - Wei-Chen Lin; Li-Kai Cheng; Tung-Ping Su; Li-Fen Chen; Pei-Chi Tu; Cheng-Ta Li; Ya-Mei Bai; Shih-Jen Tsai; Mu-Hong Chen (Psychopharmacology, 2026)

Sequence Stratigraphy, Sedimentary Evolution and Controlling Factors of the Shan-1 Member in Permian Shanxi Formation, Qingyang Gas Field, Ordos Basin, Central China - Qian-qian Fan; Shi-qiang Xia; Hui Xia; Wei Wang; Long Wang; Yan Wang; Shi-cheng Wang; Shuai-shuai Feng; Wei Zhang; Ya Li; Ping Liu; Qian-yun Dong (Applied Geophysics, 2026)

A Novel Wave-Absorbing Support System for Mitigating Rock Burst in Deep-Buried Hard Rock Tunnels - Yue-Mao Zhao; Zheng-Chen Ge; Ben-Guo He; Cheng-Xiang Yang; Xing-Long Li; Xiao-Jun Yu; De-Xian Li; Yong-Ping Liu (Rock Mechanics and Rock Engineering, 2026)

Structurally diverse monoterpenoid indole alkaloids from Damnacanthus hainanensis as well as their potential anti-inflammatory and anti-HIV effects - Gui-Qiong Wu; Long-Cheng Cui; Ye-Ping Liu; Chen-Xu Yue; Lin-Xuan Li; Tian-Yu Wang; Yu-Shan Wang; Shu-Ri Li; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2026)

Rapid evaluation of the comprehensive quality of paeonol/cyclodextrin supramolecular complexes using CASSA based on near-infrared spectroscopy combined with artificial intelligence - Bo-yao Zhang; Xin-li Li; Cheng Qian; Si-min Xue; Zhi-tong Zhang; Si-yi Liu; Guo Zhang; Guo-ping Peng; Ning Ding; Yun-feng Zheng (Molecular Diversity, 2026)

Oil phase-driven nanoemulsions improve CoQ10 stability, in vitro bioaccessibility and ex vivo intestinal uptake - Xia Jin; Peng Wu; Ni Wang; Ping Zhang; Cheng Li; Zejun Hu; Wenhao Zhao; Xiao Dong Chen (Food Research International, 2026)

A glucose-triggered self-reinforcing hydrogel based on carboxymethyl chitosan/oxidized hyaluronic acid/borax for delivering nano-selenium and dynamic diabetic wound management - Wei-Xiong Li; Shanshan Li; Hao Cheng; Yu Chen; Han-Jian Hu; Shipeng Tang; Jian Sun; Xiao-Ping Liao; Gang-Biao Jiang; Hongyan Zhang (Carbohydrate Polymers, 2026)

Quantifying the decoupling of pollution magnitude and geochemical signatures in livestock manure: a novel geometric fingerprint approach - Qiu Cheng; Yi Jijun; Fan Shoubo; Du Qiuxiang; Li Qianglin; Wang Liting; Liang Qingling; Zheng Guihua; Xiong Ping (Environmental Monitoring and Assessment, 2026)

New sesquiterpenoids from the flowers of Pentanema britannicum with cytotoxicity activities - Jun-Hui Zhang; Ping He; Sheng-He Yang; Jia-Li Lang; Yan Fu; Jian Su; Yu-Cheng Gu; Yi-Bing Wu (Natural Product Research, 2026)

Flucarbazone-sodium resistance detection in Japanese brome (Bromus japonicus Thunb. ex Murr.) and candidate herbicides for its chemical control in the wheat fields of the North China Plain - Hengzhi Wang; Yunxia Duan; Cheng Yang; Yi Li; Mengmeng Hu; Xinyu Sun; Ping Yu; Tao Jin; Jinxin Wang; Weitang Liu (Crop Protection, 2026)

The crucial role of ground ice in slowing permafrost degradation - Guojie Hu; Zhe Sun; Lin Zhao; Deliang Chen; Defu Zou; Chien-Lu Ping; Wenxin Zhang; Yao Xiao; Guangyue Liu; Ren Li; Xiaodong Wu; Yifan Wu; et al. (Science Bulletin, 2026)

Study on SCFs distribution for CFST KK-joints with internal ring stiffeners under bending moment - Kang Wang; Feng-Ping Yuan; Qiang Li; Yu-Hang Wang; Yu-Xiao Luo; Jie Yu; Cheng-Yang Du (Ocean Engineering, 2026)

Photosensitive COFs-carboxylated nanocellulose membrane enables high-efficiency uranium extraction via synergistic coordination complexation and photocatalytic reduction - Shuaishuai Guo; Zhenlong Zeng; Dongyang Xu; Dingquan Li; Ping Cao; Jie Sun; Shiqin Zhang; Cheng Wang; Guowen Peng; Qingyi Zeng (Journal of Hazardous Materials, 2026)

Investigation on thermal runaway mechanism of tert-butyl peroxy benzoate using calorimetry analysis coupled with free radical spin-trapping technology - Zhi-Ping Li; Xiao-Yu Fang; Jun-Cheng Jiang; Lei Ni; Zhi-Quan Chen; Yuan-Yuan Wang (Journal of Environmental Chemical Engineering, 2026)

The formation mechanism of ultra-deep gas condensate reservoirs: A case study of the Shunbei No. 4 strike-slip fault zone in the Tarim Basin, NW China - Xin Yang; Hongwei Ping; Zicheng Cao; Lu Yun; Haiying Li; Jun Han; Feng Geng; Cheng Huang; Xinle Zhang; Zhongdeng Lu; Honghan Chen (Journal of Asian Earth Sciences, 2026)

Cyflumetofen induces hepatic steatosis and disrupts lipid metabolism in zebrafish larvae - Wei-Guo Wang; Yi-Min Duan; Da-Wei Yan; Lan Xu; Wen-Ping Xu; Li-Ming Tao; Yang Zhang; Jia-Gao Cheng (Chemico-Biological Interactions, 2026)

Long-term intercropping increases soil aggregate stability by altering soil colloid content and stability - Chuan-Lin Xiao; Jing-Ru He; Cheng-Bao Wang; Wei-Ping Zhang; Jun Mao; Peter Christie; Jian-Ying Shang; Long Li (Plant and Soil, 2026)

Physicochemical strategies for antibiotic removal in aquaculture wastewater: Mechanistic insights, technological challenges, and sustainable development pathways - Tai-Yue Wang; Yan-Ping Qiao; Kai-Jun Yue; Ming Cheng; Li-Ting Hao; Nan Zhang; Ran-Bin Liu; Chen Shi (Aquaculture, 2026)

Efficient generation of highly reactive FeIVO2+ via the Fe(II)/Cl2 reaction for water purification - Shaoxiong He; Yuxin Wu; Wenlei Qin; Shenzhou Li; Wanting Cheng; Ping Li; Shizhong Wang; Gangfeng Ouyang; Mingshan Zhu; Jingyun Fang (Water Research, 2026)

Raccoon dog parvovirus NS1 protein antagonizes type I interferon signaling by promoting selective autophagic degradation of IRF3 - Wen-yu Cao; Rui-qi Wang; Jin-yang Zheng; Ping Ma; Bo Hu; Cheng-qi Zhang; Ya-jie Sun; Jia-jia Liu; Ding-rui Guo; Zi-han Zhao; Xin Cao; Xue Bai; et al. (Veterinary Microbiology, 2026)

Marine biomaterials for advanced food packaging: From sourcing to intelligent functional design and commercial prospects - Cheng Wang; Mengru Zhang; Tong Zhang; Haitao Du; Hongmin Xia; Renwei Guan; Fengdan Guo; Xinyi Li; Mingming Wang; Xiuwen Jia; Ping Wang (Trends in Food Science & Technology, 2026)

Cultivar-dependent effects of arbuscular mycorrhizal (AM) fungal inoculation on fruit quality and native AM fungal community in navel orange - Xin-Ping Tan; Cheng-Zhuo Li; Ying-Ning Zou; An-Qi Lei; Mashael Daghash Alqahtani; Qiang-Sheng Wu (Rhizosphere, 2026)

Advances in chitosan-mediated seed enhancement: Germination, stress tolerance, and storage stability - Huanxin Zhang; Cheng Li; Ping Liu; Ping Wu; Minqi Lv (Journal of Stored Products Research, 2026)

Benzyl isothiocyanate inhibits the conjugative transfer of mcr-1-positive plasmid via suppressing intercellular contact and limiting energy supply - Ping Cheng; Shuying Liang; Shixin Gui; Xinyu Wang; Lingfeng Yu; Wenjun Cui; Chunxu Lu; Lin Li (Journal of Environmental Management, 2026)

Proanthocyanidins in food and health: structure–activity relationships, application challenges, and emerging strategies - Ziyu Li; Wenjun Wang; Ping Cheng; Qirong Dong; Haiqi Chen; Kai Fu; Chao Fu; Yunfeng Pu; Donghong Liu (Food Chemistry, 2026)

Cyflumetofen disrupts the blood-brain barrier and induces neurotoxicity in zebrafish larvae - Wei-Guo Wang; Yi-Min Duan; Wen-Ping Xu; Li-Ming Tao; Yang Zhang; Jia-Gao Cheng (Chemico-Biological Interactions, 2026)

The Classification History of Lamiaceae and a Generic Synopsis in China - Si-Cheng Xu; Su Liu; Ya-Ping Chen; Yue Zhao; Fei Zhao; Chun-Lei Xiang; Bo Li (The Botanical Review, 2026)

Breaking the antimicrobial resistance dilemma: marine natural products, a treasure trove for the development of new anti-Staphylococcus aureus drugs - Peng-Jie Li; Liu-Xia Lv; Xi-Zhen Cao; Jian-Yu Liu; Ji-Xiu Gao; Hao-Ran Li; Gulab Said; Dan Chen; Bo Yao; Xin Liu; Mei-Yan Wei; Xiao-Ping Yang; et al. (Marine Life Science & Technology, 2026)
Antimicrobial resistance (AMR) affects multiple fields, including medicine, pharmacy, food safety, and animal husbandry, and poses a major threat to public health and economic development. Staphylococcus aureus has emerged as one of the most critical bacterial pathogens due to its widespread prevalence and significant genetic plasticity. This review outlines currently approved small-molecule drugs for clinical use and their mechanisms in controlling bacterial infections and antimicrobial resistance, highlighting the development of novel agents as an effective strategy to combat AMR. Special emphasis is placed on the antibacterial activity of marine-derived natural products (MNPs) against S. aureus , and a systematic analysis is presented for the first time on the structures, origins, activities, and structure–activity relationships of 1,192 compounds reported in 468 publications from 1977 to 2025. Among these, 36 MNPs exhibited significant activity against both methicillin-sensitive S. aureus and methicillin-resistant S. aureus (MIC ≤ 1 µg/mL). Macrolides and peptides represented the most prevalent structural classes, with compounds displaying potent activity accounting for 24% and 27% of the total active compounds, respectively. Further drug-likeness analysis shows that MNPs have promising therapeutic potential. Among the 160 highly active MNPs, over 80% have suitable lipid-water partition coefficients, and 41% fully meet Lipinski's Rule of Five. Structural analysis reveals tetrahydrofuran, tetrahydropyran, and sugar units as the most common motifs, present in 20, 16, and 14 compounds, respectively. Technologies and strategies to accelerate the development of marine-derived antibacterial drugs are also proposed. This will serve stakeholders across diverse sectors by supporting cross-sectoral coordination to address AMR.

Anti-inflammatory constituents from Murraya paniculata var. omphalocarpa - Kun-Ching Cheng; Chia-Hung Wu; Hao-Ze Li; Tsong-Long Hwang; Ping-Chung Kuo; Tian-Shung Wu (Phytochemistry Letters, 2026)

Anti-inflammatory metabolites from the leaves of Ohwia caudata - Qianqian Zhang; Ping Zhang; Yijin Wu; Huimin Li; Jingya Ruan; Jiaming Cheng; Yi Zhang; Tao Wang (Phytochemistry, 2026)

Suspensaditerpenes A–Q, anti-inflammatory labdane and nor-labdane diterpenoids from the seeds of Forsythia suspensa - Hui-Ying Li; Meng-Yu Bao; Hao-Ming Xiong; Can-Can Wang; Li-Ping Bai; Wei Zhang; Cheng-Yu Chen; Zhi-Hong Jiang; Guo-Yuan Zhu (Phytochemistry, 2026)

Dermal exposure to heavy metals contaminated soil from e-waste sites: Linking bioaccessibility to cellular uptake, cytotoxicity, and transport mechanisms in skin cells - Daolei Cui; Hua Zhong; Ziya Ma; Yiping Cheng; Chengxin Liu; Jingya Li; Jiaoyang Ma; Ping Xiang (Journal of Hazardous Materials, 2026)

Ti(IV)-incorporated covalent organic frameworks for efficient dark-photocatalytic reduction of U(VI) - Li-Ling Chen; Cheng-Peng Niu; Rui Zhang; Yun-Peng Wu; Zhen-Wen Zhang; Bin Lin; Cheng-Rong Zhang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Environmental Chemical Engineering, 2026)

Lactic acid bacteria in Jiangxiangxing Baijiu fermentation: Resource exploration, community succession and their ecological dynamics - Pan Huang; Zhongfu Duan; Shiyuan Ma; Wei Cheng; Qiuxia Li; Dan Huang; Ping Huang; Rongqing Zhou; Jiao Niu; Yadong Zhang; Chongde Wu (Food Bioscience, 2026)

Simultaneous activation of pyroptosis and cGAS-STING pathway with iridium(III) thiophene complexes for enhanced oral squamous cell carcinoma sono-immunotherapy - Jia-Wen Chen; Peng Wang; Jia-Ying Zhou; Yi-Fei Luo; Yi-Ling Li; Jia-Yin Wu; Ling-Ran Li; Bin Cheng; Cai-Ping Tan; Tong Wu (Chemical Engineering Journal, 2026)

FeC particle electrodes derived from copper slag boost peroxymonosulfate activation for efficient antibiotic degradation: non-radical pathways mediated by 3d orbital electron reconstruction - Linjin Li; Yaoze Wang; Guangfei Qu; Rui Xu; Yingying Cai; Minhua Cheng; Nanqi Ren; Ping Lu; Minjie He; Jun Wang (Bioresource Technology, 2026)

Design, synthesis and cytotoxic activity of sulfonylated derivatives of camptothecin - Xiong-Fei Luo; Zhi-Jun Zhang; Zi-Long Song; Zhi-Ping Wang; Jia-Xuan Yan; Xiao-Fei Liu; Li-Zeng Peng; Cheng-Jie Yang; Ying-Qian Liu (Natural Product Research, 2026)

Impacts of acidification and warming on carbon sequestration capacity in Pacific oysters: Roles of biosynthesis and biodeposition - Zi-Jing Meng; Cheng-Zhuang Chen; Yu-Qing Ma; Jian-Xue Feng; Ling Liu; Ping Li; Zhi-Hua Li (Aquaculture, 2026)

Efficient charge carrier separation over [Mo7O24]6- polyanions-intercalated porous graphitic carbon nitride for remarkably enhanced photocatalytic performance - Jiajia Liu; Yaodi Fu; Shimei Liu; Ping Li; Banpeng Cao; Lihong Cheng; Jingjing Liu; Yi Tang; Xiangshu Chen; Hidetoshi Kita; Lingfang Qiu; Shuwang Duo (Process Safety and Environmental Protection, 2026)

High-throughput screening identifies paullinic acid as an antiviral agent against Bombyx mori nucleopolyhedrovirus - Zhenwei Jia; Xiaoli Mo; Shidong Jiang; Li Sui; Yiling Zhang; Xueyang Wang; Jie Cheng; Ping Qian; Xudong Tang (Pesticide Biochemistry and Physiology, 2026)

Nickel isotopic evidence for potential deep magmatic sulfide ore bodies in orogenic settings - Peng-Yi Li; Shui-Jiong Wang; Fu-Ping Pei; Guan-Wen Yu; Bing-Qian Ding; Zi-Cheng Guan; Kai Song; Wen-Liang Xu (Geochimica et Cosmochimica Acta, 2026)

Isomeric halide engineering of self-assembled hole-selective layers for efficient indoor perovskite photovoltaics - Zhong-En Shi; Yi-Ting Hong; Cheng-Chieh Lu; Po-Cheng Shih; Shih-I Lu; Hsiao-Chi Hsieh; Sie-Rong Li; Yu-Che Lin; Zheng-Xuan Cai; Yan-Duo Lin; Chih-Ping Chen (Chemical Engineering Journal, 2026)

A metal-immuno photosensitizer strategy: Iridium(III)-zidovudine conjugate triggering sequential organelle stress and synergizing with PD-L1 inhibitor in oral squamous cell carcinoma - Yi-Ling Li; Peng Wang; Wu-Ya Zhang; Rui Zhou; Jia-Ying Zhou; Jia-Wen Chen; Jia-Yin Wu; Bin Cheng; Cai-Ping Tan; Tong Wu (Chemical Engineering Journal, 2026)

Anti-epileptic effect of saikosaponin a by inhibiting ferroptosis via the IL-17/Akt/ERK signaling pathway in the temporal lobe epilepsy model - Ping-Ping Li; Wen-Wen Wang; Jing-Tao Wang; Zi-Ao Xu; Xue-Fei Ji; Liao Guan; Lei Ye; Hong-Wei Cheng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Inhibition of the Microglial cGAS-STING Pathway Improves Neurological Deficits and Long-Term Hydrocephalus Symptoms in Mice with Intraventricular Hemorrhage - Hao-Xiang Wang; Hua-Jiang Deng; Kun-Hong Zhong; Zi-Ang Deng; Bao-Cheng Gao; Xin Tang; Yuan-You Li; Ke-Ru Huang; Ai-Ping Tong; Da-Xiong Feng; Liang-Xue Zhou (Molecular Neurobiology, 2026)

Breaking the Alzheimer’s Treatment Stalemate: Synergistic Application Strategies of Nanomaterials and Pharmaceutical Agents - Han Gao; Fangyuan Cheng; Zihan Zhang; Bo Yan; Pan Liao; Shishuang Zhang; Dai Li; Fanglian Chen; Ping Lei (Molecular Neurobiology, 2026)

Association between low daily average temperature and epilepsy outpatient visits: a hospital-based study in Chongqing, China - Pei Jiang; Jing Yang; Yumeng Zhou; Jinchi Gu; Fengxia Liu; Chunlei Tan; Yao Cheng; Hao Wang; Li Mao; Peng Hu; Ping Chen; Ding Liu; et al. (International Journal of Biometeorology, 2026)

Programmed cell death in osteoarthritis - Haolin Li; Ping Chen; Weigang Cheng; Zhimin Zhang; Juanjuan Yang; Hao Zhang; Fangmei Jin; Lili Kan; Lei Chen; Haidong Wang (Apoptosis, 2026)

Sustainable phosphate removal from water using iron particles coupled with a micro-electric field: Mechanisms and long-term performance - Bing Li; Feifei Xia; Jianhua Cheng; Zhiyi Deng; Ping Li; Jinhua Wu (Journal of Water Process Engineering, 2025)

Recovery of V2O5 from spent catalysts for NH3 and humidity sensors - Yan Li; Ping Hu; Miaomiao Liu; Bo Ran; Yuqing Zhu; Junxi Cheng; Jun Sun; Zhaofeng Wu (Journal of Environmental Chemical Engineering, 2025)

Palladium-catalyzed thermo, photo, and electrocatalytic CO₂ conversion to methanol and formaldehyde: A review of mechanistic pathways using synthetic, biogas, and fossil-derived CO2 - Yen-Yi Lee; Masimukku Srinivaas; I.-Cheng Li; Kapa Keharika; Rajender Boddula; Ramyakrishna Pothu; Sanna Gull; Bo-Wun Huang; Jein-Wen Chen; Prashanth W. Menezes; Guo-Ping Chang-Chien (Journal of Environmental Chemical Engineering, 2025)

The variation of the East Asian summer monsoon on multi-centennial scale during 8.3–2.9 ka BP - Chao-Jun Chen; Ya-Xi Dong; Yao Wu; Jian Zhang; Hai-Bo Wang; Yan-Xia Xue; Wen-Jun Sun; Man-Ping Xie; Hai Cheng; Jun-Yun Li; Ming-Qiang Liang; Ting-Yong Li (Global and Planetary Change, 2025)

Wheat germ peptides enhance hypoxia tolerance by modulating gut microbiota and reprogramming brain energy metabolism in mice - Jing-yang Cai; Ying-Ying Liu; Meng-Cheng Li; Xin-Xin Guo; Ai-Mei Liao; Yin-Chen Hou; Quan-Ping Liu; Yong-Chao Fan; Long Pan; Ji-Hong Huang (Food Bioscience, 2025)

Ambient-dried polymer aerogel engineered via interparticle “stringing” towards ultrahigh robustness, flame retardancy and harsh-environment durability - Ting-Ting Li; Ting Wang; Chengxu Xu; Xue Gou; Xi-Ping Huang; Si-Yao Zhong; Zhi-Cheng Fu; Jinni Deng; Wenli An; Hai-Bo Zhao; Ming-Jun Chen (Chemical Engineering Journal, 2025)

Toxic effects of enrofloxacin on grass carp (Ctenopharyngodon idellus): an ecological risk assessment based on cross-system regulatory mechanisms and network toxicology - Ping Li; Bianhao Zeng; Xuqian Cao; Yiwei Liu; Cheng-Zhuang Chen; Bin Liu; Ling Liu; Yi Chai; Zhi-Hua Li (Aquatic Toxicology, 2025)

IFNGR1, IRF8 genetic polymorphisms modulate the susceptibility of non-tuberculous mycobacteria pulmonary disease and influence the patients’ treatment outcomes and immune status - Li-ping Cheng; Zhi-bin Liu; Lei Wang; Jie Cao; Qing-rong Qu; Hai Lou; Xiao-na Shen; Juan Yang; Yuanyuan Yu; Rui Juan Zheng; Wei Sha; Qin Sun (Inflammation Research, 2025)

Quantitative Evaluation of Gas Injection Contribution Using Fluid Inclusion Data: A Case Study of the Condensate Gas Reservoirs of the Eastern Shunbei Area in the Tarim Basin - Zicheng Cao; Lu Yun; Hongwei Ping; Haiying Li; Feng Geng; Jun Han; Cheng Huang; Xin Yang; Honghan Chen (Journal of Earth Science, 2025)

Wind-tunnel simulation study of shelter effects of farmland shelterbelts with different configurations - Xiaoqian Li; Ping Lv; Zhuo Zhang; Lanjie Li; Xue Yang; Cheng Tang (Agroforestry Systems, 2025)

Beyond biodiversity: The more essential role of multi-trophic network complexity for predicting ecosystem multifunctionality under multiple stressors - Shangsheng Sun; Haojie Su; Qingyang Rao; Jianfeng Chen; Yafang Qin; Yongchao Peng; Chaoyue Cheng; Misha Zhong; Ruijing Ma; Yuwei Wang; Yihan Wang; Zengliang Jian; et al. (Water Research, 2025)

Network-based investigation of norfloxacin-induced nasal immune-related inflammatory responses in carp (Cyprinus carpio) and its cross-species implications for olfactory immune disturbance - Jia-Ming Zhang; Ping Li; Cheng-Zhuang Chen; Bin Liu; Ling Liu; Zhi-Hua Li (Fish & Shellfish Immunology, 2025)

Platinum-copper nanocubezyme facilitate spinal cord recovery via synchronously alleviating oxidative stress and mitigating BNIP3-mediated mitochondrial dysfunction - Xiangge Liu; Cheng Peng; Huiyi Yang; Jiajun Deng; Ping Wu; Yongchun Xiao; Li Wan; Ke Wang; Guowei Zhang; Hua Yang; Jianyu Zou; Judun Zheng; et al. (Chemical Engineering Journal, 2025)

Characterization of particle number size distribution and new particle formation in a highly-humid megacity Wuhan, central China - Haoqian Wang; Xiaoxiao Li; Jin Wu; Hao Wu; Yiran Li; Chong Liu; Ning Ma; Ping Zeng; Xuehui He; Jiapeng Ran; Huaying Song; Dandan Huang; et al. (Atmospheric Environment, 2025)

Organoids in Genetic Disorders: from Disease Modeling to Translational Applications - Yuanhang Zhu; Nanshan Lin; Juan Li; Haoqian Zhang; Ping Zhang; Xin Cheng; Qian Yang; Ling Liu (Stem Cell Reviews and Reports, 2025)

Crushing characteristics and energy dissipation modeling of Single-Particle-Size carbonaceous mudstone as roadbed fill - Yan Wang; Hong-yuan Fu; Jian-Ping Song; Ling Zeng; Tao Li; Jian-Ping Xiong; Hong-Ri Zhang; Wen-Guang Wang; You-Jun Li; Jing-Cheng Chen (Bulletin of Engineering Geology and the Environment, 2025)

Chlorchinaldol: A promising antiviral agent against iridoviruses in fish - Jia-Cheng Qin; Xiao-Ping Tan; Ying-Jie Jin; Guang-Shuo Wang; Shen-Ye Qu; Peng-Fei Li; Gao-Xue Wang; Fei Ling (Aquaculture, 2025)

Quantifying the impact of thermal maturity on carbon isotope variations of marine oils from the Shunbei ultra-deep petroleum system, Tarim Basin - Zhongdeng Lu; Hongwei Ping; Zicheng Cao; Lu Yun; Haiying Li; Feng Geng; Jun Han; Cheng Huang; Honghan Chen (Organic Geochemistry, 2025)

Reducing melamine exposure and oxidative stress markers in melamine-exposed workers: A pragmatic intervention study - Chia-Fang Wu; Chih-Hong Pan; Yu-Ming Hsu; Chiung-Yu Peng; Ching-Mei Cheng; Sih-Syuan Li; Chien-Ping Huang; Ming-Tsang Wu (Journal of Hazardous Materials, 2025)

Organic matter from spent paper cooking liquor promotes the growth and quality of Chinese chives - Yan Liu; Yuechao Yang; Guiwei Wang; Xiaoqi Wang; Ping Wang; Shan Li; Jiahui Liu; Songyuan Wang; Yijie Bai; Yao Cheng (Journal of Environmental Chemical Engineering, 2025)

The synergistic enhancement of adsorption for Pb2+ and organic dyes by a chitosan-based hydrogel as a multipollutant adsorbent - Yun Wang; Li-Ping Fang; Chen-Yang Li; Chang-Jing Cheng; Ting Liang; Xing-Bin Lv; Hai-Rong Yu (Journal of Environmental Chemical Engineering, 2025)

Lipid profiles and microstructure of alpine Holstein milk: Comparison with common Holstein milk - Xinying Hu; Qingyun Wang; Shuai Wang; Xinyi Cheng; Ping Qin; Jingwei Cui; Li Wang; Wei Wei; Xingguo Wang (International Dairy Journal, 2025)

Experimental study on the mechanism of CO2/external fluid interaction in shale pore structure - Jianguang Wei; Qiuyu Lu; Ao Zhang; Zhejun Pan; Guo Li; Chao Tang; Ping Fu; Haoran Cheng; Ying Yang (Fuel, 2025)

Kinetics of MnO2-catalyzed combustion of carbonaceous materials in mold flux - Peng Cheng; Qiuping Li; Zerong Duan; Guanghua Wen; Ping Tang; Zibing Hou; Bingzhou He (Fuel, 2025)

Cosolvent-modulated polyamide nanostructures enable precise Mg2+/Li+ separation for lithium recovery from brines - Ping Li; Yuan Zhou; Chunxi Hai; Ying Cheng; Yu Tang; Yanxia Sun; Shengde Dong; Luxiang Ma; Xin He; Qi Xu (Desalination, 2025)

Protein engineering and flow reactor design for anchored peptide-mediated continuous biocatalysis - Huan Li; Chun-Jiang Ma; Ya-Ting Gao; Qing-qing Zhou; Huan Chen; Feng Cheng; Ya-Ping Xue; Yu-Guo Zheng (Chemical Engineering Journal, 2025)

High-entropy sulfide and nanozyme hybrid system with synergistic interface-engineering: Ultra-sensitive photoelectrochemical detection of chloramphenicol - Yi-Hong Chen; Ai-Jun Wang; Ya-Cheng Shi; Li-Ping Mei; Pei Song; Tiejun Zhao; Jiu- Ju Feng (Chemical Engineering Journal, 2025)

In situ addition of layered double hydroxides promotes sulfate-dependent anaerobic methane oxidation and microbial community shifts in freshwater-influenced mangroves sediments - Jijuan Ding; Fei Liu; Jing Huang; Ping Li; Junmao Zhang; Bo Wu; Longfei Shu; Zhili He; Cheng Wang (Water Research, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Changes in cell wall characteristics and expression of MiERF12, MiERF109-like, and MiERF113 during mango softening - Yuhan Long; Lihong Xie; Ping Yi; Fang Huang; Min Huang; Ting Gan; Jian Sun; Li Li; Hao Dong; Qi Wei; Zhenmei Fan; Qiuyu Cheng (Postharvest Biology and Technology, 2025)

Oxidative damage induced by daily exposure to primary and emerging aromatic amines: Insights from large scale biomonitoring and cell-based high-throughput PCR array analysis - Shaohan Zhang; Zijun Zhou; Pingping Wang; Yanan Yao; Yuhao Cao; Jialan Liu; Ping Li; Tao Zhang; Hongkai Zhu; Lei Wang; Hongwen Sun; Zhipeng Cheng (Journal of Hazardous Materials, 2025)

Molecular mechanisms underlying multi-generational skeletal abnormalities in marine medaka induced by the quinolone antibiotic norfloxacin (NOR) - Cun-Long Wang; Ping Li; Bin Liu; Cheng-Zhuang Chen; Yu-Qing Ma; Jian-Xue Feng; Ya-Nan Xu; Ling Liu; Zhi-Hua Li (Journal of Hazardous Materials, 2025)

AhR-mediated histone lactylation drives cellular senescence during benzo[a]pyrene-evoked chronic obstructive pulmonary disease - Li-Hong Chen; Jun-Ping Wei; Meng-Die Li; Xiu Lu; Yi-Cheng Ma; Yu Wang; Ling Zheng; Jun Fei; Wei Cao; De-Xiang Xu; Jin Yang; Hui Zhao; et al. (Journal of Hazardous Materials, 2025)

Construction of double S-scheme heterojunction in MIL-125(Ti)/ZnIn2S4/ZnS QDs to improve interfacial charge transfer and reduction potential for photocatalytic hydrogen production - Xiuxiu Huang; Shijian Zhang; Wenbin Ruan; Xinru Wang; Xiang Li; Shuangshuang Huai; Rui Cheng; Congliang Cheng; Ping Li; Jingjing Xia; Xiufang Wang (Fuel, 2025)

Multifunctional au-DTNB-ag nanoparticles immunoprobes based on color-Raman properties for lateral flow immunoassay detection of Glycinin - Peng Bo Huang; Jing Long Qu; Shuo Yang; Tian Jiao Shui; Huan Huan Yang; Li Ping Cheng; Yang Qin; Jun Xi (Food Chemistry, 2025)

A flexible and efficient UNITID-based access control (UBAC) model for environmental monitoring data - Jinku Huang; Changxiu Cheng; Bin Li; Yang Gao; Ping Li; Jiawei Wan; Jadunandan Dash (Environmental Modelling & Software, 2025)

Stiffness matters: Exploiting mechanotransduction to guide cellular behavior and potentiate cancer therapy - Jie Wang; Lin Long; Cheng Sun; Ping Li; Sheng Yao; Ning Wang; Jun Xiao (Chemical Engineering Journal, 2025)

The role of lactate metabolism in retinoblastoma tumorigenesis and ferroptosis resistance - Zhihui Zhang; Junjie Tang; Yaoming Liu; Yinghao Wang; Jinmiao Li; Yang Gao; Chao Cheng; Shicai Su; Shuxia Chen; Siming Ai; Ping Zhang; Rong Lu (Tissue and Cell, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Isolation of pentasaccharide resin glycosides from the whole plants of Ipomoea biflora and their cytotoxic activities - Jin-Ping Gu; Tian-Zi Qi; Dong-Rong Zhu; Xu-Jia He; Su-Peng Guo; Xin Lan; Hong Gu; Jia-Lie Luo; Min Yang; Yu-Cheng Gu; Wen-Li Wang; Guang-Tong Chen; et al. (Phytochemistry, 2025)

Machine learning analysis: Environmental and operational factors' influence on decay rate and organic sludge yield in full-scale wastewater treatment plants - Jinze Li; Lizhan Tang; Junyan Liu; Li-ping He; Li Gu; Shang Cheng; Yiyuan Wei; Binquan Jiao; Yongdong Chen (Journal of Water Process Engineering, 2025)

Traditional and novel organophosphate esters in atmosphere of greenhouse covered with mulch films: Seasonal variations, partitioning and exposure risks - Fang Zhao; Sinuo Tian; Jing Liu; Yingjun Wang; Guanglu Cui; Xuejiao Ha; Zhihong Ma; Hua Ping; Cheng Li (Journal of Hazardous Materials, 2025)

Revealing the Oxidative Stress-Related Molecular Characteristics and Potential Therapeutic Targets of Schizophrenia through Integrated Gene Expression Data Analysis - Xiu-Mei Zhu; Ji Chen; Hua-Jie Ba; Chun Yang; Jian-Wei Liu; Rui Guo; Shi-Lin Li; Ping Huang; Cheng-Tao Li; Su-Hua Zhang (Molecular Neurobiology, 2025)

Intercropping enhances the reciprocal facilitation of N and P uptake through complementarity - Hao-Yue Qin; Cheng-Bao Wang; Ping Wang; Si-Cun Yang; Xiao-Fei Li; Long Li (Plant and Soil, 2025)

The GLI3 may be involved in the damage process of Eimeria tenella to chicken cecal tissue - Wanjiang Xiang; Ying Chen; Ye He; Yongmei Yu; Ping Li; Bi Wang; Zhentao Cheng (Veterinary Parasitology, 2025)

Investigating fracture response characteristics and fractal evolution laws of pre-holed hard rock using infrared radiation: Implications for construction of underground works - Ze-Kun Zhang; Jin-Xing Lai; Zhan-ping Song; Yong-Li Xie; Jun-ling Qiu; Yun Cheng; Le Zhang (Tunnelling and Underground Space Technology, 2025)

Prediction method of train induced vibration source intensity based on generalized transfer function - Wuji Guo; Zhiping Zeng; Fushan Liu; Peicheng Li; Weidong Wang; Cheng Chang; Qiuyi Li; Ping Li (Soil Dynamics and Earthquake Engineering, 2025)

Exploring possible ancient applications of perilla: evidence from 3 million fruit remains from Han Dynasty tombs in China - Yun-Jun Bai; Ming Jiang; Xue-Ping Wei; Zhi-Jun Zhao; Xin-Ying Zhou; Hong-En Jiang; Tao Xie; Xiao-Lin Li; Yu-Yang Zhao; Xue Yan; Meng Cheng; Lu-Qi Huang; et al. (Science Bulletin, 2025)

Long-term settlement of deepsea pipelines on a soft clayey seabed: Poro-elasto-viscoplastic modeling - Jun Cheng; Jian Li; Fu-Ping Gao; Zhen-Yu Yin (Ocean Engineering, 2025)

A preliminary investigation of pore development mechanisms in highly matured solid bitumen: Implications from the Ediacaran Dengying Formation solid bitumen in the central Sichuan Basin, Southwest China - Lianqiang Zhu; Hui Tian; Peng Cheng; Haifeng Gai; Tengfei Li; Qin Zhou; Wei Wu; Chao Luo; Ping'an Peng (Marine and Petroleum Geology, 2025)

Effects of pore structures of carbon paper on water management capability of a proton exchange membrane fuel cell - Yu-Ting Liu; Guo-Bao Huang; Xiao-Fang Zhang; Ting-Ting Yao; Li-Xia Cheng; Hong Zhu; Gang-Ping Wu (Fuel, 2025)

A bionic yeast for the colon-targeted delivery of curcumin in the treatment of inflammatory bowel disease - Dunsheng Liang; Xiao-Fan Shen; Ting-Ting Li; Yao Deng; Hong-Liang Xiao; Zhi-Peng Li; Shuan-Cheng Bai; Xiao-Yu Ma; Xiao-ping Liao; Dong-Hao Zhao; Hao Ren; Chaoqun Zhang; et al. (Chemical Engineering Journal, 2025)

Mechanisms of SIRT1/SIRT3-mediated reduction of mitochondrial regeneration and inflammatory response in diabetic cerebral ischemia-reperfusion injury - Cheng Xin; Ouya Liu; Miao Sun; Ping Han; Xiaowen Li; Qingfeng Niu; Nenghong Ma; Xiao Yang; Changchun Hei; Ping Liu (Metabolic Brain Disease, 2025)

Cepharanthine mitigates NIBV-induced pyroptosis via the MDA5/NF-κB/NLRP3 signaling pathway - Zhenni Liu; Ruoyun Tang; Mengbing Ding; Meiqin Wu; Ying Li; Cheng Huang; Qiurong Qi; Ping Liu; Xiaona Gao; Xiaoquan Guo (Veterinary Microbiology, 2025)

Early Eocene Metasequoia and Taxodium (Cupressaceae) from Lingbao, Henan Province and their implication for a perhumid climate in central China - Ping Liu; Hui Jia; Li Xu; Yu Li; Ming-Yue Luo; Tian-Qi Dong; Jiao Huang; Cheng Quan (Palaeoworld, 2025)

Geothermal gas geochemistry in Southeast Tibetan Plateau margin influenced by magma chambers and fractures - Jia-Yi Wu; Hai Gang Cao; Peng Cheng Zhao; Yu Ping Guo; Xue-Gang Chen; Xiaohu Li; Jui-Fen Tsai; Pei-Ling Wang; Li-Hung Lin (Journal of Volcanology and Geothermal Research, 2025)

Designing flexible aliphatic linker based molecular imprinted covalent organic framework for rapid and selective extraction and detection of trace zearalenone - Li-Hong Su; Hai-Long Qian; Shu-Ting Xu; Cheng Yang; Zhenyu Wang; Xiu-Ping Yan (Journal of Hazardous Materials, 2025)

Fe-doped TiO2 nanosheet exposure accelerates the spread of antibiotic resistance genes by promoting plasmid-mediated conjugative transfer - Ping Cheng; Botao Wang; Qianyu Ji; Pingping Yuan; Shixin Gui; Shuying Liang; Lin Li; Hongwei Xu; Shaoqi Qu (Journal of Hazardous Materials, 2025)

Comparative mechanisms of PDS-activated antibiotic remediation in groundwater via controlled-release materials with different mesoporous catalysts - Ting Wang; Jing-le Chen; Rui Huang; Hua-li Chen; Cheng Hu; Gang Chen; Kou-ping Chen; Ji-chun Wu (Journal of Environmental Management, 2025)

Co-transport of polyethylene microplastics and antibiotic resistance genes in soil: Influencing factors, mechanisms, and control strategies - Xiao-Ming Lu; Li-Bo Lu; Xi-Cheng Huang; Xue-Ping Liu (Journal of Environmental Chemical Engineering, 2025)

Advanced materials for CO2 capture and storage: A comprehensive review of current progress and future prospects - Jun Wang; Linjin Li; Guangfei Qu; Minhua Cheng; Yuanchuan Ren; Ping Lu; Ting Zhang; Yaoze Wang; Fenghui Wu (Journal of Environmental Chemical Engineering, 2025)

Comparison of microwave-assisted and hot-air-drying method on the physicochemical properties and eating quality of rice bran noodles - Ping-Hsiu Huang; Yu-Tsung Cheng; Wen-Chien Lu; I-Yu Chiu; Chiun-Chung R. Wang; Po- Hsien Li (Food Bioscience, 2025)

Mass deposition of microbes from wildfire smoke to the sea surface microlayer - Siyao Yue; Yafang Cheng; Lishan Zheng; Senchao Lai; Shan Wang; Tianli Song; Linjie Li; Ping Li; Jialei Zhu; Meng Li; Lianfang Wei; Chaoqun Ma; et al. (Limnology and Oceanography, 2025)
Microbes in the sea surface microlayer (SML) are key to connecting the ocean and the atmosphere, affecting the exchange of matter, momentum, and heat at the interface. However, their sources have never been quantified systematically. Seawater has long been deemed their major source, whereas atmospheric deposition is regarded as trivial or merely providing additional nutrients. Here, combining atmospheric observations and quantitative budget analyses, we show that during the Indonesian peatland wildfire events the smoke can directly deposit abundant microbes into the SML, which can be comparable to the estimated supply from seawater and potentially diversify the microbial community of the SML. This land–air–ocean interaction is relevant for global climate, as it may induce previously unknown effects on the air–sea interactions, especially in an increasingly warming future with more intensifying wildfires.

Multi-Objective Optimization Based on Response Surface Methodology and Multi-Objective Particle Swarm Optimization for Pipeline Selection of Replenishment Oiler - Yujin Cong; Cheng Meng; Ming Yang; Yong Liu; Ping Yi; Tie Li; Shuai Huang (Journal of Marine Science and Engineering, 2025)
Ship pipeline selection, as a crucial component of ship pipeline design, is often a time-consuming process due to its high complexity. In this study, the response surface methodology combined with the multi-objective particle swarm optimization algorithm was used to optimize the fuel pipeline resistance and its space volume, aiming to select the optimal design scheme for an X-type replenishment oiler. Firstly, a one-dimensional pipeline system simulation model of a replenishment oiler was established based on the Flowmaster software (version 4.2_0 2020), and the fueling process was simulated. The simulation results were validated against the experimental results, and good agreements were obtained. Then, the response surface methodology was employed to establish regression models for the pipeline resistance, pipeline space volume, and imbalance degree of branch flows. Finally, multi-objective particle swarm optimization was used to optimize the target and select the optimal virtual solution from the Pareto front. Constrained by the international application standard, the optimal real solution was determined. Compared with the original scheme, the optimized scheme reduced the resistance by 3.57% for the #1 pipeline system and by 3.51% for the #2 pipeline system, respectively, and the space volume of the pipeline system was reduced by 5.72% while ensuring the flow balance.

Toxic effects of emerging pollutants on mucosal organs of teleost fish: A review focusing on mucosal microbiota, physical barrier and immune barrier - Jia-Ming Zhang; Ping Li; Cheng-Zhuang Chen; Ling Liu; Zhi-Hua Li (Science of The Total Environment, 2025)

Cascading environmental, phenological, and physiological influences on spatial variability of annual gross primary productivity in the Northern Hemisphere - Lang Han; Gui-Rui Yu; Zhi Chen; Qiu-Feng Wang; Xian-Jin Zhu; Wei-Kang Zhang; Tie-Jun Wang; Zhi-Feng Yan; Tian-You Zhang; Shi-Ping Chen; Hui-Min Wang; Jun-Hua Yan; et al. (Science of The Total Environment, 2025)

Study on seismic performance of steel frame beam-slab-column joint based on angle unilateral connection - Jie Yu; Jie Peng; Yu-Hang Wang; Wen- Wen Luo; Cheng-Yi Li; Li-Ping Wang (Engineering Structures, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Validation of Interaction Between Sugarcane miR167d and Predicted Target Gene ScPUM1 and Analysis of Their Expression Under Cold Stress: A Novel Mechanism of miR167d - Qiqi Song; Pengjin Zhu; Jiahui Li; Qin Cheng; Qinliang Tan; Quanguang Zhou; Ping Lv; Zemei Nong (Journal of Plant Growth Regulation, 2025)

Anti-hypoxia polyacetylenes and sesquiterpenoids from Codonopsis pilosula (Franch.) Nannf - Zhuo-Yang Cheng; Jun-Ge Jin; Meng Yan; Xin-Yue Chen; Jian-Kuan Li; Jian-Ping Gao; Jiang-Tao Zhou (Natural Product Research, 2025)

Model-informed Drug Development (MIDD) Approach to Support Biopharmaceutical Development of Iberdomide - Caroline Sychterz; Ping Chen; Ajay Saxena; Hongxia Lin; Lu Chen; Yan Li; Lu Gaohua; Yiming Cheng (The AAPS Journal, 2025)
Iberdomide is a BCS III CELMoD™ agent currently under development for treatment of multiple myeloma. Five formulations were used during clinical development, starting with active ingredient in gelatin capsule (AIC), followed by subsequent formulations in gelatin (F1), HPMC capsules (F2 and F3), and finally the intended commercial form (ICF). A food effect study with the Phase I AIC formulation showed no food effect and two relative bioavailability studies bridging from AIC to formulation F1 and F2 showed similar systemic exposure. Modeling and simulation, based on in vitro dissolution, was used to bridge gaps in clinical data to demonstrate lack of a food effect across all formulations including ICF. First, a previously developed population pharmacokinetic (PK) model showed that formulation was not a covariate on iberdomide PK. Then a physiologically-based pharmacokinetic model (PBPK) informed by in vitro biorelevant dissolution was used to mechanistically describe iberdomide absorption. While minor differences between formulations were noted in their in vitro dissolution, PBPK modeling showed lack of a food effect across all five formulations. Sensitivity analysis using the PBPK model demonstrated that iberdomide permeability and total amount of drug released from formulation are the most sensitive parameters in defining the systemic exposure of iberdomide, in agreement with iberdomide’s BCS III classification where drug release from drug product, and not solubility, is the rate-limiting step of dissolution. Based on the totality of evidence, which included clinical and in vitro data supplemented by modeling and simulation, no food effect is expected with the ICF. Graphical Abstract

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Cooperation of Lactoplantibacillus plantarum and polyethylene microplastics facilitated the disappearance of tetracycline during anaerobic fermentation of whole plant maize - Yubo Zhang; Pan Wang; Yu Tang; Chaosheng Liao; Xiaolong Tang; Pai Hou; Cheng Chen; Xiaokang Huang; Guangrou Lu; Lin Li; Mingjie Zhang; Fuxiang Li; et al. (Journal of Hazardous Materials, 2025)

The three-dimensional electrocatalytic oxidation system for refractory organic wastewater remediations: Mechanisms, electrode material and applications - Linjin Li; Yaoze Wang; Guangfei Qu; Ping Lu; Ting Zhang; Jun Wang; Minhua Cheng; Nanqi Ren; Yuanchuan Ren (Journal of Environmental Chemical Engineering, 2025)

A remotely triggered phase change hydrogel dressing for controlled release and promoting healing of infected wounds - Xiaolong Hu; Hongyan Zhang; Zuan-Tao Lin; Yu Chen; Hao Cheng; Bi-Huan Zhong; Yongli Li; Xiao-Ping Liao; Jian Sun; Mei X. Wu; Gang-Biao Jiang (Chemical Engineering Journal, 2025)

A review on the genus Melodinus: traditional uses, phytochemical diversity and pharmacological activities of indole alkaloids - Si-Fan Teng; Fang-Ru Li; Qi-Min Cui; Afsar Khan; Ting He; Xiao-Dong Luo; Ya-Ping Liu; Gui-Guang Cheng (Phytochemistry Reviews, 2025)

Dietary retinoic acid improved the growth, lipid metabolism and immune status in Macrobrachium rosenbergii - Qin-Cheng Huang; Li Wang; Zhi-Min Gu; Cui Liu; Tian-Tian Ye; Jun-Jun Yan; Ji-Lun Meng; Yu-Tong Zheng; Xian-Ping Ge; Zhi-Deng Lin; Guo-Yuan Zou (Frontiers in Marine Science, 2025)
The effect of dietary retinoic acid (RA) on the growth, lipid deposition, oxidation resistance, immunity, hepatopancreatic and intestinal health of Macrobrachium rosenbergii was evaluated. A total of 1200 prawns (0.22 ± 0.00 g) were divided into six groups and fed their corresponding feed containing 4, 132, 296, 562, 1206 or 2562 mg/kg dietary RA. The weight gain rate, specific growth rate and final body weight of the prawns changed linearly and quadratically, with the maximum observed in those fed 296 mg/kg dietary RA. Increasing dietary RA linearly and quadratically raised the RA content in the whole body. Compared to the prawns fed 4 mg/kg dietary RA, there was significantly lower lipid deposition in the muscle, hepatopancreas and whole body of prawns fed 296 mg/kg dietary RA. Prawns fed 296 mg/kg dietary RA had lower triglyceride (TG) content in the hepatopancreas with upregulated gene expression of retinoid X receptor ( RXR ), diacylglycerol acyltransferase 1 ( dgat1 ) and carnitine palmitoyltransferase 1 ( cpt1 ). Additionally, 296 mg/kg dietary RA increased the protein expression of RXR, CAMKKβ and phospho-AMPK. A dietary RA level of 296 mg/kg could decrease oxidative stress by upregulating the expression of peroxiredoxin 5 ( prx5 ) and improve immunity by upregulating expression of toll - like receptor 2 ( toll2 ), myeloid differentiation factor 88 (myd88 ) and dosal in the hepatopancreas. The intestinal health related genes ( crustin 2 / 3 / 4 , anti-lipopolysaccharide factor 1 / 7 , prx5 , peritrophin-1 , myosin light chain kinase , claudin , myd88 and dosal ) and morphological structure were also positively affected by dietary RA. Furthermore, dietary RA could relieve the immune responses induced by lipopolysaccharide, thus leading to lower transcription of antimicrobial peptides. In summary, dietary RA could improve the growth, lipid utilisation, antioxidant capacity and immunity of M . rosenbergii . To avoid the negative effects of excessive addition and obtain optimal growth, a diet containing 296 mg/kg dietary RA was suggested by the present study.

Regional abnormalities of white and gray matter in youths with conduct problems - Man Dong; Xiaodong Cheng; Yage Li; Shanling Ji; Hao Yu; Liangliang Ping; Chuanxin Liu; Cong Zhou (Brain Imaging and Behavior, 2025)

RIPK3 activation of CaMKII triggers mitochondrial apoptosis in NIBV-infected renal tubular epithelial cells - Ying Li; Qiurong Qi; Yifei Chen; Mengbing Ding; Manzi Huang; Cheng Huang; Ping Liu; Xiaona Gao; Xiaoquan Guo; Zhanhong Zheng (Veterinary Microbiology, 2025)

Urinary biomarkers of drinking water disinfection byproducts in relation to blood-based liver function parameters among reproductive-aged Chinese women - Ping-Ping Gui; Yan-Ling Deng; Min Zhang; Yu Miao; Peng-Hui Liu; Jia-Yue Zeng; Yang Wu; Cheng-Ru Li; Xiao-Ying Liu; Yang-Juan Li; Jin-Qin Zhu; A-Xue Liu; et al. (Science of The Total Environment, 2025)

Sex-specific effects of triphenyltin on gut microbiota and intergenerational effects in marine medaka (Oryzias melastigma) - Ping Li; Bian-Hao Zeng; Shu-Wen He; Bin Liu; Cheng-Zhuang Chen; Jian-Xue Feng; Ling Liu; Zhi-Hua Li (Journal of Hazardous Materials, 2025)

Large-deformation analyses of seismic landslide runout considering spatially random soils and stochastic ground motions - Shun-Ping Ren; Yang Li; Xue-Jian Chen; Po Cheng; Fei Liu; Kai Yao (Bulletin of Engineering Geology and the Environment, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Fire dynamics, fire generated pollutants, and acute health implications: A scaling law analysis of heavy-fuel-oil pool fires - Kuang-Chung Tsai; Li-Hsin Cheng; Chi-Fu Yeh; Tzu-Yan Tseng; Tzu-Ping Tseng; Li-Jen Huang; Shu-Hsing Yeh; Hui-Tsung Hsu; Ching-Ho Lin; Chin-Hsing Lai; Peter Brimblecombe; Ming-Jen Chen (Fuel, 2025)

Triptolide exposure triggers ovarian inflammation by activating cGAS-STING pathway and decrease oocyte quality in mouse - Si-Yao Cheng; Yi-Fan Yang; Ya-Long Wang; Zhao-Ping Yue; Yan-Zhu Chen; Wen-Ke Wang; Zhi-Ran Xu; Lin-Feng Li; Hao Shen; Zhi-Min Qi; Chang-Long Xu; Yu Liu (Food and Chemical Toxicology, 2025)

Corrigendum to “Application of Mo2C for enhancement of co-catalytic performance of Fe3+/PS based fenton-like reaction in degrading tetracycline hydrochloride” [Chem. Eng. J. 474 (2023) 145508] - Hao Cheng; Yi Wen; Chao Huang; Ping Wang; Chengyou Sun; Chongling Feng; Jialu Xu; Li Du; Ting Yan; Min Cheng (Chemical Engineering Journal, 2025)

Design and evaluation of C18 stationary phases with different polar-embedded groups for liquid chromatography - Xiao-Dong Cheng; Zheng Zhang; Yun-Ping Li; Xue-xin Dai (Analytica Chimica Acta, 2025)

Enhanced nano-LC-MS for analyzing dansylated oral cancer tissue metabolome dissolved in solvents with high elution strength - Ya-Ju Hsieh; Cheng-Yu Hung; Yi-Ting Chen; Yu-Tsun Lin; Kai-Ping Chang; Wei-Fan Chiang; Chih-Yen Chien; Chih-Ching Wu; Liang Li; Jau-Song Yu; Kun-Yi Chien (Analytica Chimica Acta, 2025)

Penicipyrrolizidinones A−C, three pyrrolizidinone alkaloids with unprecedented skeletons from the mangrove-derived fungus Penicillium sp. DM27 - Zhenling Chen; Jing-Jing Zhang; Cheng-Yun Huang; Wei-Chen Chen; Li-Ming He; Qing-Qing Tang; Kong-Kai Zhu; Jing Li; Ping Gao; Meng-Ke Zhang; You-Sheng Cai (Phytochemistry, 2025)

Effects of reclamation on the distribution and diversity of comammox along the coastal wetlands of China - Dongyao Sun; Yinghui Jiang; Hengchen Wei; Jun Li; Dengzhou Gao; Xianbiao Lin; Cheng Chen; Guoyu Yin; Yifei Zhang; Lijun Hou; Min Liu; Ping Han (International Biodeterioration & Biodegradation, 2025)

Petrogenesis of the unbrecciated pigeonite cumulate eucrite Northwest Africa 8326: Bridging the gap between eucrites and diogenites - Xiao-Wen Liu; Ai-Cheng Zhang; Li-Hui Chen; Lang Zhang; Xiao-Jun Wang; Jia Liu; Li-Ping Qin; Yu Liu; Qiu-Li Li; Xiao-Xiao Ling (Geochimica et Cosmochimica Acta, 2025)

Overall solar H2O2 generation in water and real seawater by covalent organic frameworks with kgd topology - Jie-Yu Yue; Li-Ping Song; Zi-Xian Pan; Min Cheng; Xuan Wang; Qing Xu; Peng Yang (Chemical Engineering Journal, 2025)

Varied chromosome distribution behaviours during meiosis in triploid Chinese chives contribute to the formation of viable pollen - Peng-Qiang Yao; Li-Hua Xie; Mei-Yu Li; Si-Qian Jiao; Shuai-Zheng Qi; Zhe Wang; Shi-Ping Cheng (Chromosome Research, 2024)

Ecological influences of sulfadiazine on rhizosphere soil microbial communities in ryegrass (Lolium perenne L.)-soil potting systems: Perspectives on diversity, co-occurrence networks, and assembly processes - Ping Li; Cheng-Zhuang Chen; Jin-Xin Wang; Ling Liu; Zhi-Hua Li (Science of The Total Environment, 2024)

Precipitation-induced biomass enhancement and differential allocation in Inner Mongolia's herbaceous and shrub communities - Xiangyun Li; Ya Hu; Zhaobin Song; Ping Cong; Huan Cheng; Xuebo Zheng; Wenjing Song; Ping Yue; Shaokun Wang; Xiaoan Zuo (Science of The Total Environment, 2024)

Kopsileuconines A−D: Bisindole alkaloids with cytotoxic activity from Kopsia hainanensis - Ni-Ping Li; Shan-Na Chen; Wei-Fang Su; Fen Liu; Lian-Jing Li; Jian-Guo Song; Min-Jing Cheng; Yi-Yi Li; Run-Qiang Chen; Xue-Ping Lei; Wen-Cai Ye; Lei Wang (Phytochemistry, 2024)

Multigenerational effects of combined exposure of triphenyltin and micro/nanoplastics on marine medaka (Oryzias melastigma): From molecular levels to behavioral response - Jian-Xue Feng; Bin Liu; Cheng-Zhuang Chen; Yu-Qing Ma; Cun-Long Wang; Ya-Nan Xu; Ling Liu; Ping Li; Zhi-Hua Li (Journal of Hazardous Materials, 2024)

Calixarene incorporated molecular imprinting on covalent organic framework for supramolecular recognition and specific extraction of citrinin - Li-Hong Su; Hai-Long Qian; Shu-Ting Xu; Cheng Yang; Xiu-Ping Yan (Journal of Hazardous Materials, 2024)

Advanced ceramic membranes: Novel strategies for sulfamethoxazole removal in wastewater treatment - Yen-Yi Lee; Guo-Ping Chang-Chien; I.-Cheng Li; Bo-Wun Huang; Minh-Ky Nguyen; Minh-Thuan Pham; Chien-Hsing Wu (Journal of Environmental Chemical Engineering, 2024)

EDDS application destabilizes soil organic matter in phytoremediation: Insights from quantity and molecular composition of dissolved organic matter - Yan-ping Zhao; Peng-ran Guo; Zhi-liang Chen; Jin-li Cui; Jian-xu Wang; Chao Chen; Hang Wei; Cheng Wang (Environmental Research, 2024)

A novel mutation in hERG gene associated with azithromycin-induced acquired long QT syndrome - Yun-Jiu Cheng; Yang Wu; Hui-Qiang Wei; Yi-Jian Liao; Li-Ping Qu; Yue-Han Pan; Li-Juan Liu; Wen-Tao Bi (Molecular Biology Reports, 2024)

Extracting hydromechanical properties of montmorillonite quasi-crystals via nanoindentation of oriented thin films - Yu-Cheng Li; Yong-Gui Chen; Li Liu; Guo-Ping Zhang; Wei-Min Ye; Qiong Wang (Applied Clay Science, 2024)

Maternal Serum Iodine Concentrations in Early Pregnancy Exhibited Well Diagnostic Ability for Thyroid Dysfunction, Inverse Associations with Gestational Weight Gain, and Birth Size: Longitudinal Analyses Based on Huizhou Mother-Infant Cohort - Zhao-min Liu; Huan-huan Long; Dan Li; Ai-ping Fang; Chao-gang Chen; Cheng Wang; Min-min Li; Yi Wu; Su-juan Zhang; Wen-jing Pan (Biological Trace Element Research, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

S-scheme 2D/2D B-doped N-deficient g-C3N4/ZnIn2S4 heterojunction for efficient H2 production intergrated with tertracycline degradation under visible-light illumination - Jiajia Liu; Yaodi Fu; Guoliang Chu; Ke Wen; Lingfang Qiu; Ping Li; Lihong Cheng; Banpeng Cao; Yi Tang; Xiangshu Chen; Hidetoshi Kita; Shuwang Duo (Process Safety and Environmental Protection, 2024)

Physical and mechanical characterization of solid waste collected from rural areas of China: Experimental study - Yu-Ping Li; Baoyun Fan; Le Cheng; Jianyong Shi; Xiulei Li; Lianghu Su; Zeeshan Khursheed (Process Safety and Environmental Protection, 2024)

Conjugation-regulated lateral and stereoelectronic effects in single-molecule junctions - Xiao Wei; Xuanhao Cao; Jie Hao; Xinyue Chang; Ping Duan; Li Cheng; Keqiu Chen; Jinying Wang; Chuancheng Jia; Xuefeng Guo (Chemical Engineering Journal, 2024)

Comparative transcriptome analysis reveals the immune defense mechanism of the red swamp crayfish (Procambarus clarkii) in response to Vibrio parahaemolyticus challenge - Xiang Lu; Sheng Tang; Xin Liu; Jun-Jie Jiang; Dan-Dan Bian; Dai-Zhen Zhang; Qiu-Ning Liu; Yong-Xu Cheng; Bo-Ping Tang; Li-Shang Dai (Aquaculture, 2024)

Occurrence and maturation transformation of organic and inorganic nitrogen in the Lower Cambrian shelf–slope facies shale: Implications for overmature N2-rich shale reservoirs in Southern China - Guangming Meng; Haifeng Gai; Xiumin Yang; Ping Gao; Qin Zhou; Chengang Lu; Gang Li; Xing Wang; Peng Cheng (Marine and Petroleum Geology, 2024)

Genesis of high-Al chromitites from Xiaosuihe peridotite (Central Jilin Province, NE China): Implication for initial subduction of the Paleo-Asian ocean - Bing-Qian Ding; Fu-Ping Pei; Jing-Yang Wei; Jin-Rui Zhang; Zi-Cheng Guan; Kai Song; Tian-Jiao Sang; Peng-Yi Li (Lithos, 2024)

Multi-scenario application of chitosan emulsions as fat replacers: Based on the regulation of chitosan hydrophobicity and emulsion rheological properties - Cheng-Zhen Nie; Yao Li; Xu-Hui Huang; Hao-Peng Wang; Xu-Song Wang; Xiu-Ping Dong; Bei-Wei Zhu; Lei Qin (Food Hydrocolloids, 2024)

Mitigating nitrite inhibition in Klebsiella strain denitrification: Stimulating endogenous driving force with microscale zero-valent iron - Wen-ying Cao; Kuang-di Xu; Su Zhang; Si-jia Li; Yi-cheng Yuan; Jing-xuan Lu; Lei Yu; Shao-hua Zhou; Jun-ting Gan; Quan Wang; Rong-ping Chen; Ke Yin (Chemical Engineering Journal, 2024)

Mn doping and core-shell engineering of silane-modified Mn-TiO2@SiO2 nanoparticles with drastically reduced photocatalytic activity for transparent UV-shielding hybrid materials - Xiangyu Tian; Xinuo Cai; Zixu Zeng; Yi He; Xijun Xu; Lecheng Lei; Cheng Xu; Xin Xu; Yongfeng Xu; Ping Li; Xingwang Zhang (Chemical Engineering Journal, 2024)

Prevalence and molecular characteristics of intestinal pathogenic Escherichia coli isolated from diarrheal pigs in Southern China - Qian Li; Jing-Jing Dai; Shu-Yi Chen; Ruan-Yang Sun; Dong Wang; Shuan-Cheng Bai; Min-Ge Wang; Jian Sun; Xiao-Ping Liao; Ya-Hong Liu; Liang-Xing Fang (Veterinary Microbiology, 2024)

Vinorelbine administration impedes the timely progression of meiotic maturation and induces aneuploidy in mouse oocytes - Si-Yu Cheng; Zi-Yun Yi; Chun-Hui Zhang; Qing-Yuan Sun; Wei-Ping Qian; Jian Li (Reproductive Toxicology, 2024)

Avermectin induced vascular damage in zebrafish larvae: association with mitochondria-mediated apoptosis and VEGF/Notch signaling pathway - Wei-Guo Wang; Xu-Feng Jiang; Cheng Zhang; Xiu-Ping Zhan; Jia-Gao Cheng; Li-Ming Tao; Wen-Ping Xu; Zhong Li; Yang Zhang (Journal of Hazardous Materials, 2024)

Trade-offs of reproductive growth and Cd remobilization regulated Cd accumulation in wheat grains (Triticum aestivum L.) - Ying Wang; Pei-Pei Gao; Yu-Meng Shang; Rong-Rong Jia; Yu-Cheng Wang; Xiang-Yu Li; Li-Ping Geng; Yong Zhao; Joshua Walrath; Wen-Ju Liu (Journal of Hazardous Materials, 2024)

Co2+ coordination-assisted molecularly imprinted covalent organic framework for selective extraction of ochratoxin A - Li-Hong Su; Hai-Long Qian; Cheng Yang; Xiu-Ping Yan (Journal of Hazardous Materials, 2024)

Wastewater-based epidemiology to monitor 68 NPS/conventional drug use in Taipei metropolitan area in Taiwan during and after COVID-19 pandemic - Te-Tien Ting; Pin-Chuan Chen; Ya-Chi Chang; Pin-Ju Chiang; Hsu-Cheng Li; Shih-Hsun Chen; Pei-Chieh Chen; Hai-Tien Chu; Ping-Yu Chuang; Yi-Hsin Liu; Pai-Shan Chen (Journal of Hazardous Materials, 2024)

Rapid and non-destructive identification of Panax ginseng origins using hyperspectral imaging, visible light imaging, and X-ray imaging combined with multi-source data fusion strategies - Jiacong Ping; Zehua Ying; Nan Hao; Peiqi Miao; Cheng Ye; Changqing Liu; Wenlong Li (Food Research International, 2024)

Tuning the planarity of molecularly imprinted covalent organic frameworks for selective extraction of ochratoxin A in alcohol samples - Hao-Ze Li; Hai-Long Qian; Shu-Ting Xu; Cheng Yang; Xiu-Ping Yan (Food Chemistry, 2024)

Natural pyrethrins induce cytotoxicity in SH-SY5Y cells and neurotoxicity in zebrafish embryos (Danio rerio) - Wei-Guo Wang; Shou-Lin Li; Bin Liu; Ning Tang; Cheng Zhang; Xu-Feng Jiang; Li-Ming Tao; Wen-Ping Xu; Yang Zhang (Environmental Research, 2024)

Corrigendum to “2′-O-galloylhyperin attenuates LPS-induced acute lung injury via upregulation antioxidation and inhibition of inflammatory responses in vivo” [Chem. Biol. Interact. 304 (1 May 2019) 20–27] - Sun-Dong Zhang; Peng Wang; Jing Zhang; Wei Wang; Li-Ping Yao; Cheng-Bo Gu; Thomas Efferth; Yu-Jie Fu (Chemico-Biological Interactions, 2024)

Water flush boosts performance of elemental sulfur-based denitrification packed-bed systems: Optimization and mechanisms - Jia-Min Xu; Heng Dong; Hao-Ran Xu; Yi-Lu Sun; Yang Yu; Li-Ying Zhang; Gen-Ping Yi; Wen-Ke He; Chang-Min Wu; Ai-Jie Wang; Hao-Yi Cheng (Bioresource Technology, 2024)

Molecular Cloning and Functional Analysis of ScHAK10 Gene Promoter from Sugarcane (Saccharum officinarum L.) - Hai-Bin Luo; Cheng-Mei Huang; Hui-Qing Cao; Yuan-Wen Wei; Lin Xu; Kai-Chao Wu; Zhi-Nian Deng; Xing-Jian Wu; Li-Ping Ye; Xiao-Ping Yi (Tropical Plant Biology, 2024)

Exosomal GDNF from Bone Marrow Mesenchymal Stem Cells Moderates Neuropathic Pain in a Rat Model of Chronic Constriction Injury - Xuelei Zhang; Huan Liu; Xiaolei Xiu; Jibo Cheng; Tong Li; Ping Wang; Lili Men; Junru Qiu; Yanyan Jin; Jianyong Zhao (NeuroMolecular Medicine, 2024)

Exploring seasonal variations, assembly dynamics, and relationships of bacterial communities in different habitats of marine ranching - Cheng-Zhuang Chen; Ming-Hao Yin; Lin-Jing Niu; Jin-Xin Wang; Ling Liu; Yong-Jun Sun; Wen-Ming Ju; Ping Li; Zhi-Hua Li (Marine Pollution Bulletin, 2024)

Structural characterization of modified soy protein isolate composite coatings and its application on fresh-cut cantaloupe (Cucumis melo cv. Xiaomi) - Tian Yang; Dan-Dan Zhou; Cai-E Wu; Ting-Ting Li; Gong-Jian Fan; Xiao-Jing Li; Kai-Ping Cong; Zhi-Cheng Yan; Xin Cheng (Food Bioscience, 2024)

A Test System for Microwave-Assisted Dual-Mode Mechanical Cutting of Hard Rock Under True Triaxial Compression - Xia-Ting Feng; Xiang-xin Su; Cheng-xiang Yang; Feng Lin; Shi-ping Li; Jiu-yu Zhang; Tian-yang Tong (Rock Mechanics and Rock Engineering, 2024)
This paper introduces a test system for microwave-assisted dual-mode mechanical cutting of hard rock under true triaxial compression. The test system was developed by Northeastern University, China, to simulate the cutting and breaking of hard rock by a tunnel boring machine (TBM). The test system is mainly composed of a dual-mode mechanical cutting subsystem, a true triaxial loading subsystem and a high-power microwave presplitting subsystem. The system performs dual-mode cutting under true triaxial stress, applies a single sensor to monitor the three-dimensional force of the cutter head, and integrates the reduction in the vibration and resistance to torsion during the cutting process. Mechanical cutting tests of basalt under different amounts of microwave irradiation and true triaxial stress conditions were conducted in Chifeng, Inner Mongolia, China. The results showed that microwave radiation presplitting effectively improved the efficiency of mechanical rock breaking. However, after 180 s of microwave irradiation, true triaxial high stress inhibited the mechanical breaking of basalt in terms of the overall excavation depth. During the tests, each system performed stably. The test results verified the reliability of the test system.

Wearable solid-phase microextraction sampling for enhanced detection of volatile analytes in human ears - Wenzheng Mo; Lei Li; Bi-Cheng Yang; Xiangjie Wang; Baixue Wang; Jianfeng Zhang; Qiaoyun Huang; Zhong-Ping Yao; Dong Zhang; Bin Hu (Analytica Chimica Acta, 2024)

Role of ginsenoside Rb1 in attenuating depression-like symptoms through astrocytic and microglial complement C3 pathway - Cheng-Fu Li; Qiu-Ping Zhang; Jie Cheng; Guang-Hui Xu; Ji-Xiao Zhu; Li-Tao Yi (Metabolic Brain Disease, 2024)

An engineered DNA aptamer-based PROTAC for precise therapy of p53-R175H hotspot mutant-driven cancer - Lingping Kong; Fanlu Meng; Ping Zhou; Ruixin Ge; Xiaoshan Geng; Zhihao Yang; Guo Li; Linlin Zhang; Jing Wang; Jinfeng Ma; Cheng Dong; Jun Zhou; et al. (Science Bulletin, 2024)

Effects of different thawing methods on physical and physicochemical properties of frozen dough and quality of corresponding steamed bread - Fan Zhang; Jinying Guo; Peiyao Li; Fen Zhao; Xue Yang; Qiaofen Cheng; J. Stephen Elmore; Ping Wang; Can Cui (Food Chemistry, 2024)

GHK-Cu/Pionin-loaded in situ electrospun PVB/PVP smart dressing promotes wound healing via anti-oxidant, anti-inflammatory, antimicrobial, and tissue regenerative effects - Yan Wang; Zhichao Zheng; Janak L. Pathak; Haoyu Cheng; Sizhen Huang; Zi Fu; Ping Li; Lihong Wu; Huade Zheng (Chemical Engineering Journal, 2024)

sp2-c linked Cu-based metal-covalent organic framework for chemical and photocatalysis synergistic reduction of uranium - Jin-Lan Liu; Mu-Xiang Lin; Juan Huang; Cheng-Rong Zhang; Jia-Xin Qi; Yuan-Jun Cai; Xiao-Juan Chen; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

Formation of secondary organic aerosols from Cl-initiated oxidation of anisole: Rapid release of ultrafine particles and organic chlorides - Fashuai Pan; Jiaoyang Ma; Qianqian Yan; Gaosheng Zhao; Bin Jia; Li Xu; Ping Cheng (Atmospheric Environment, 2024)

Biosafety assessments of hexafluoropropylene trimer derivative as a fluorinated cooling fluid for electronics - Yi-Tong Zhou; Pei-Jie Zhang; Shu-Ping Wang; Chang-Hao Li; Jia-Qing Zhang; Wei-Xin Zhang; Yuan-Di Zhao; Yuan-Cheng Cao; Jin-Xuan Fan (Toxicological Research, 2024)

Evaluation and projection of circulation conditions tied to summertime compound drought and heatwave frequency over the Yangtze River Delta, China, for the carbon neutrality period based on CMIP6 GCMs - Jing Wang; Ping Liang; Fei Cheng; Yanju Liu; Chengyu Song; Wei Wu; Qingfeng Zheng; Tianyu Zhang; Ping Qu; Yujie Li; Yihui Ding (International Journal of Climatology, 2024)
Frequent occurrences of compound droughts and heatwaves (CDHWs) may have considerable adverse impacts on human health and socioeconomic development. To project future summertime CDHWs over the Yangtze River Delta (YRD) of China under carbon neutrality (CN) for policymakers, we used nine global climate models (GCMs) from the Coupled Model Intercomparison Project Phase 6 (CMIP6) and evaluated and projected circulation conditions tied to the summer YRD CDHW frequency in the boreal summer. The results show that a marked mid‐tropospheric regional‐scale anticyclonic anomaly centred over the East China Sea can be deemed the dominant system linking the more frequent occurrence of YRD CDHWs. Our selected nine CMIP6 GCMs better captured the observed climatological and anomalous spatial circulation patterns connected to the summer YRD CDHW frequency. Moreover, the nine models' multi‐model ensemble mean (9MME) was better than most of the individual models regarding the related climatological circulation simulations. The 9MME‐projected changes in circulation conditions tied to summer YRD CDHWs during the carbon neutrality period (2050–2060) under SSP119 favour the comparable occurrence of the YRD with that for the same period under the medium greenhouse gas (GHG) warming scenario (SSP245), but the intensities of the CDHWs are the least severe. However, the highest number of YRD CDHWs is driven by the high GHG warming scenario (SSP585), and these CDHWs feature the most severe intensity. Our research identified a new paradigm regarding the frequency and intensity of the summer YRD CDHW under SSP119, highlighting the potential role of the newly accessible CN‐oriented sustainable development pathway in alleviating compound extremes.

The origins of odor (β-cyclocitral) under different water nutrient conditions: Algae or submerged plants? - Yu Lin; Chaoyue Cheng; Yutai Dai; Weijie Li; Jiping Chen; Mo Chen; Ping Xie; Qiang Gao; Xiaoyue Fan; Xuwei Deng (Science of The Total Environment, 2024)

Human health risk assessment and toxic effect of heavy metal(loid)s in Bamboo shoot products - Yu-Mei Xie; Meng-Yan Zhang; Fei-Peng Liu; Cheng-Chen Wang; Wen-Yuan Dong; Chun-Mei Xu; Xin Li; Wu-Mei Xu; Ping Xiang (Journal of Environmental Chemical Engineering, 2024)

Physicochemical properties of Dioscorea alata Tainung No. 1 and 2 via different drying methods and application on the frozen tangyuan - Ping-Hsiu Huang; Yu-Tsung Cheng; Shu-Ju Chen; Wen-Chien Lu; Po-Yuan Chiang; Wen-Pei Cheng; Chiun-Chuang R. Wang; Po-Hsien Li (Food Bioscience, 2024)

Environmentally relevant concentrations of benzophenones exposure disrupt intestinal homeostasis, impair the intestinal barrier, and induce inflammation in mice - Yu-Jia Lin; Hong-Mei Li; Yan-Rong Gao; Ping-Fan Wu; Bin Cheng; Chen-Long Yu; Yu-Xin Sheng; Hai-Ming Xu (Environmental Pollution, 2024)

Karyotype analysis of Chinese chive germplasms with different ploidy levels and their evolutionary relationships - Peng-Qiang Yao; Jian-Hua Chen; Pei-Fang Ma; Li-Hua Xie; Jiang Shi; Shi-Ping Cheng (Genetic Resources and Crop Evolution, 2024)

Occurrence, potential sources, and ecological risks of traditional and novel organophosphate esters in facility agriculture soils: A case study in Beijing, China - Fang Zhao; Hua Ping; Jing Liu; Tianyu Zhao; Yingjun Wang; Guanglu Cui; Xuejiao Ha; Zhihong Ma; Cheng Li (Science of The Total Environment, 2024)

Artificial microbial consortia engineering: Intensify nitrogen removal from mature landfill leachate by simultaneous nitrification and denitrification - Xia Ke; Yi-Xin Li; Ting-Ting Guo; Zu-Lian Liao; Su-Qin Tang; Yi-Cheng Zhang; Shi-Peng Zhou; Ya-Ping Xue; Yu-Guo Zheng (Journal of Water Process Engineering, 2024)

A highly-efficient locally encoded boundary scheme for lattice Boltzmann method on GPU - Zehua Zhang; Cheng Peng; Chengxiang Li; Hua Zhang; Tao Xian; Lian-Ping Wang (Computer Physics Communications, 2024)

Core-shell DOPO/caramel nano-polymer with desirable UV shielding and flame retardancy for polyamide 6 fabric - Wen-Jie Jin; Xian-Wei Cheng; Sheng-Nan Ma; Ling Li; Rui-Kai Wu; Jin-Ping Guan (Chemical Engineering Journal, 2024)

Phosphorylated covalent organic framework/graphene composites for photoelectrothermal integrated collaborative reduction of uranium - Rui Zhang; Liang Tao; Cheng-Peng Niu; Cheng-Rong Zhang; Tie-Ying Shi; Xiao-Xing Wang; Ying-Ao Wang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

Enhancing biohydrogen production from xylose through natural FeS2 ore: Mechanistic insights - Yun Xu; Miao-yu Deng; Si-jia Li; Yi-cheng Yuan; Hao-yu Sun; Quan Wang; Rong-ping Chen; Lei Yu (Bioresource Technology, 2024)

A bipolar SMPS network for measuring atmospheric aerosols using natural air ions - Yiran Li; Jin Wu; Hao Wu; Xiaomeng Liu; Qi Zhou; Yiqun Lu; Yuhang Wu; Mengyu Liu; Hengjia Ou; Shixin Mai; Xuehui He; Huaying Song; et al. (Atmospheric Environment, 2024)

A New Perspective on the Semi-quantitative Meso-structural Failure Mechanism of Deep Weak Interlayer Zone Under Different Stress Paths - Shu-Qian Duan; Po Gao; Ding-Ping Xu; Bei Cao; Guo-feng Liu; Quan Jiang; Shi-Li Qiu; Jie-Cheng Xiong (Rock Mechanics and Rock Engineering, 2024)

Simultaneous and on-line detection of organic and heavy metal components in water using a novel nebulization-assisted injection plasma ionization triple quadruple mass spectrometry instrument - Gaosheng Zhao; Maolin Yang; Tingting Zhang; Bin Jia; Li Xu; Ping Cheng (Analytica Chimica Acta, 2024)

Drought shortens subtropical understory growing season by advancing leaf senescence - Huanfa Sun; Liming Yan; Zhao Li; Wanying Cheng; Ruiling Lu; Xingli Xia; Jiaye Ping; Chenyu Bian; Ning Wei; Cuihai You; Songbo Tang; Ying Du; et al. (Global Change Biology, 2024)
Subtropical forests, recognized for their intricate vertical canopy stratification, exhibit high resistance to extreme drought. However, the response of leaf phenology to drought in the species‐rich understory remains poorly understood. In this study, we constructed a digital camera system, amassing over 360,000 images through a 70% throughfall exclusion experiment, to explore the drought response of understory leaf phenology. The results revealed a significant advancement in understory leaf senescence phenology under drought, with 11.75 and 15.76 days for the start and end of the leaf‐falling event, respectively. Pre‐season temperature primarily regulated leaf development phenology, whereas soil water dominated the variability in leaf senescence phenology. Under drought conditions, temperature sensitivities for the end of leaf emergence decreased from −13.72 to −11.06 days °C −1 , with insignificance observed for the start of leaf emergence. Consequently, drought treatment shortened both the length of the growing season (15.69 days) and the peak growth season (9.80 days) for understory plants. Moreover, this study identified diverse responses among intraspecies and interspecies to drought, particularly during the leaf development phase. These findings underscore the pivotal role of water availability in shaping understory phenology patterns, especially in subtropical forests.

Analysis of factors influencing the energy efficiency in Chinese wastewater treatment plants through machine learning and SHapley Additive exPlanations - Jinze Li; Zexuan Du; Junyan Liu; Linji Xu; Li-ping He; Li Gu; Hong Cheng; Qiang He (Science of The Total Environment, 2024)

A new salinity-based model for Cryogenian Mn-carbonate deposits - Wei Wei; Wenchao Yu; Yuansheng Du; Thomas J. Algeo; Zhiquan Li; Meng Cheng; Ping Wang; Jingyu Zhang; Leslie J. Robbins; Kurt Konhauser (Precambrian Research, 2024)

Sesquiterpenes from Inula macrophylla and their anti-neuroinflammatory activity - Rui Ma; Bakhrom Komilov; Cheng-Bo Wang; Komila Alibekovna Eshbakova; Jun-Li Yang; Wei Ha; Yan-Ping Shi (Phytochemistry Letters, 2024)

Integrating molecular imprinting into flexible covalent organic frameworks for selective recognition and efficient extraction of aflatoxins - Li-Hong Su; Hai-Long Qian; Cheng Yang; Chuanxi Wang; Zhenyu Wang; Xiu-Ping Yan (Journal of Hazardous Materials, 2024)

Excellent dimensional stability anion exchange membrane based on PVA/EVOH/PyPECH for acid recovery by diffusion dialysis - Yifei Gong; Haiyang Shen; Hua Zhao; Yueyue Zhang; Ping Li; Congliang Cheng (Journal of Environmental Chemical Engineering, 2024)

Nickel phosphide cocatalyst and carbon defects simultaneously boosting the photocatalytic hydrogen production over carbon nitride - ChuChang Mao; Qinghua Qu; Fada Li; Cheng Fang; Hongping Li; Jing Ding; Hui Wan; Ping Zhang; Guofeng Guan (Journal of Environmental Chemical Engineering, 2024)

Application of g-C3N4-based photocatalysts for N2 photofixation - Longjian Li; Ping Zhang; Ning Li; Tuerhong Reyila; Yongchong Yu; Xiaoping Su; Cheng Peng; Lijuan Han (Journal of Environmental Chemical Engineering, 2024)

Molecular mechanism of efficient degradation of TPM dyes by Serratia species WKD at high temperature - Yi Wei; Xin-Jiao Dong; Gang Li; Huan Wu; Lin-Na Du; Jia-Cheng Zhou; Jun Zhang; Yan-Ping Xiao; Yue-Mei Shang; Hong-Xia Liu (International Biodeterioration & Biodegradation, 2024)

Self-floating, monolithic, and aligned phenolic carbon aerogels from coal tar for solar-driven evaporation - Hong-Lei Yan; Jin-Yuan Cheng; Zhan-Ku Li; Jing-Chong Yan; Wei-Dong Zhang; Zhi-Ping Lei; Shi-Biao Ren; Zhi-Cai Wang; Heng-Fu Shui (Fuel, 2024)

Environmental performance of unfired bricks produced from co-disposal of mine tailings and municipal solid waste incineration fly ash based on comprehensive leaching tests - Ping Wang; Jiangshan Li; Yuanan Hu; Hefa Cheng (Environmental Pollution, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Effects of the Glucocorticoid-Mediated Mitochondrial Translocation of Glucocorticoid Receptors on Oxidative Stress and Pyroptosis in BV-2 Microglia - Ruonan Dang; Xuyang Hou; Xinglan Huang; Caifeng Huang; Xiaoqing Zhao; Xingrong Wang; Ning Zhang; Yuqi Yang; Nan Li; Sheng Liu; Peng Yan; Ping Fan; et al. (Journal of Molecular Neuroscience, 2024)

Exploring the antiviral potential of paeonol from medicinal plants: A promising strategy for controlling white spot syndrome virus - Cheng Chen; Chang-Shuai Liang; Xiang-Yu Qu; Peng-Fei Li; Xiao-Ping Tan; Fei Ling; Gao-Xue Wang (Aquaculture, 2024)

Microbial colony sequencing combined with metabolomics revealed the effects of chronic hexavalent chromium and nickel combined exposure on intestinal inflammation in mice - Yueming Gu; Shuangyan Zheng; Cheng Huang; Xianhong Cao; Ping Liu; Yu Zhuang; Guyue Li; Guoliang Hu; Xiaona Gao; Xiaoquan Guo (Science of The Total Environment, 2024)

Potential of perennial sorghum for biogas production: Pretreatment with yeast-contained inoculants during anaerobic storage - Xiaolong Tang; Chaosheng Liao; Shufeng Zhou; Cheng Chen; Lin Li; Guangrou Lu; Xiaokang Huang; Mingjie Zhang; Chao Chen; Ping Li (Fuel, 2024)

Unravelling hidden threats of water disinfection: Toxicity evaluation and toxic products identification during diclofenac degradation - Ding Pan; Cheng Zhang; Cai-Shan Wang; Peng Zhang; Xin-Yi Jiao; Qian-Ru Ma; Li-Ting Wang; Dai-Jun Li; Li-Ping Li (Environmental Pollution, 2024)

Brittleness ductility transition depth of new fracture in the Baodi Miaozhuang Uplift - He Li; Yi-Bing Dong; Yi-Xi Wang; Wu-Ping Gao; Cheng-Guo Yan; Ling-Ling Cai; Bo-Yang Wu; Peng Zhao (Applied Geophysics, 2024)

A system dynamics simulation-based strategic analysis of integrated water resources utilization and management in Shenzhen city - Guangzhi Zheng; Jing-Cheng Han; Ping Li; Bing Li; Xiaofeng Wu; Yuefei Huang; Muhammad Ahmad (Environmental Science and Pollution Research, 2024)

Degradation mechanism of antibiotics by flower-like Bi2S3 sensitized anatase/rutile TiO2 coupled with SiO2 photonic crystals - Ruizhen Liu; Huaiyuan Jiang; Ping Li; Jianfei Yin; Zhengrui Xu; Xiaoyu Chen; Jian Cheng; Shuangxi Gu; Renliang Lyu (Journal of Water Process Engineering, 2024)

Shale oil potential and mobility in low- to medium-maturity lacustrine shales: A case study of the Yanchang Formation shale in southeast Ordos Basin, China - Huairen Cao; Jun Shi; Zhao-Wen Zhan; Hao Wu; Xiaoyu Wang; Xin Cheng; Haolin Li; Yan-Rong Zou; Ping'an Peng (International Journal of Coal Geology, 2024)

Physical, textural and crystallization properties of ground nut oil-based diacylglycerols in W/O margarine system - Wanting Ke; Yee-Ying Lee; Jianqiang Cheng; Chin-Ping Tan; Oi-Ming Lai; Aijun Li; Yong Wang; Zhen Zhang (Food Chemistry, 2024)

Micro(nano)plastics in marine medaka: Entry pathways and cardiotoxicity with triphenyltin - Ling Liu; Ren-Yan Du; Ruo-Lan Jia; Jin-Xin Wang; Cheng-Zhuang Chen; Ping Li; Ling-Ming Kong; Zhi-Hua Li (Environmental Pollution, 2024)

Deciphering the role of hydraulic retention time (HRT) in integrated fixed-film activated sludge (IFAS) system under aniline stress: Effects on microbial succession and communication - Nan-ping Wu; Bin Tan; Meng Li; Naif Abdullah Al-Dhabi; Bing Lin; Qi He; Hao-nan Shen; Jia-jing Cheng; Wangwang Tang; Qian Zhang (Chemical Engineering Journal, 2024)

Fluorogenic RNA aptamer output sensors via transcription activated by recombinase polymerase amplification for nucleic acid testing - Jiajie Liang; Xin Liu; Wei Xiao; Peijun Teng; Ping Guan; Wanli Liang; Liangshan Hu; Guanbo He; Haorong He; Gan Li; Siyi Zou; Cheng Lu; et al. (Chemical Engineering Journal, 2024)

Sibship analysis revealed the reproductive strategy and current population status of the silver carp (Hypophthalmichthys molitrix) from the middle and lower reaches of the Yangtze River, China - Ping Yang; Cheng Chen; Dan Yu; Minzheng Li; Huanzhang Liu (Conservation Genetics, 2024)

Whole-Transcriptome Analysis Reveals the RNA Profiles in Mouse Bone Marrow Mesenchymal Stem Cells or Zebrafish Embryos After Exposure to Environmental Level of Tributyltin - Ping Li; Cheng-Zhuang Chen; Ling Liu; Zhi-Hua Li (Bulletin of Environmental Contamination and Toxicology, 2024)

Adequate nutrient intake mitigate the toxic effects of bromate on the rotifer Brachionus calyciflorus - Tao Chen; Xiao-Ping Xu; Jin-Cheng Li; Kai-Yan Tao; Chang-Shuang Zhao (Environmental Science and Pollution Research, 2024)

MiRNAs enabled Golden pompano (Trachinotus blochii) in response to different reoxygenation patterns after hypoxic stress - Tian Jiang; Jun Long Sun; Chun Xiu Jin; Yu Zhang; Zai Hui Tong; Yue Gu; Fu Cheng Yao; Li Ping Shi; Fei Biao Song; Jian Luo (Aquaculture, 2024)

Biodegradation of sulfadiazine by ryegrass (Lolium perenne L.) in a soil system: Analysis of detoxification mechanisms, transcriptome, and bacterial communities - Jin-Xin Wang; Ping Li; Cheng-Zhuang Chen; Ling Liu; Zhi-Hua Li (Journal of Hazardous Materials, 2024)

Highly efficient activation of periodate by a manganese-modified biochar to rapidly degrade methylene blue - Jiamin Gong; Honghui Jiang; Xiang Li; Hao Cheng; Ziqi Wang; Jingju Cai; Meifang Li; Ping Wang; Hui Wang; Xi Hu; Xinjiang Hu (Environmental Research, 2024)

Preparation and characterization of lotus root starch based bioactive edible film containing quercetin-encapsulated nanoparticle and its effect on grape preservation - Ya-Fan Zeng; Ying-Ying Chen; Yuan-Yuan Deng; Chao Zheng; Cheng-Zhi Hong; Qiang-Ming Li; Xue-Fei Yang; Li-Hua Pan; Jian-Ping Luo; Xue-Ying Li; Xue-Qiang Zha (Carbohydrate Polymers, 2024)

Vector-mediated viral exchange between crops and weedy plants - Xiao-bin Shi; Zhuo Zhang; Fan Li; Evan L. Preisser; Li-ping Huang; De-yong Zhang; Zhan-hong Zhang; Song-bai Zhang; Xu-guo Zhou; An-sheng Zhang; Hui Liu; Yuan-hua Wu; et al. (Journal of Pest Science, 2024)

The effects of Spinosad on zebrafish larvae and THP-1 cells: Associated with immune cell damage and NF-kappa B signaling pathway activation - Wei-Guo Wang; Shou-Qian Xiong; Jin Lu; Lian-Hua Zhu; Cheng Zhang; Jia-Gao Cheng; Zhong Li; Wen-Ping Xu; Li-Ming Tao; Yang Zhang (Chemosphere, 2023)

Clarification of the phosphorus release mechanism for recovering phosphorus from biofilm sludge in alternating aerobic/anaerobic biofilm system - Hao Zhang; Shuang-Shuang Zhang; Wei Zhang; Wu-Cheng Ma; Yang Pan; Lin Chen; Liang Zhu; Yi-Ping Li; Jing-Ru Li (Science of The Total Environment, 2023)

The MPK6-LTF1L1 module regulates lignin biosynthesis in rice through a distinct mechanism from Populus LTF1 - Ping Zhu; Yu Zhong; Laifu Luo; Junhui Shen; Jiayan Sun; Laigeng Li; Longjun Cheng; Jinshan Gui (Plant Science, 2023)

Wood frame structured carbons with integrated sieving layer for propylene/propane separation - Cheng-Tong Wang; Wen-Cui Li; Shuang Xu; Ru-Shuai Liu; Guang-Ping Hao; An-Hui Lu (Chemical Engineering Journal, 2023)

Association between thermal stress and cardiovascular mortality in the subtropics - Maidina Jingesi; Shuhua Lan; Jing Hu; Mengyi Dai; Suli Huang; Siyi Chen; Ning Liu; Ziquan Lv; Jiajia Ji; Xiaoheng Li; Peng Wang; Jinquan Cheng; et al. (International Journal of Biometeorology, 2023)

Genetic spectrums and clinical profiles of critically ill neonates with congenital auricular deformity in the China Neonatal Genomes Project - Feifan Xiao; Bingbing Wu; Chenbin Dong; Guoqiang Cheng; Yun Cao; Laishuan Wang; Xinran Dong; Yulan Lu; Lin Yang; Liping Chen; Long Li; Xinnian Pan; et al. (Human Genetics, 2023)

Multiscale information interaction at local frequency band in functional corticomuscular coupling - Shengcui Cheng; Xiaoling Chen; Yuanyuan Zhang; Ying Wang; Xin Li; Xiaoli Li; Ping Xie (Cognitive Neurodynamics, 2023)

White matter alterations in mild cognitive impairment revealed by meta-analysis of diffusion tensor imaging using tract-based spatial statistics - Longfei Li; Wei Yang; Yu Wan; Hailong Shen; Ting Wang; Liangliang Ping; Chuanxin Liu; Min Chen; Hao Yu; Shushu Jin; Yuqi Cheng; Xiufeng Xu; et al. (Brain Imaging and Behavior, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Factors affecting the accumulation of organotins by wild fish: A case study in the Three Gorges Reservoir, China - Jun-min Gao; Jia You; Jing-cheng Wu; Jin-song Guo; Ping-ting Fu; Li-xia Zhang (Environmental Science and Pollution Research, 2023)

Relationship of individual and mixed urinary metals exposure with liver function in the China National Human Biomonitoring (CNHBM) of Zhejiang Province - Ping Cheng; Yi Tao; Jinfeng Hu; Hongxin Wang; Ruifang Zhao; Shenghua Mei; Yin Yang; Fugen Ye; Zhijian Chen; Hao Ding; Mingluan Xing; Peiwei Xu; et al. (Chemosphere, 2023)

Baicalin mitigates nephropathogenic infectious bronchitis virus infection-induced spleen injury via modulation of mitophagy and macrophage polarization in Hy-Line chick - Guanming Tian; Cheng Huang; Zhengqing Li; Zhihua Lu; Chenlu Feng; Yu Zhuang; Guyue Li; Ping Liu; Guoliang Hu; Xiaona Gao; Xiaoquan Guo (Veterinary Microbiology, 2023)

Biomass-derived carbon dots with light conversion and nutrient provisioning capabilities facilitate plant photosynthesis - Bingxu Cheng; Zhilin Yang; Feiran Chen; Le Yue; Xuesong Cao; Jing Li; Hai-Long Qian; Xiu-Ping Yan; Chuanxi Wang; Zhenyu Wang (Science of The Total Environment, 2023)

Tailor-made yolk-shell nanocomposites of star-shape Au and porous organic polymer for nitrogen electroreduction to ammonia - Hongming He; Hao-Ming Wen; Ping Li; Hong-Kai Li; Cheng-Peng Li; Zhihong Zhang; Miao Du (Chemical Engineering Journal, 2023)

Livestock wastes from family-operated farms are potential important sources of potentially toxic elements, antibiotics, and estrogens in rural areas in North China - Yang Li; Xinyu Li; Xupu Ma; Tianlei Qiu; Xincheng Fu; Zhihong Ma; Hua Ping; Cheng Li (Environmental Science and Pollution Research, 2023)

Alteromonas Aquimaris sp. nov., Isolated from Surface Seawater - Qin Wang; Xin-Yuan Hu; Li-Ping Sun; Hui-Jing Niu; Cai-Xia Pei; Yi Li; Cheng-Qiang Xia (Current Microbiology, 2023)

Recovering phosphorus and lithium separately from wastewater and brine using a novel coupled biofilm-precipitation system - Hao Zhang; Shuang-Shuang Zhang; Wei Zhang; Wu-Cheng Ma; Yi-Ping Li; Lin Chen; Liang Zhu; Yang Pan (Journal of Water Process Engineering, 2023)

A momentum-based prediction model of backwater rise within and downstream of an emergent canopy in nonuniform flow - Ping Wang; Yonggang Zhang; Jinhua Cheng; Huilan Zhang; Li Zeng (Journal of Hydrology, 2023)

Surface imprinted-covalent organic frameworks for efficient solid-phase extraction of fluoroquinolones in food samples - Li-Hong Su; Hai-Long Qian; Cheng Yang; Chuanxi Wang; Zhenyu Wang; Xiu-Ping Yan (Journal of Hazardous Materials, 2023)

Red mud with enhanced dealkalization performance by supercritical water technology for efficient SO2 capture - Zimeng Nie; Qun Zhao; Qilin Zhao; Yingjie Li; Dian Yang; Huaying Liu; Shupu Yang; Jie Li; Senlin Tian; Chen Li; Cheng Tie; Jianhong Huang; et al. (Journal of Environmental Management, 2023)

A neglected contributor of thermal hydrolysis to sludge anaerobic digestion: Fulvic acids release and their influences - Mingze Shi; Hongbo Liu; Xuedong Zhang; Yajie Li; Fang Huang; Cheng Zhao; Jun Guo; Ping Wu; He Liu (Journal of Environmental Management, 2023)

Application of Mo2C for enhancement of co-catalytic performance of Fe3+/PS based fenton-like reaction in degrading tetracycline hydrochloride - Hao Cheng; Yi Wen; Chao Huang; Ping Wang; Chengyou Sun; Chongling Feng; Jialu Xu; Li Du; Ting Yan; Min Cheng (Chemical Engineering Journal, 2023)

Synergization of an endoplasmic reticulum-targeted iridium(III) photosensitizer with PD-L1 inhibitor for oral squamous cell carcinoma immunotherapy - Jia-Ying Zhou; Qing-Hua Shen; Xiao-Jing Hong; Wu-Ya Zhang; Qiao Su; Wu-Guo Li; Bin Cheng; Cai-Ping Tan; Tong Wu (Chemical Engineering Journal, 2023)

Lateral flow DNA biosensor for visual detection of nucleic acid with triple-helix DNA functionalized carbon nanotube - Yan Huang; Zhihao Cheng; Li-Ping Xu; Xueji Zhang; Guodong Liu (Analytica Chimica Acta, 2023)

Association of urinary bisphenols with thyroid function in the general population: a cross-sectional study of an industrial park in China - Yang Hu; Shiming Lai; Ying Li; Xiaodong Wu; Mingluan Xing; Xueqing Li; Dandan Xu; Yuan Chen; Jie Xiang; Ping Cheng; Xiaofeng Wang; Zhijian Chen; et al. (Environmental Science and Pollution Research, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Simultaneous phosphorus recovery from wastewater and sludge by a novel denitrifying phosphorus removal system - Hao Zhang; Wei Zhang; Shuang-Shuang Zhang; Wu-Cheng Ma; Liang Zhu; Yi-Ping Li; Yang Pan; Lin Chen (Bioresource Technology, 2023)

Performance and mechanism of different pretreatment methods for inoculated sludge in biohydrogen production - Wei-xin Cheng; Ling-ling Wang; Yun Xu; Si-jia Li; Quan Wang; Rong-ping Chen; Lei Yu (Bioresource Technology, 2023)

Formation of secondary organic aerosols from the ozonolysis of Cis-3-hexenyl acetate: The effect of acidic seed particles and SO2 - Dalin Shi; Yi Chen; Jixing Liu; Gaosheng Zhao; Li Xu; Bin Jia; Ping Cheng (Atmospheric Environment, 2023)

Nitidine chloride regulates cell function of bladder cancer in vitro through downregulating Lymphocyte antigen 75 - Shi-shuo Wang; Gao-qiang Zhai; Zhi-guang Huang; Jia-yuan Luo; Juan He; Jie-zhuang Huang; Ling Yang; Chu-nan Xiao; Su-li Li; Kai-rong Chen; Yan-yu Chen; Han-chu Ji; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Minimal addition of transglutaminase on the preparation and characteristics of tilapia (Oreochromis mossambicus) surimi - Ping-Hsiu Huang; Yu-Tsung Cheng; Yung-Jia Chan; Wen-Chien Lu; Wen-Ching Ko; Hung-Chun Hsieh; Po-Hsien Li (Fisheries Science, 2023)

Schizophrenia in the genetic era: a review from development history, clinical features and genomic research approaches to insights of susceptibility genes - Ye Lv; Lin Wen; Wen-Juan Hu; Chong Deng; Hui-Wen Ren; Ya-Nan Bao; Bo-Wei Su; Ping Gao; Zi-Yue Man; Yi-Yang Luo; Cheng-Jie Li; Zhi-Xin Xiang; et al. (Metabolic Brain Disease, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Quantitative evaluation for the sources and aging processes of organic aerosols in urban Guangzhou: Insights from a comprehensive method of dual‑carbon isotopes and macro tracers - Fan Jiang; Junwen Liu; Zhineng Cheng; Ping Ding; Sanyuan Zhu; Xin Yuan; Wei Chen; Zhisheng Zhang; Zheng Zong; Chongguo Tian; Weiwei Hu; Junyu Zheng; et al. (Science of The Total Environment, 2023)

Metamorphic P–T evolution of the pelitic granulites from the Helanshan in the North China Craton revealed by phase equilibrium modeling and garnet trace elements: Implications for Paleoproterozoic collisional orogenesis - Xiao-Fei Xu; Long-Long Gou; Yun-Peng Dong; Cheng-Li Zhang; Xiao-Ping Long; Yu-Hang Zhao; Feng Zhou; Zhi-Bo Tian (Precambrian Research, 2023)

The health risk of acetochlor metabolite CMEPA is associated with lipid accumulation induced liver injury - Wei-Guo Wang; Mu-Yao Li; Lin Diao; Cheng Zhang; Li-Ming Tao; Wei-Xing Zhou; Wen-Ping Xu; Yang Zhang (Environmental Pollution, 2023)

Compound-specific radiocarbon analysis of benzene polycarboxylic acids for source apportionment of polyaromatic organic matter in ambient aerosols - Xin Yi; Xiaofei Geng; Yangzhi Mo; Guangcai Zhong; Jiao Tang; Sanyuan Zhu; Zhineng Cheng; Shizhen Zhao; Jun Li; Örjan Gustafsson; Ping'an Peng; Gan Zhang (Atmospheric Environment, 2023)

Fluorescence enhancement of surface plasmon coupled emission by Au nanobipyramids and its modulation effect on multi-wavelength radiation - Kai-Xin Xie; Rui-Ping Huo; Xiu-Li Song; Qiao-Ling Liu; Yue Jiang; Yu-Han Li; Lu-Lu Dong; Jia-Xin Cheng (Analytica Chimica Acta, 2023)

Long-term hypoxia and reoxygenation induced oxidative stress lead to immunosuppression and apoptosis in golden pompano (Trachinotus blochii) - Yue Gu; Jun Long Sun; Fu Cheng Yao; Tian Jiang; Chun Xiu Jin; Li Ping Shi; Shu Kui Sun; Fei Biao Song; Jian Luo (Frontiers in Marine Science, 2023)
The fluctuations of dissolved oxygen (DO) often lead to hypoxia in aquaculture, which has a huge adverse impact on fish. This study mainly investigated the effects of long-term hypoxia on oxidative stress, immune response, and cell apoptosis in the liver of golden pompano ( Trachinotus blochii ), which is not tolerant to hypoxia. So we conducted a 14 day low oxygen stress experiment on the golden pompano with a DO of 3.0 ± 0.2 mg/L, then restore the DO to normal levels and continue the 14 day reoxygenation experiment. Results showed that hypoxia and reoxygenation led to significant changes in liver structure. During hypoxia and reoxygenation, the expression of oxidative stress related genes ( SOD1 , SOD2 , GSH-Px , and CAT ) and levels of antioxidant enzymes (CAT and MDA) in the liver were increased. Liver lysozyme activity and the relative expression of the pro-inflammatory factors interleukin ( IL)-1β were significantly increased, but the expression of IL-34 was down-regulated during hypoxia. The expression of IL-12β was significantly increased during reoxygenation. The expression of anti-inflammatory factor IL -11 was decreased duringreoxygenation. The expression of toll like receptors ( TLRs ) -7, -8, and -9 increases after hypoxia and decreases after reoxygenation, indicating that both hypoxia and reoxygenation affect the immune response. In addition, during hypoxia and reoxygenation, TUNEL-positive signals increased, the bcl2/bax ratio decreased, the expression levels of caspases-3 and -8 were significantly up-regulated during hypoxia, and expression levels of caspases-9 was up-regulated during reoxygenation. In summary, hypoxia and reoxygenation can cause oxidative stress, induce inflammatory reactions, inhibit immune processes, activate apoptosis, and lead to liver damage of the golden pompano, which may be irreversible.

Prediction and mitigation analysis of railway-induced vibrations of a layered transversely isotropic ground comprising different media with a hybrid 2.5-D method - Shi-Jin Feng; Yi-Cheng Li; Jian-Ping Li (Computers and Geotechnics, 2023)

Saltwater incursion regulates N2O emission pathways and potential nitrification and denitrification in intertidal wetland - Yinghui Jiang; Guoyu Yin; Ye Li; Lijun Hou; Min Liu; Cheng Chen; Dongsheng Zheng; Han Wu; Dengzhou Gao; Yanling Zheng; Ping Han (Biology and Fertility of Soils, 2023)

A facile approach to undecylenic acid-functionalized stationary phases for per aqueous liquid chromatography - Xiao-Dong Cheng; Zheng Zhang; Yun-Ping Li (Analytica Chimica Acta, 2023)

Identification of metabolites from edible mushroom Morchella sextelata and their biological evaluation - De-Xian Li; Xia Cheng; Fo-Pei Ma; Jie-Yu Chen; Yi-Ping Chen; Xiao-Shan Zhao; Qi Luo (Natural Product Research, 2023)

Metagenomics analysis reveals the effects of norfloxacin on the gut microbiota of juvenile common carp (Cyprinus carpio) - Ping Li; Cheng-Zhuang Chen; Xue-Li Zhao; Ling Liu; Zhi-Hua Li (Chemosphere, 2023)

Transcriptomic and physiological analysis of the effect of octanoic acid on Meloidogyne incognita - Jian-Yu Wang; Qiu-Yue Li; Li Ren; Cheng Guo; Jian-Ping Qu; Zheng Gao; Hui-Fang Wang; Qian Zhang; Bo Zhou (Pesticide Biochemistry and Physiology, 2023)

Effect of co-inoculation of Lactobacillus plantarum and Lentilactobacillus buchneri on aerobic stability and microbial community composition of perennial sorghum silage - Maoya Li; Shufeng Zhou; Xiaolong Tang; Chaosheng Liao; Ping Li; Yixiao Xie; Qiming Cheng; Chao Chen (Biomass and Bioenergy, 2023)

Vancomycin Pretreatment on MPTP-Induced Parkinson’s Disease Mice Exerts Neuroprotection by Suppressing Inflammation Both in Brain and Gut - Chun Cui; Hui Hong; Yun Shi; Yu Zhou; Chen-Meng Qiao; Wei-Jiang Zhao; Li-Ping Zhao; Jian Wu; Wei Quan; Gu-Yu Niu; Yi-Bo Wu; Chao-Sheng Li; et al. (Journal of Neuroimmune Pharmacology, 2023)

LC-MS Based Metabolomic Profiling of Largehead Hairtail (Trichiurus japonicus) Ovary Reveals Metabolic Signatures of Ovarian Developmental Process (II–IV) - Liu-Ying Feng; Li-Ping Yan; Run-Wei Li; Sheng-Fa Li; Jia-Hua Cheng; Yan Jin (Fishes, 2023)
Trichiurus japonicus is an economically important fish that ranks 11th in global marine fish capture production. However, the reproductive characteristics of this fish have undergone notable changes in recent decades, potentially affecting the quality of offspring and sustainable utilization. To improve our understanding of the physiological regulation of maturation in T. japonicus, untargeted liquid chromatography mass spectrometry was utilized to identify the small molecules that characterize the comprehensive metabolic profiles of ovaries during ovary development from stage II to stage IV. According to the results of OPLS-DA, the ovarian metabolite profiles of the three developmental stages were separated. The concentrations of 124 and 100 metabolites were significantly altered between stage II vs. III and III vs. IV, respectively. Lipids and lipid-like molecules accounted for the largest proportion of the altered metabolites, followed by amino acids, peptides, and analogues. The significantly altered metabolites-enriched pathways differed slightly between stages II and III and stages III and IV. Steroid-related pathways were heavily affected during stages II to III, while significantly altered metabolites from stages III to IV were involved in oocyte-maturation-related pathways. Through metabonomics analysis, potentially important metabolic pathways and metabolites between different ovarian stages were detected, providing basic information for further investigation of maturation mechanisms in wild fish.

Erosion and accretion of salt marsh in extremely shallow water stages - Dezhi Chen; Jieping Tang; Fei Xing; Jun Cheng; Mingliang Li; Yiyi Zhang; Benwei Shi; Lianqiang Shi; Ya Ping Wang (Frontiers in Marine Science, 2023)
Salt marshes, which commonly exist on the upper tidal flat, provide a natural barrier against sea level rise and coastal storm. The extremely shallow water stages (water depth< 0.2 m), including the initial stage of flood tides and the last stage of ebb tides, can induce a significant impact on sediment dynamics of saltmarshes and associated tidal flats, despite lasting for only a short time (around 10 min), which has been less studied. In this study, two parallel field sites were established to quantify erosion-accretion processes and morphological changes during extremely shallow water stages in salt marshes within Doulonggang tidal flat along the Jiangsu coast. Our results revealed that obvious accretion occurred during extremely shallow water stages, with a total deposition amount of +33.8 mm in vegetated areas and +20.8 mm in unvegetated areas. In contrast, erosion dominated during deep water stages, with a total erosion amount of -22.3 mm at the vegetated site and -32.7 mm at the unvegetated site. The magnitude of bed-level change during extremely shallow water stages was 7~8 times greater than that during deep water stages, even though the duration of extremely shallow water stages was only about 14~15% of the entire tidal cycle. Furthermore, strong winds significantly impacted deposition during extremely shallow water stages compared to calm weather. During the strong wind period, the average bed level change rate reached +0.15 mm/min and +0.12 mm/min in the vegetated and unvegetated areas, respectively. This is significantly higher than the +0.05 mm/min and +0.01 mm/min during the calm weather period. These results reveal that extremely shallow water stages have substantial impacts on sedimentary processes, which are vital for the maintenance of tidal flat systems.

Effects of disinfectants, sponge densities, water circulation rates, and vibration frequency on the artificial incubation of redclaw crayfish embryos - Cheng Shun; Jiang Wen-ping; Liu Shi-li; Chi Mei-li; Zheng Jian-bo; Liu Yi-nuo; Hang Xiao-ying; Peng Miao; Li Fei; Wang Dan-li (Aquaculture, 2023)

Southern Ocean warming and its climatic impacts - Wenju Cai; Libao Gao; Yiyong Luo; Xichen Li; Xiaotong Zheng; Xuebin Zhang; Xuhua Cheng; Fan Jia; Ariaan Purich; Agus Santoso; Yan Du; David M. Holland; et al. (Science Bulletin, 2023)

An oligosaccharide marker for rapid authentication of edible bird’s nest - Li-Feng Li; Hui-Yuan Cheng; Jun Lang; Tin-Long Wong; Ji-Xia Zhang; Wen-Jie Wu; Quan-Wei Zhang; Hau-Yee Kong; Check-Hei Lai; Hau-Yee Fung; Man Liu; Wan-Rong Bao; et al. (Food Chemistry, 2023)

Impacts of climate change on vicennial spatial behaviors of Trichiurus japonicus in the East China Sea - Yan Jin; Xing-Wei Yuan; Yi Zhang; Jian-sheng Li; Li-ping Yan; Zun-lei Liu; Jia-hua Cheng (Estuarine, Coastal and Shelf Science, 2023)

Synthesis and biological evaluation of esculetin derivatives as potential anti-HBV agents - Zhen Ye; Tong-Shi-Yao Zhao; Shan-Bin Li; Xian-Li Zhou; Qin Luo; Jiang-Ke Qin; Cheng-Qin Liang; Ping Wang; Guang-Bo Ge (Medicinal Chemistry Research, 2023)

Association between the NEP rs701109 polymorphism and the clinical efficacy and safety of sacubitril/valsartan in Chinese patients with heart failure - Hong-Yu Luo; Li-Chen Gao; Hui-Zhi Long; Zi-Wei Zhou; Shuo-Guo Xu; Feng-Jiao Li; Hong-Li Li; Yan Cheng; Cai-Xia Li; Xing-Yu Peng; Liang Li; Ran Chen; et al. (European Journal of Clinical Pharmacology, 2023)

Effects of small-scale silo types and additives on silage fermentation and bacterial community of high moisture alfalfa on the Qinghai-Tibetan Plateau - Ping Li; Chaosheng Liao; Lijun Yan; Changbing Zhang; Liangyin Chen; Minghong You; Qiming Cheng; Chao Chen (Animal Feed Science and Technology, 2023)

Histone methyltransferase SETDB1 promotes osteogenic differentiation in osteoporosis by activating OTX2-mediated BMP-Smad and Wnt/β-catenin pathways - Lianying Hu; Zhen Cheng; Lunan Wu; Liangliang Luo; Ping Pan; Shujin Li; Qiyu Jia; Ning Yang; Bin Xu (Human Cell, 2023)

Metabonomic Analysis of Macrobrachium rosenbergii with Iron Prawn Syndrome (IPS) - Xi-Lian Li; Pei-Jing Shen; Wen-Ping Jiang; Ji-Lun Meng; Hai-Hua Cheng; Qiang Gao (Fishes, 2023)
We previously reported on the comparison of proteomic data between seven tissue types of a novel “iron prawn” species. However, no transcripts or metabolic information are available for this species. We therefore performed shotgun LC–MS/MS metabonomic and RNA-seq analyses of the total protein from “iron prawns”. KEGG analysis revealed that the largest group consisted of a total of 114 KEGG pathway proteins, comparing the “iron prawns” with the normal prawns. A total of 423 peptides, corresponding to metabolic pathways, ABC transporters, starch and sucrose metabolism, insulin resistance/secretion, fatty digestion and absorption, and lipid metabolism, were identified. The pathways of carbohydrate and amino acid metabolism decreased in female iron prawns, while organic acid and its derivatives increased. However, the pathway of organic acid and its derivatives decreased and lipid metabolism increased in the male iron prawns. The pathways of choline metabolism in cancer and glycerophospholipid/histidine/propanoate metabolism have been significantly affected in iron prawns. Our work provides insight into the understanding of the formation mechanism of the “iron prawn”.

Quantitative Assessment of Climate Change Impacts on Forest Ecosystems - Dan Liu; Hao Yan; Cheng Long Yu; Shi Ping Yin; Cheng Wei Wang; Li Juan Gong (Forest Science, 2023)
Characterizing and predicting the response of terrestrial ecosystems to global change is part of the fundamental challenges of contemporary ecology and ecological conservation. The assessment of climate change impact on forest ecosystems has rarely used a multi-index fusion method for quantitative evaluation. We used forest distribution, net primary productivity, and vegetation coverage to establish an assessment model of the impact of climate change on forest ecosystems. We analyzed the change characteristics of these indicators in the Heilongjiang Province of China. Our results indicate the following: (1) from 2001 to 2019, the forest area in Heilongjiang Province ranged from 234,000 to 246,000 km2. The forest net primary productivity (NPP) ranged from 4.40 to 5.55 MgC·ha-1·yr-1, and the vegetation coverage ranged from 42.42% to 67.64%. The forest NPP and the vegetation coverage showed a significant upward trend. (2) The values of forest ecological roles were significantly positively correlated with the climatic potential. (3) The contribution rate of climate change to forest ecosystem change was negatively correlated with forest coverage, which varied from 4.79% to 18.07% in different regions (cities) of the province. Study Implications: Assessing the influence of climate on forest ecosystems comprehensively and accurately before the government prepares ecological measures is necessary. However, the responses of vegetation coverage and net primary productivity to climate change may not be consistent, so climate studies that consider forest ecosystem change trends by a single indicator may have confounding results. We established a model for evaluating the impact of climate change on forest ecosystems to solve this problem. This knowledge may provide a reference for the response, adaptation, and vulnerability assessment of forest ecosystems to climate change.

Preparation and characterization of carboxymethyl chitosan/pullulan composite film incorporated with eugenol and its application in the preservation of chilled meat - Zhen Zeng; Yu-Jing Yang; Qian Tu; Yu-Ying Jian; Da-Ming Xie; Ting Bai; Shan-Shan Li; Yun-Tao Liu; Cheng Li; Cai-Xia Wang; Ai-Ping Liu (Meat Science, 2023)

Integrative analyses of transcriptome and metabolome reveal comprehensive mechanisms of Epigallocatechin-3-gallate (EGCG) biosynthesis in response to ecological factors in tea plant (Camellia sinensis) - Ping Xiang; Qiufang Zhu; Luhuan zhang; Puzhen Xu; Lijia Liu; Yuanyuan Li; Bosi Cheng; Xingjian Wang; Jianghong Liu; Yutao Shi; Liangyu Wu; Jinke Lin (Food Research International, 2023)

Periploca sepium leaf dry weight, area, and thickness scale differently under different light environments in Taohe riparian forests - Min Ma; Cheng-Zhang Zhao; Man-Ping Kang; Xiao-Ya Li; Zhi-Wei Zhang; Xu-Qian Bai (Flora, 2023)

Eicosane-based thermo-conductive phase change composite for efficient capture solar energy and using in real-environment as power source - Linhong Li; Maohua Li; Yue Qin; Yapeng Chen; Wen Dai; Zhenbang Zhang; Xiangdong Kong; Ping Gong; Yandong Wang; Rongjie Yang; Bo Wang; Tao Cai; et al. (Chemical Engineering Journal, 2023)

Salvia miltiorrhiza polysaccharide and its related metabolite 5-methoxyindole-3-carboxaldehyde ameliorate experimental colitis by regulating Nrf2/Keap1 signaling pathway - Yu-Ping Fu; Xi Peng; Chao-Wen Zhang; Quan-Xing Jiang; Cen-Yu Li; Berit Smestad Paulsen; Frode Rise; Chao Huang; Bin Feng; Li-Xia Li; Xing-Fu Chen; Ren-Yong Jia; et al. (Carbohydrate Polymers, 2023)

Accelerated Fe(III)/Fe(II) cycle for rapid elimination of Rhodamine B by a novel Mo2C co-catalytic Fe2+/H2O2 system - Hao Cheng; Xinyan Li; Chao Huang; Jian Zhu; Ping Wang; Heng Cao; Chongling Feng; Dingxun Ling; Hao Liu; Min Cheng (Journal of Cleaner Production, 2023)

Solidification and stabilization of Pb–Zn mine tailing with municipal solid waste incineration fly ash and ground granulated blast-furnace slag for unfired brick fabrication - Ping Wang; Jiangshan Li; Yuanan Hu; Hefa Cheng (Environmental Pollution, 2023)

Erratum to: Rigid block characteristics on subaerial landslide-tsunamis using a 3D coupled Eulerian-Lagrangian model - Yi-ding Bao; Jian-ping Chen; Li-jun Su; Xin Zhou; Cheng-shan Yin (Journal of Mountain Science, 2023)

Distribution and physical–biological controls of dimethylsulfide in the western tropical Indian Ocean during winter monsoon - Shi-Mei Liang; Xing Zhai; Cheng-Xuan Li; Ming Xin; Ping Sun; Xuan-Li Liu; Lin Liu; Bao-Dong Wang (Frontiers in Marine Science, 2023)
New field observation on distribution, turnover, and sea–air flux of three dimethylated sulfur compounds (dimethylsulfide (DMS), dimethylsulfoniopropionate, and dimethylsulfoxide) in the western tropical Indian Ocean (WTIO; 4°N–10°S, 61°–65°E) were conducted under the major Global Change and Air–Sea Interaction Program during the 2021/2022 Northeast Monsoon (December 21, 2021 to January 11, 2022). Significantly high surface concentrations of DMS were identified in the region of the Seychelles–Chagos Thermocline Ridge (SCTR; 5°–10°S). This occurred because the shallow thermocline/nitracline and associated upwelling fueled biological production of DMS in the subsurface, which was brought to the surface through vertical mixing. The calculated sea–air DMS flux was also significantly strong in the SCTR region during the Northeast Monsoon owing to combination of high wind speed and high surface concentration of DMS. This finding is similar to results obtained previously during the Southwest Monsoon, suggesting that the SCTR region is an area of active DMS emission during both the Northeast Monsoon and the Southwest Monsoon. Microbial consumption was the dominant pathway of DMS removal, accounting for 74.4% of the total, whereas the processes of photolysis (17.7%) and ventilation (7.9%) were less important. Future work should be undertaken in the WTIO to establish how DMS emission is linked to aerosol properties and climate change.

Physiological and molecular responses in the silver carp (Hypophthalmichthys molitrix) larvae after acute mercury exposure - Cheng-Zhuang Chen; Yi Chai; Ya-Jun Wang; Ping Li; Ling Liu; Zhi-Hua Li (Environmental Science and Pollution Research, 2023)

Heavy metal(loid)s in agricultural soil from main grain production regions of China: Bioaccessibility and health risks to humans - Cheng-Chen Wang; Qiao-Chu Zhang; Shao-Guo Kang; Meng-Ying Li; Meng-Yan Zhang; Wu-Mei Xu; Ping Xiang; Lena Q. Ma (Science of The Total Environment, 2023)

ARSCP: An antimicrobial residue surveillance cloud platform for animal-derived foods - Jun-Jun Yu; Ya-Lin Hu; Cheng-Zheng Liu; Shuai-Bin Wu; Zi-Jian Zheng; Ze-Hua Cui; Li Chen; Tian Wei; Shi-Kai Sun; Jun Ning; Xiang Wen; Qiu-Yue Diao; et al. (Science of The Total Environment, 2023)

Kojicone C, new anti-inflammatory polyketide from insect-associated fungus Aspergillus versicolor - Tian-Xiao Li; Chi Zhang; Feng-Cheng Shi; Ye Ye; Jia-Le Huang; Lei Wu; Chun-Ping Xu (Phytochemistry Letters, 2023)

Using BHR to detect coal seam interface in coal mine - Bici Jiang; Jianyuan Cheng; Ping Li; Tao Fan (Journal of Applied Geophysics, 2023)

Effect of Tribute citrus essential oil nanoemulsion-loaded gelatin on the gel behavior and gelation surface morphologies - Guoqiang Li; Qingqing Zhou; Shuxun Liu; Cheng Qian; Jiarun Han; Tao Zhou; Ping Li; Qing Gu (Food Bioscience, 2023)

Phospholipase A2 induces acute kidney injury by complement mediated mitochondrial apoptosis via TNF-α/NF-κB signaling pathway - Xin Tang; Tiantian Wei; Mingjing Guan; Peiyun Li; Yajun Pu; Lixin Cheng; Zhifeng Zhou; Ping Fu; Ling Zhang (Food and Chemical Toxicology, 2023)

Cobalt single atom anchored on N-doped carbon nanoboxes as typical single-atom catalysts (SACs) for boosting the overall water splitting - Tong Li; Siyuan Ren; Cheng Zhang; Lingxia Qiao; Jiang Wu; Ping He; Jia Lin; Yongsheng Liu; Zaiguo Fu; Qunzhi Zhu; Weiguo Pan; Baofeng Wang; et al. (Chemical Engineering Journal, 2023)

A 2D mesoporous hydrazone covalent organic framework for selective detection and ultrafast recovery of Au(III) from electronic waste - Li Zhang; Jia-Qi Fan; Qiong-Qing Zheng; Sai-Jin Xiao; Cheng-Rong Zhang; Shun-Mo Yi; Xin Liu; Wei Jiang; Quan-Gen Tan; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

Potential for volatile fatty acid production via anaerobically-fermenting rice straw pretreated with silage effluent and phenyllactic acid - Hong Sun; Chaosheng Liao; Liangyin Chen; Qiming Cheng; Yulong Zheng; Chunmei Wang; Yixiao Xie; Chao Chen; Ping Li (Bioresource Technology, 2023)

Smog chamber study of secondary organic aerosol formation from gas- and particle-phase naphthalene ozonolysis - Jixing Liu; Shuping Zhu; Teng Guo; Bin Jia; Li Xu; Jun Chen; Ping Cheng (Atmospheric Environment, 2023)

Different roles of primary and secondary sources in reducing PM2.5: Insights from molecular markers in Pearl River Delta, South China - Kong Yang; Duo-Hong Chen; Xiang Ding; Jun Li; Yu-Qing Zhang; Tao Zhang; Qiao-Yun Wang; Jun-Qi Wang; Qian Cheng; Hao Jiang; Ping Liu; Zi-Rui Wang; et al. (Atmospheric Environment, 2023)

Separation of a new triterpenoid saponin together with six known ones from Clematis tangutica (Maxim.) Korsh and evaluation of their cytotoxic activities - Yangfei Wei; Tao Chen; Shuo Wang; Cheng Shen; Shuping Yan; Zhibo Song; Yarong Liu; Fengmei Yang; Ping Hai; Yulin Li (Natural Product Research, 2023)

Biofertilizer made from a mixed microbial community can enhance the suppression of fusarium wilt of banana when combined with acid soil ameliorant - Jianfeng Huang; Yuwan Pang; Gen Cheng; Tengfei Wu; Qiaoyi Huang; Xu Huang; Qiong Yi; Mu Zhang; Shuanhu Tang; Hongting Fu; Ping Li (European Journal of Plant Pathology, 2023)

Cognitive changes are associated with increased blood-brain barrier leakage in non-brain metastases lung cancer patients - Da-Fu Zhang; Zhen-Hui Li; Zhi-Ping Zhang; Yin-Fu He; Bin-Li Shang; Xiu-Feng Xu; Ying-Ying Ding; Yu-Qi Cheng (Brain Imaging and Behavior, 2023)
To explore the relationship between cognitive function and blood–brain barrier leakage in non-brain metastasis lung cancer and healthy controls. 75 lung cancers without brain metastasis and 29 healthy controls matched with age, sex, and education were evaluated by cognitive assessment, and the Patlak pharmacokinetic model was used to calculate the average leakage in each brain region according to the automated anatomical labeling atlas. After that, the relationships between cognitive and blood–brain barrier leakage were evaluated. Compared with healthy controls, the leakage of bilateral temporal gyrus and whole brain gyrus were higher in patients with lung cancers ( P < 0.05), mainly in patients with advanced lung cancer ( P < 0.05), but not in patients with early lung cancer ( P > 0.05). The cognitive impairment of advanced lung cancers was mainly reflected in the damage of visuospatial/executive, and delayed recall. The left temporal gyrus with increased blood–brain barrier leakage showed negative correlations with delayed recall (r = -0.201, P = 0.042). An increase in blood–brain barrier leakage was found in non-brain metastases advanced lung cancers that corresponded to decreased delayed recall. With progression in lung cancer staging, blood–brain barrier shows higher leakage and may lead to brain metastases and lower cognitive development.

Rigid block characteristics on subaerial landslide-tsunamis using a 3D coupled Eulerian-Lagrangian model - Yi-ding Bao; Jian-ping Chen; Li-jun Su; Xin Zhou; Cheng-shan Yin (Journal of Mountain Science, 2023)

Effects of light color, photoperiod, and growth-related gene interference or overexpression on the survival, growth, or physiological and biochemical indices of red claw crayfish juveniles - Shun Cheng; Jian-bo Zheng; Yong-yi Jia; Mei-li Chi; Wen-ping Jiang; Shi-li Liu; Fei Li; Yi-nuo Liu; Zhi-min Gu; Dan-li Wang (Aquaculture, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Confined Fe single atomic sites on (100) plane of anatase TiO2 nanofibers boost white LED driven Fenton-like norfloxacin degradation - Zhilin Ji; Rongsheng Cai; Wanneng Ye; Ping Lu; Chung-Li Dong; Yu-Cheng Huang; Xilin She; Denys S. Butenko; Yiming Liu; Yukun Zhu; Dongjiang Yang (Journal of Cleaner Production, 2023)

Oligosaccharide analysis of the backbone structure of the characteristic polysaccharide of Dendrobium officinale - Tin-Long Wong; Li-Feng Li; Ji-Xia Zhang; Quan-Wei Zhang; Xue-Ting Zhang; Li-Shuang Zhou; Hau-Yee Fung; Lei Feng; Hui-Yuan Cheng; Chu-Ying Huo; Man Liu; Wan-Rong Bao; et al. (Food Hydrocolloids, 2023)

Regulating electronic structure by Mn doping for nickel cobalt hydroxide nanosheets/carbon nanotube to promote oxygen evolution reaction and oxidation of urea and hydrazine - Kaili Wu; Chenyang Cao; Keren Li; Chaojie Lyu; Jiarun Cheng; Hongyu Li; Pengfei Hu; Jiwen Wu; Woon-Ming Lau; Xixi Zhu; Ping Qian; Jinlong Zheng (Chemical Engineering Journal, 2023)

From lab to practical: An ammonia-powered fuel cell electric golf cart system - Lingling Zhai; Chiu Shek Wong; Honglei Zhang; Pei Xiong; Xiangdang Xue; Yiu Lun Ho; Cuidong Xu; Yat Chi Fong; Jie Mei; Wing Wa Chan; Shu Chuen Ip; Shuangxia Niu; et al. (Chemical Engineering Journal, 2023)

Salt Bridge-intermediated three phase decoupling electrolytes for high voltage electrolytic aqueous Zinc-Manganese dioxides battery - Qi Xu; Qi-Xing Xie; Tong Xue; Gao Cheng; Jian-Dong Wu; Lan Ning; Xiang-Hui Yan; You-Jun Lu; Zhong-Li Zou; Bei-Ping Wang; Feng-Lan Han (Chemical Engineering Journal, 2023)

Transcriptional analysis of heavy metal P1B-ATPases (HMAs) elucidates competitive interaction in metal transport between cadmium and mineral elements in rice plants - Peng Tian; Yu-Xi Feng; Cheng-Zhi Li; Ping Zhang; Xiao-Zhang Yu (Environmental Science and Pollution Research, 2023)

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Inhibition of Spinal 5-HT3 Receptor and Spinal Dorsal Horn Neuronal Excitability Alleviates Hyperalgesia in a Rat Model of Parkinson’s Disease - Cheng-Jie Li; Li-Ge Zhang; Lu-Bing Liu; Meng-Qi An; Li-guo Dong; Han-Ying Gu; Yong-Ping Dai; Fen Wang; Cheng-Jie Mao; Chun-Feng Liu (Molecular Neurobiology, 2022)

Inhibition of Microglial NLRP3 with MCC950 Attenuates Microglial Morphology and NLRP3/Caspase-1/IL-1β Signaling In Stress-induced Mice - Qing Liu; Man-Man Zhang; Min-Xia Guo; Qiu-Ping Zhang; Na-Zhi Li; Jie Cheng; Shi-Le Wang; Guang-Hui Xu; Cheng-Fu Li; Ji-Xiao Zhu; Li-Tao Yi (Journal of Neuroimmune Pharmacology, 2022)

Acute Toxicity of a Novel anti-fouling Material Additive DCOIT to Marine Chlorella sp - Jin-Chuang Ru; Xue-Li Zhao; Zhi-Han Cao; Cheng-Zhuang Chen; Ping Li; Zhi-Hua Li (Bulletin of Environmental Contamination and Toxicology, 2022)

Derivation of new resistance principle on flow-induced morphological response of flexible vegetation - Feng-Cong Jia; Wei-Jie Wang; Ling-Hua Liu; Jin-Jin Li; Ai-Ping Huang; Jing Zhang; Yi-Cheng Fu; Yang Yu (Environmental Science and Pollution Research, 2022)

Damage and Failure Characteristics and Constitutive Model of Copper-Bearing Skarns Disturbed by Hierarchical Dynamic Loading After Loading And Unloading - Chun Wang; Jia Li; Lu- ping Cheng; Xin-ru Li; Pan-long Zhang; Man-gu Hu (Rock Mechanics and Rock Engineering, 2022)

The Influence of the Rotary Speed of a Microwave Applicator on Hard-Rock Fracturing Effect - Xia-ting Feng; Shi-ping Li; Cheng-xiang Yang; Feng Lin; Tian-yang Tong; Xiang-xin Su; Jiu-yu Zhang (Rock Mechanics and Rock Engineering, 2022)

Application of regional citrate anticoagulation in patients at high risk of bleeding during intermittent hemodialysis: a prospective multicenter randomized controlled trial - Xiaoyan Tang; Dezheng Chen; Ling Zhang; Ping Fu; Yanxia Chen; Zhou Xiao; Xiangcheng Xiao; Weisheng Peng; Li Cheng; Yanmin Zhang; Hongbo Li; Kehui Li; et al. (Journal of Zhejiang University-SCIENCE B, 2022)

Salinimicrobium sediminilitoris sp. nov., Isolated from a Tidal Flat - Cheng-Qiang Xia; Hui-Jing Niu; Kai-Shi Dong; Li Guan; Li-Ping Sun; Qin Wang; Yan-Jiao Zhang; Yi Li; Cai-Xia Pei (Current Microbiology, 2022)

Distribution of ultrafine aerosols and volatile organic compounds from surgical smoke during electrocauterization - Chi-Tsung Chen; Shiang-Fu Huang; Cheng-Jung Li; Jou-Mien Huang; Kai-Ping Chang; Gwo-Hwa Wan (Air Quality, Atmosphere & Health, 2022)

Isolation, identification, and quantification of triterpene saponins in the fresh fruits of Panax notoginseng - Zheng-yi Qu; He-cheng Wang; Yin-ping Jin; Ya-li Li; Ying-ping Wang (Natural Product Research, 2022)

Study on the Effectiveness and Mechanism of Mercapto-Modified Attapulgite for Remediation of Cadmium-Contaminated Paddy Soil - Guangxi He; Xiaping Zhu; Yan An; Yuying Chen; Cheng Fu; Ningfei Lei; Ying Zeng; Junya Li; Zepeng Wang; Ping Zhao (Water, Air, & Soil Pollution, 2022)

Genome-wide identification and expression analysis of JmjC domain–containing genes in grape under MTA treatment - Yi-Zhe Cheng; Guang-Qi He; Sheng-Di Yang; Shuai-Hui Ma; Jin-Ping Ma; Fang-Hui-Zi Shang; Xu-Fei Li; Hui-Ying Jin; Da-Long Guo (Functional & Integrative Genomics, 2022)

Long-term changes in zooplankton in the Changjiang estuary from the 1960s to 2020 - Ping Du; Wen-Jian Ye; Bang-Ping Deng; Ming Mao; Yuan-Li Zhu; Fang-Ping Cheng; Zhi-Bing Jiang; Lu Shou; Quan-Zhen Chen (Frontiers in Marine Science, 2022)
The Changjiang estuary (CJE) is a large estuary that is affected by multiple anthropogenic stressors and climate change. The long-term trend of zooplankton in the CJE is an important indicator of the ecological response to stressors. We applied the Mann–Kendall trend analysis and Pettitt test to detect the trend and breakpoints of the biomass of the large mesozooplankton (LMZ; 505–20 000 μm) in four seasons, abundance of main LMZ taxa in summer from the 1960s to 2020, and abundance of dominant species in summer from 2000 to 2020 in the CJE. Results showed that LMZ biomass increased significantly during spring and summer, and the breakpoints both occurred in the 1980s. After the breakpoint, the mean biomass increased from 142.88 to 429.42 mg/m 3 in spring and from 296.28 to 723.92 mg/m 3 in summer. After 2000, the abundance of Copepoda in summer increased by more than 10 times compared to the 1960s. Under the conditions of warming and increased dinoflagellate abundance in the CJE, the abundance of the warm-water and omnivorous small calanoid copepod Paracalanus aculeatus increased significantly. Meanwhile, the significant decrease in the abundance of the temperate brackish species Labidocera euchaeta was probably mainly related to warming. The rapid changes in LMZ biomass during the late 1980s and mid-1990s is probably the result of a combination of enhanced bottom–up support, reduced top–down pressure, and promotion of temperature. This study provides scientific evidence and insights into the adaptive management of the Changjiang Basin.

Association of cognitive impairment and reduced cortical thickness in prefrontal cortex and anterior cingulate cortex with treatment-resistant depression - Mu-Hong Chen; Wan-Chen Chang; Pei-Chi Tu; Wei-Chen Lin; Cheng-Ta Li; Wen-Sheng Huang; Ya-Mei Bai; Shih-Jen Tsai; Tung-Ping Su (Brain Imaging and Behavior, 2022)

Prognostic Value of miR-137 in Children with Medulloblastoma and its Regulatory Effect on Tumor Progression - Wenyuan Ji; Xuan Zhe; Lusheng Li; Yang Cheng; Xueling Zhao; Ping Liang; Chunxi Long; Jianjun Zhou (NeuroMolecular Medicine, 2022)

Modified Green–Ampt Model Considering Vegetation Root Effect and Redistribution Characteristics for Slope Stability Analysis - Shaohong Li; Peng Cui; Ping Cheng; Lizhou Wu (Water Resources Management, 2022)

The Effects of Ground and Treadmill Running on Energy Metabolism and Muscle Contractile Properties: A Randomized Cross-Over Study - Yuan Zhou; Jian-gang Chen; Xiao-long Li; Xin-liang Pan; Yi-zheng Zhou; Zheng-ao Li; Zhi-cheng Liang; Jia-min Long; Ming-ze Qin; Jing Zhang; Bing Shi; Bing-jun Wan; et al. (Journal of Science in Sport and Exercise, 2022)
Purpose This study aimed to compare the effects of ground and treadmill running on energy metabolism and muscle contractile properties, providing a basis for the general public to choose running venues. Methods Ten male college students (age, 20.10 ± 1.53 years; height, 176.20 ± 5.49 cm; weight, 72.14 ± 8.25 kg; body fat percent, 12.41% ± 4.65%) were recruited in this study. Energy expenditure (EE) was measured using the accelerometer (GT9X) combined with specific estimation equations. Average heart rate (HR) was measured using a heart rate band (Polar). Muscle contractile properties were assessed by measuring muscle displacement (Dm) and contraction velocity (Vc) using tensiomyography (TMG-S1). Blood glucose (Glu) and lactate (Lac) were measured by portable devices (eB-G and Lactate Scout). The running speed was 9 km/h and the duration was 25 min. Two-way ANOVA (protocol × time) was used to analyze the effect of running protocols on energy metabolism and muscle contractile properties. Results EE of treadmill running was significantly higher than EE of ground running (protocol main effect, P < 0.001), and HR of treadmill running was significantly higher than that of ground running in the first testing time (protocol simple effect, P = 0.026; protocol × time interaction P = 0.043). The decrease in Dm of the rectus femoris after treadmill running was significantly higher than that of ground running (protocol main effect, P = 0.009). The interaction of different running protocols and testing times on Lac was significant ( P = 0.025), but all results of the simple effects analysis were not statistically significant ( P > 0.05). Conclusion Our study found a difference in energy expenditure between treadmill and ground running at 9 km/h with duration of 25 min. In addition, treadmills are more likely to cause a decrease in muscle displacement distance of the rectus femoris measured after exercise than ground running. Future studies are needed to further investigate whether the differences are induced by internal metabolism or the environmental conditions of running.

MoOpy2 is essential for fungal development, pathogenicity, and autophagy in Magnaporthe oryzae - Ying‐Ying Cai; Jing‐Yi Wang; Xi‐Yu Wu; Shuang Liang; Xue‐Ming Zhu; Lin Li; Jian‐Ping Lu; Xiao‐Hong Liu; Fu‐Cheng Lin (Environmental Microbiology, 2022)
Summary The development and pathogenicity of the fungus Magnaporthe oryzae , the causal agent of destructive rice blast disease, require it to perceive external environmental signals. Opy2, an overproduction‐induced pheromone‐resistant protein 2, is a crucial protein for sensing external signals in Saccharomyces cerevisiae . However, the biological functions of the homologue of Opy2 in M. oryzae are unclear. In this study, we identified that MoOPY2 is involved in fungal development, pathogenicity, and autophagy in M. oryzae . Deletion of MoOPY2 resulted in pleiotropic defects in hyphal growth, conidiation, germ tube extension, appressorium formation, appressorium turgor generation, and invasive growth, therefore leading to attenuated pathogenicity. Furthermore, MoOpy2 participates in the Osm1 MAPK pathway and the Mps1 MAPK pathway by interacting with the adaptor protein Mst50. The interaction sites of Mst50 and MoOpy2 colocalized with the autophagic marker protein MoAtg8 in the preautophagosomal structure sites (PAS). Notably, the Δ Moopy2 mutant caused cumulative MoAtg8 lipidation and rapid GFP‐MoAtg8 degradation in response to nitrogen starvation, showing that MoOpy2 is involved in the negative regulation of autophagy activity. Taken together, our study revealed that MoOpy2 of M. oryzae plays an essential role in the orchestration of fungal development, appressorium penetration, autophagy and pathogenesis.

Endosomal sorting complexes required for transport‐0 ( ESCRT ‐0) are essential for fungal development, pathogenicity, autophagy and ER ‐phagy in Magnaporthe oryzae - Li‐Xiao Sun; Hui Qian; Meng‐Yu Liu; Ming‐Hua Wu; Yun‐Yun Wei; Xue‐Ming Zhu; Jian‐Ping Lu; Fu‐Cheng Lin; Xiao‐Hong Liu (Environmental Microbiology, 2022)
Summary Magnaporthe oryzae is an important plant pathogen that causes rice blast. Hse1 and Vps27 are components of ESCRT‐0 involved in the multivesicular body (MVB) sorting pathway and biogenesis. To date, the biological functions of ESCRT‐0 in M. oryzae have not been determined. In this study, we identified and characterized Hse1 and Vps27 in M. oryzae . Disruption of MoHse1 and MoVps27 caused pleiotropic defects in growth, conidiation, sexual development and pathogenicity, thereby resulting in loss of virulence in rice and barley leaves. Disruption of MoHse1 and MoVps27 triggered increased lipidation of MoAtg8 and degradation of GFP‐MoAtg8, indicating that ESCRT‐0 is involved in the regulation of autophagy. ESCRT‐0 was determined to interact with coat protein complex II (COPII), a regulator functioning in homeostasis of the endoplasmic reticulum (ER homeostasis), and disruption of MoHse1 and MoVps27 also blocked activation of the unfolded protein response (UPR) and autophagy of the endoplasmic reticulum (ER‐phagy). Overall, our results indicate that ESCRT‐0 plays critical roles in regulating fungal development, virulence, autophagy and ER‐phagy in M. oryzae .

Cancer metabolism and tumor microenvironment: fostering each other? - Yiyuan Yuan; Huimin Li; Wang Pu; Leilei Chen; Dong Guo; Hongfei Jiang; Bo He; Siyuan Qin; Kui Wang; Na Li; Jingwei Feng; Jing Wen; et al. (Science China Life Sciences, 2022)

Implication of exogenous abscisic acid (ABA) application on phytoremediation: plants grown in co-contaminated soil - Lang Cheng; Lei Pu; Ai Li; Xiaping Zhu; Ping Zhao; Xiangning Xu; Ningfei Lei; Jinsong Chen (Environmental Science and Pollution Research, 2022)

Comparative Genomic Analysis of Streptococcus pneumoniae Strains: Penicillin Non-susceptible Multi-drug-Resistant Serotype 19A Isolates - Lifeng Li; Juanjuan Zhou; Mingchao Li; Zengyuan Yu; Kaijie Gao; Junwen Yang; Ping Cheng; Junmei Yang; Wancun Zhang; Zhidan Yu; Huiqing Sun (Current Microbiology, 2022)

A Hydroponic Study on Effect of Zinc Against Mercury Uptake by Triticale: Kinetic Process and Accumulation - Ting Liu; Yi Man; Ping Li; Hua Zhang; Huangxin Cheng (Bulletin of Environmental Contamination and Toxicology, 2022)

Seven new glycosides from the leaves of Datura metel L. - Jin-Yan Tan; Yan Liu; Yan-Gang Cheng; Yan-Ping Sun; Xiao-Mao Li; Wei Guan; Juan Pan; Bing-You Yang; Hai-Xue Kuang (Natural Product Research, 2022)

Effects of environmental factors on plant functional traits across different plant life forms in a temperate forest ecosystem - Xiaoqin Cheng; Tain Ping; Zuzheng Li; Tian Wang; Hairong Han; Howard E. Epstein (New Forests, 2022)

Association between serum folate levels and blood concentrations of cadmium and lead in US adults - Zuxiang Wu; Huan Hu; Chenxi Wang; Ji Wu; Yurong Xiong; Yang Fu; Xiaoshu Cheng; Hai Su; Ping Li (Environmental Science and Pollution Research, 2022)

C-dot doping for enhanced catalytic performance of TiO2/5A for toluene degradation in non-thermal plasma-catalyst system - Jixing Liu; Yanyan Ji; Shuping Zhu; Teng Guo; Li Xu; Junguo Dong; Ping Cheng (Environmental Science and Pollution Research, 2022)

The chemical profile and biological activity of different extracts of Sapindus mukorossi Gaertn. against Cutibacterium acnes - Min-Ping Wei; Jin-Dan Qiu; Lu Li; Yun-Fei Xie; Ya-Hui Guo; Hang Yu; Yu-Liang Cheng; He Qian; Wei-Rong Yao (Natural Product Research, 2021)

Cytotoxic triterpenoid glycosides from leaves of Cyclocarya paliurus - Hui-Hui Sun; Wen-Yan Lv; Jie Tan; Yu-Cheng Tang; Hui Zhu; Jian-Bo Qu; Jing Li; Jian-Ping Wu; Xi-Wen Chang; Zhi-Chun Yang; Wen-Xuan Wang; Zu-Hui Chen; et al. (Natural Product Research, 2021)

Impact of rhizosphere microorganisms on arsenic (As) transformation and accumulation in a traditional Chinese medical plant - Jiao-Jiao Li; Long Yang; Cui-Ping Miao; Ya-Jun Teng; Zi-Hao Fu; Chang-Lei Cheng; Xue-Xiu Chang; Yu Qian; Li-Xing Zhao (Environmental Science and Pollution Research, 2021)

Down-regulation of PTTG1 suppresses PDGF-BB-induced proliferation, migration and extracellular matrix production of airway smooth muscle cells (ASMCs) by regulating PI3K/AKT/mTOR signaling pathway - Guodong Cheng; Xiaowei Liu; Ping Li; Yan Li (Molecular & Cellular Toxicology, 2021)

MiR-590-5p inhibits pathological hypertrophy mediated heart failure by targeting RTN4 - Ping Fan; Likun Zhang; Tianyu Cheng; Jing Wang; Junyun Zhou; Li Zhao; Cuie Hua; Quan Xia (Journal of Molecular Histology, 2021)

Globular adiponectin inhibits osteoblastic differentiation of vascular smooth muscle cells through the PI3K/AKT and Wnt/β-catenin pathway - Yun Zhou; Li-Long Wei; Rui-Ping Zhang; Cheng-Wu Han; Yongtong Cao (Journal of Molecular Histology, 2021)
Lipid metabolism is closely related to the improvement of vascular calcification (VC) in chronic kidney disease (CKD). Globular adiponectin (gAd) has been reported to be involved in the development of VC in CKD, but the detailed regulatory role remains unclear. The present study is aimed to investigate the biological function and the underlying regulation mechanism of gAd in the process of VC during CKD. Vascular smooth muscle cells (VSMCs) calcification was determined by Alizarin Red S staining. Protein signaling related with VC was tested by western blotting. The expression and intracellular localization of runt-related transcription factor 2 (Runx2) was detected by immunofluorescence and uraemic rat with VC was established by a two-step nephrectomy. Combined with the results of Alizarin Red S staining, we discovered that β-glycerophosphate (β-Gp)-induced the osteoblastic differentiation of VSMCs was significantly reversed by gAd treatment. Along with the VSMCs calcification and the increase of Runx2 in β-Gp-exposed VSMCs, the activities of protein kinase B (AKT) and Wnt/β-catenin pathway were enhanced, but that were counteracted by the exposure of gAd in rat and human VSMCs. After administration with agonists of the Wnt (SKL2001) and AKT (SC79), there appeared more osteoblastic differentiation and higher expression of Runx2 in gAd-treated VSMCs, but showing lower impact in the presence of SC79 than that in the presence of SKL2001. In the in vivo experiments, intravenous injection of gAd also significantly inhibited VC and Runx2 level in uraemic rat in a dose-dependent manner, possibly through regulating Wnt/β-catenin pathway. This study demonstrates that gAd ameliorates osteoblastic differentiation of VSMCs possibly by blocking PI3K/AKT and Wnt/β-catenin signaling transduction. The findings provide an important foundation for gAd in treating VC in kidney diseases.

A small attentional YOLO model for landslide detection from satellite remote sensing images - Libo Cheng; Jia Li; Ping Duan; Mingguo Wang (Landslides, 2021)

Citrus NIP5;1 aquaporin regulates cell membrane water permeability and alters PIPs plasma membrane localization - Mingfei Zhang; Ruilian Liu; Hai Liu; Hongbin Yang; Xin Li; Ping Wang; Feng Zhu; Rangwei Xu; Shaowu Xue; Yunjiang Cheng (Plant Molecular Biology, 2021)

Genetic Analysis of ZNF Protein Family Members for Early-Onset Parkinson’s Disease in Chinese Population - Chun Yu Li; Ru Wei Ou; Yong Ping Chen; Xiao Jing Gu; Qian Qian Wei; Bei Cao; Ling Yu Zhang; Yan Bing Hou; Kun Cheng Liu; Xue Ping Chen; Wei Song; Bi Zhao; et al. (Molecular Neurobiology, 2021)

Using the Metabolome to Understand the Mechanisms Linking Chronic Arsenic Exposure to Microglia Activation, and Learning and Memory Impairment - Rui-Yuan Zhang; Jie-Bai Tu; Rui-Tu Ran; Wen-Xuan Zhang; Qiang Tan; Ping Tang; Tao Kuang; Shu-Qun Cheng; Cheng-Zhi Chen; Xue-Jun Jiang; Chang Chen; Ting-Li Han; et al. (Neurotoxicity Research, 2021)

Cross-frequency and iso-frequency estimation of functional corticomuscular coupling after stroke - Ping Xie; Xiaohui Pang; Shengcui Cheng; Yuanyuan Zhang; Yinan Yang; Xiaoli Li; Xiaoling Chen (Cognitive Neurodynamics, 2021)

Proton Pump Inhibitor Exposure and Acute Myocardial Infarction Risk: A Nested Cohort Study - Hsiang-Jung Tseng; Chih-Ming Cheng; Shih-Jen Tsai; Wei-Chen Lin; Ya-Mei Bai; Chia-Fen Tsai; Tung-Ping Su; Cheng-Ta Li; Tzeng-Ji Chen; Mu-Hong Chen (Cardiovascular Toxicology, 2021)

Influence of major water conservation projects on river channels and shorelines in the middle and lower reaches of the Yangtze River - Yue-hua Jiang; He-qin Cheng; Quan-ping Zhou; Yun Li; Guo-qiang Yang; Yang Jin; Shi-jia Mei; Xuan Gu; Hong Zhang (Arabian Journal of Geosciences, 2021)

New cytotoxic biflavones from Selaginella doederleinii - Li-Fei Liu; Hui-Hui Sun; Jian-Bing Tan; Qi Huang; Fei Cheng; Kang-Ping Xu; Zhen-Xing Zou; Gui-Shan Tan (Natural Product Research, 2021)

Sesquiterpenoids from the roots and rhizomes of Valeriana amurensis and their effects on NGF-induced neurite outgrowth in PC12 cells - Fa-Wu Dong; Fang Li; Jia-Jia Ren; Cheng-Mei Zhao; Hong-Li Diao; Bao-Jing Li; Yan-Ping Li; Jiang-Miao Hu; Hong-Ping He (Natural Product Research, 2021)

An Insight into the Excavation-Induced Stress Paths on Mechanical Response of Weak Interlayer Zone in Underground Cavern Under High Geostress - Shu-Qian Duan; Quan Jiang; Guo-Feng Liu; Jie-Cheng Xiong; Po Gao; Ding-Ping Xu; Ming-Yu Li (Rock Mechanics and Rock Engineering, 2021)

Interest-activity symptom severity predicts response to ketamine infusion in treatment-resistant depression - Mu-Hong Chen; Wei-Chen Lin; Hui-Ju Wu; Ya-Mei Bai; Cheng-Ta Li; Shih-Jen Tsai; Chen-Jee Hong; Pei-Chi Tu; Tung-Ping Su (Psychopharmacology, 2021)

Groundwater sources, flow patterns, and hydrochemistry of the Central Yinchuan Plain, China - Ying Li; Ping Wu; Xiao-Qin Huang; Bo Zhang; Zhao-Xiang Xu; Yang Li; Jie Li; Lu-Chen Wang; Yu-Fang Sun; Xu-Chen Meng; Cheng-Wen Wang; Zi-Zhao Cai (Hydrogeology Journal, 2021)

The MYB transcription factor Baymax1 plays a critical role in rice male fertility - Xiao-Jiao Xiang; Lian-Ping Sun; Ping Yu; Zheng-Fu Yang; Pei-Pei Zhang; Ying-Xin Zhang; Wei-Xun Wu; Dai-Bo Chen; Xiao-Deng Zhan; Riaz-Muhammad Khan; Adil Abbas; Shi-Hua Cheng; et al. (Theoretical and Applied Genetics, 2021)

Small RNA Sequencing Analysis of Germinating Single-bud Seedcane Sett in Sugarcane - Kai-Chao Wu; Lin Xu; Zhi-Nian Deng; Tian Pang; Rong-Hua Zhang; Yi-Jie Li; Xiao-Yan Liu; Cheng-Feng Huang; Wen-Xian Qin; Jian-Feng Wei; Li-Ping Wei; Yang-Rui Li; et al. (Sugar Tech, 2021)

Starch bio-template synthesis of W-doped CeO2 catalyst for selective catalytic reduction of NOx with NH3: influence of ignition temperature - Zhi-Bo Xiong; Zhen-Zhuang Li; Yan-Ping Du; Cheng-Xu Li; Wei Lu; Su-Le Tian (Environmental Science and Pollution Research, 2021)

Sesquiterpenoids and meroterpenoids from a mangrove derived fungus Diaporthe sp. SCSIO 41011 - Xiao-Wei Luo; Chun-Mei Chen; Kun-Long Li; Xiu-Ping Lin; Cheng-Hai Gao; Xue-Feng Zhou; Yong-Hong Liu (Natural Product Research, 2021)

An A 1 -type granite that borders A 2 -type: insights from the geochemical characteristics of the Zongyang A-type granite in the Lower Yangtze River Belt, China - Xiao-Yan Jiang; Kai Wu; Jin-Cheng Luo; Li-Peng Zhang; Wei Dong Sun; Xiao-Ping Xia (International Geology Review, 2020)

Two new anthraquinone derivatives and one new triarylbenzophenone analog from Selaginella tamariscina - Rui Liu; Hui Zou; Zhen-Xing Zou; Fei Cheng; Xia Yu; Ping-Sheng Xu; Xiao-Min Li; Dai Li; Kang-Ping Xu; Gui-Shan Tan (Natural Product Research, 2020)

Comparing GWAS and Brain Structure-Specific Gene Expression Profiles Identifies Psychiatric Disorder-Related Brain Structures at Different Developmental Stages - Xin Qi; Cuiyan Wu; Yanan Du; Shiqiang Cheng; Yan Wen; Mei Ma; Chujun Liang; Li Liu; Bolun Cheng; Lu Zhang; Ping Li; Feng Zhang (Neuroscience Bulletin, 2020)

Blockade of HCN2 Channels Provides Neuroprotection Against Ischemic Injury via Accelerating Autophagic Degradation in Hippocampal Neurons - Cheng Chen; Li Liu; Ya-Qiao Shu; Ping Jing; Yun Lu; Xiao-Xue Zhang; Xian-Gang Zong; Lian-Jun Guo; Chang-Jun Li (Neuroscience Bulletin, 2020)

DhLHY, a Circadian Expressed Gene of Doritaenopsis Hybrid, Promotes Floral Transition in Low Temperature, but Postpones Flowering in Overexpressed Transgenic Arabidopsis - Chi Zhang; Qian Cheng; Haiyan Li; Ping Luo; Yongyi Cui (Tropical Plant Biology, 2020)

Cognitive Load of Exercise Influences Cognition and Neuroplasticity of Healthy Elderly: An Exploratory Investigation - Yi-Ping Chao; Changwei W. Wu; Li-Jung Lin; Cheng-Hung Lai; Hong-Yi Wu; Ai-Ling Hsu; Chiao-Nan Chen (Journal of Medical and Biological Engineering, 2020)
This study explored the effects of exercise with either high cognitive load or low cognitive load on cognitive performance and neuroplasticity in healthy elderly. Twenty-eight sedentary community-dwelling seniors participated in this study. Participants were assigned to one of three groups: the control group (C), low-cognitive load exercise group (LE), or high-cognitive load exercise group (HE). Individuals in both exercise groups engaged in moderate-intensity aerobic exercise for 4 months. Resting-state functional MRI and diffusion MRI were used to investigate the effects of intervention on functional and structural connectivity, respectively. Analysis of covariance with baseline, age and the education year as covariates was used to determine the effects of intervention. We found 4 months of exercise with high-cognitive load, but not exercise with low-cognitive load, improved the overall cognitive function of healthy elderly. Additionally, the HE group showed increased resting-state functional connectivity of superior frontal gyrus and anterior cingulate cortex and decreased functional connectivity of middle occipital gyrus and postcentral gyrus. The age-related alterations in local efficiency and betweenness were protected by exercise. Our findings might suggest that exercise with greater cognitive load likely results in greater training effects on cognition and brain connectivity than exercise requiring lower cognitive loads for healthy elderly.

Dynamic Risk Assessment Method of Collapse in Mountain Tunnels and Application - Sheng Wang; Li-ping Li; Shaoshuai Shi; Shuai Cheng; Huijiang Hu; Tao Wen (Geotechnical and Geological Engineering, 2020)

The implications of hippocampal neurogenesis in adolescent rats after status epilepticus: a novel role of notch signaling pathway in regulating epileptogenesis - Ping Yuan; Wei Han; Lingling Xie; Li Cheng; Hengsheng Chen; Jin Chen; Li Jiang (Cell and Tissue Research, 2020)

Dynamic change of vegetation and its response to climate and topographic factors in the Xijiang River basin, China - Lu Jia; Zhan-bin Li; Guo-ce Xu; Zong-ping Ren; Peng Li; Yu-ting Cheng; Yi-xin Zhang; Bin Wang; Jia-xin Zhang; Shu Yu (Environmental Science and Pollution Research, 2020)

Dryland agricultural environment and sustainable productivity - Gou-Xia Li; Bing-Cheng Xu; Li-Na Yin; Shi-Wen Wang; Sui-Qi Zhang; Lun Shan; Sang-Soo Kwak; Qingbo Ke; Xi-Ping Deng (Plant Biotechnology Reports, 2020)

Evaluating the Genetic Correlations Between Left-Handedness and Mental Disorder Using Linkage Disequilibrium Score Regression and Transcriptome-Wide Association Study - Bolun Cheng; Chujun Liang; Ping Li; Li Liu; Shiqiang Cheng; Mei Ma; Lu Zhang; Xin Qi; Yan Wen; Feng Zhang (Biochemical Genetics, 2020)

Effects of Starvation on Antioxidant-Related Signaling Molecules, Oxidative Stress, and Autophagy in Juvenile Chinese Perch Skeletal Muscle - Ping Wu; Aimin Wang; Jia Cheng; Lin Chen; Yaxiong Pan; Honghui Li; Qi Zhang; Jiaqi Zhang; Wuying Chu; Jianshe Zhang (Marine Biotechnology, 2020)

Front Cover - Wei Wang; Jie Wang; Francis M. P. Choi; Ping Ding; Xiao‐xu Li; Guo‐dong Han; Meng‐wen Ding; Minquan Guo; Xiong‐wei Huang; Wei‐xiang Duan; Zhi‐yuan Cheng; Zhi‐yuan Chen; et al. (Global Ecology and Biogeography, 2020)

Global warming and artificial shorelines reshape seashore biogeography - Wei Wang; Jie Wang; Francis M. P. Choi; Ping Ding; Xiao‐xu Li; Guo‐dong Han; Meng‐wen Ding; Minquan Guo; Xiong‐wei Huang; Wei‐xiang Duan; Zhi‐yuan Cheng; Zhi‐yuan Chen; et al. (Global Ecology and Biogeography, 2020)
Aim Rapid anthropogenic warming coupled with changes in land use is altering the distributions of species, with consequences for ecosystem functioning and services. It is crucial to evaluate species range shifts based on understanding of the interaction of temperature with non‐climatic factors such as habitat availability and dispersal potential. Here, we aim to investigate roles of environmental temperature, habitat availability and population connectivity on the distributions of hard‐shore intertidal animals. We further examine potential roles of extensive artificial seawall construction in enabling poleward expansion of species in China, thus reshaping coastal biogeography. Location Chinese coast. Time period 2013–2017. Major taxa studied Intertidal invertebrates. Methods We took an integrative approach encompassing distributional ecology, thermal physiology, molecular genetics, heat budget modelling and larval dispersal to elucidate how interacting multiple drivers, including temperature, habitat availability and larval dispersal, determine distributions of hard‐shore invertebrates, focusing on what sets their range edges at a boundary between biogeographic provinces. Results Our results untangle the complex interactions of global climate change with the impacts of regional scale coastal development. Temperature, larval transport and habitat availability are the major proximate factors controlling the range limits of coastal marine species. The artificial shorelines provide suitable habitats for hard‐shore species on the Yangtze River Delta, and minimum temperature in winter is an important factor setting the new northern range limit of these hard‐shore species along the Chinese coast. Main conclusions In the face of global warming and global sprawl of marine hard infrastructure, species distributions, community structures and biogeographic patterns are experiencing dramatic changes. The combined influence of multiple human stressors including climate change and artificial shorelines can be evaluated by using a multidisciplinary framework, including ecological distribution, physiological sensitivity of species to these stressors, and the role of dispersal in maintaining population connectivity.

The false smut pathogen Ustilaginoidea virens requires rice stamens for false smut ball formation - Jing Fan; Jie Liu; Zhi‐You Gong; Pei‐Zhou Xu; Xiao‐Hong Hu; Jin‐Long Wu; Guo‐Bang Li; Juan Yang; Yu‐Qiu Wang; Yu‐Feng Zhou; Shuang‐Cheng Li; Li Wang; et al. (Environmental Microbiology, 2020)
Summary Rice false smut has emerged as a serious grain disease in rice production worldwide. The disease is characterized by the transformation of individual rice florets into false smut balls, which is caused by the fungal pathogen Ustilaginoidea virens . To date, little is known about the host factors required for false smut ball formation by U . virens . In this study, we identified histological determinants for the formation of false smut balls by inoculating U . virens into rice floral mutants defective with respect to individual floral parts. The results showed that U . virens could form mature false smut balls in rice floral mutants with defective pistils, but failed to develop false smut balls in the superwoman mutant lacking stamens, identifying that U . virens requires rice stamens to complete its infection cycle. Comparative transcriptome analysis indicated a list of candidate host genes that may facilitate nutrient acquisition by U . virens from the rice stamens, such as SWEET11 , SWEET14 and SUT5 , and genes involved in the biosynthesis of trehalose and raffinose family sugars. These data pinpoint rice stamens as the key target organ of U . virens infection and provide a valuable starting point for dissecting the molecular mechanism of false smut ball formation.

Effects of root exudates on the activation and remediation of cadmium ion in contaminated soils - Cheng Chen; Zhongbao Li; Shengjin Li; Nanxin Deng; Ping Mei (Environmental Science and Pollution Research, 2020)

A challenge in anaerobic digestion of swine wastewater: recalcitrance and enhanced-degradation of dietary fibres - Zhuo Zeng; Ping Zheng; Cheng Shi; Meng Zhang; Yiyu Li; Wudi Zhang; Shengdao Shan (Biodegradation, 2019)

Multi‐model analysis of climate impacts on plant photosynthesis in China during 2000–2015 - Hao Yan; Shao‐Qiang Wang; Jun‐Bang Wang; Yun Cao; Ling‐Ling Xu; Men‐Xin Wu; Lu Cheng; Liu‐Xi Mao; Feng‐Hua Zhao; Xian‐Zhou Zhang; Yun‐Fen Liu; Yan‐Fen Wang; et al. (International Journal of Climatology, 2019)
Differences, arising from differences in gross primary production (GPP) model structures and driving forces, have fuelled arguments concerning interannual changes of GPP in China since 2000. To better investigate the interannual variability of GPP and its covariance with climate factors in China, this study adopted a multi‐model analysis based on three GPP models (i.e., Terrestrial Ecosystem Carbon flux model [TEC], Breathing Earth System Simulator model [BESS], and MOD17 GPP model). The results show that annual GPP in China increased by 0.021–0.057 Pg C year −1 from 2000 to 2015 attributable to atmospheric‐CO 2 fertilization effects and favourable climate change, that is, increasing precipitation ( P r ) and temperature ( T a ). However, northern China and southern China had a large difference in the amplitude of these GPP changes; annual GPP increased by 0.017–0.039 Pg C year −1 in northern China but only 0.001–0.018 Pg C year −1 in southern China. Northern China and southern China occupy contrasting climate zones and this contrast produced different interannual variability of GPP through different mechanisms. Northern China has a dry climate with GPP changes sensitive to P r . As a result, more P r along with higher T a in northern China produced the strong uptrend of GPP from 2000 to 2015. In contrast, southern China has a wet climate with its GPP sensitive to solar radiation and T a . For the interval of 2000–2015, decreasing radiation plus drought exerted a negative influence on GPP in southern China. This study highlights the diverse mechanisms in which climate change affects GPP in dry and wet climate zones. A robust multi‐model analysis is preferred to reduce uncertainties arising from a single GPP model and its driving data.

Exotic Spartina alterniflora invasion alters soil nitrous oxide emission dynamics in a coastal wetland of China - Dengzhou Gao; Lijun Hou; Xiaofei Li; Min Liu; Yanling Zheng; Guoyu Yin; Yi Yang; Cheng Liu; Ping Han (Plant and Soil, 2019)

DNA methylation and mRNA expression of COL6A3 in antler mesenchyme of female and male reindeer - Jian-Cheng Zhai; Ruo-Bing Han; Sheng-Nan Wang; Qiang-Hui Wang; Yan-Ling Xia; Wei-Shi Liu; Ya-Jie Yin; He-Ping Li (Genes & Genomics, 2019)

Experimental investigation on the mechanical characteristics of gas-bearing coal considering the impact of moisture - Ming-yi Chen; Yuan-ping Cheng; Jing-chun Wang; Hao-ran Li; Ning Wang (Arabian Journal of Geosciences, 2019)

F‐box proteins MoFwd1, MoCdc4 and MoFbx15 regulate development and pathogenicity in the rice blast fungus Magnaporthe oryzae - Huan‐Bin Shi; Nan Chen; Xue‐Ming Zhu; Shuang Liang; Lin Li; Jiao‐Yu Wang; Jian‐Ping Lu; Fu‐Cheng Lin; Xiao‐Hong Liu (Environmental Microbiology, 2019)
Summary The Skp1‐Cul1‐F‐box‐protein (SCF) ubiquitin ligases are important parts of the ubiquitin system controlling many cellular biological processes in eukaryotes. However, the roles of SCF ubiquitin ligases remain unclear in phytopathogenic Magnaporthe oryzae . Here, we cloned 24 F‐box proteins and confirmed that 17 proteins could interact with MoSkp1, showing their potential to participate in SCF complexes. To determine their functions, null mutants of 21 F‐box‐containing genes were created. Among them, the F‐box proteins MoFwd1, MoCdc4 and MoFbx15 were found to be required for growth, development and full virulence. Fluorescent‐microscopy observations demonstrated that both MoFbx15 and MoCdc4 were localized to the nucleus, compared with MoFwd1, which was distributed in the cytosol. MoCdc4 and MoFwd1 bound to MoSkp1 via the F‐box domain, the deletion of which abrogated their function. Race tube and qRT‐PCR assays confirmed that MoFwd1 was involved in circadian rhythm by regulating transcription and protein stability of the core circadian clock regulator MoFRQ . Moreover, MoFWD1 also orchestrates conidial germination by influencing conidial amino acids pools and oxidative stress release. Overall, our results indicate that SCF ubiquitin ligases play indispensable roles in development and pathogenicity in M. oryzae .

New adenine analogues and a pyrrole alkaloid from Selaginella delicatula - Cai-Ping Yao; Zhen-Xing Zou; Yan Zhang; Jing Li; Fei Cheng; Ping-Sheng Xu; Gan Zhou; Xiao-Min Li; Kang-Ping Xu; Gui-Shan Tan (Natural Product Research, 2019)

Effect of Interaction between Adenosine and Nitric Oxide on Central Nervous System Oxygen Toxicity - Cheng-wei Xie; Zhong-zhuang Wang; Ya-nan Zhang; Yu-liang Chen; Run-ping Li; Jun-dong Zhang (Neurotoxicity Research, 2019)

Digitizing and modeling of structural planes in fractured rock mass tunnel based on SfM - Shang-qu Sun; Li-ping Li; Cheng-shuai Qin; Hong-liang Liu; Yan-huan Zhang; Xing-zhi Ba (Arabian Journal of Geosciences, 2019)

Gene structure, recombinant expression and function characterization of Siniperca chuatsi Fsrp‐3 - Jianhua Wang; Jia Cheng; Yulong Li; Huiling Yan; Ping Wu; Xin Zhu; Li Liu; Lin Chen; Wuying Chu; Jianshe Zhang (Journal of Fish Biology, 2019)
A full‐length complementary (c)DNA sequence encoding follistatin‐related protein 3 ( fsrp‐3 ) was determined from skeletal muscle in Chinese mandarin fish Siniperca chuatsi , its molecular structure was characterised and its function suggested. The putative structure of S. chuatsi Fsrp‐3 contains an N‐terminal domain and two follistatin domains. Quantitative reverse‐transcription (qRT)‐PCR assays revealed that fsrp‐3 messenger (m)RNA was differentially expressed among assayed tissues and was highly expressed in heart and intestine. fsrp‐3 mRNA exhibited increasing expression from the larval to the juvenile stage (500 g). To investigate the potential function of S. chuatsi fsrp‐3 in muscle growth, we constructed a Fsrp‐3 prokaryotic expression system and injected the purified Fsrp‐3 fusion protein into the dorsal muscle. Fsrp‐3 administration significantly influenced cross‐section area, satellite cell activation frequency and nuclear density of S. chuatsi muscle fibres. Following Fsrp‐3 treatment, the expression of myogenic regulatory factors was up‐regulated and decline in the expression of myostatin was observed. The study revealed that Fsrp‐3 may affect muscle growth by regulating myogenic regulatory factor expression and antagonizing myostatin function to initiate satellite cell activation and differentiation in S. chuatsi .

Crop diversity facilitates soil aggregation in relation to soil microbial community composition driven by intercropping - Xiu-li Tian; Cheng-bao Wang; Xing-guo Bao; Ping Wang; Xiao-fei Li; Si-cun Yang; Guo-chun Ding; Peter Christie; Long Li (Plant and Soil, 2019)

Habitat selection of wintering cranes (Gruidae) in typical lake wetland in the lower reaches of the Yangtze River, China - Cheng Wang; Bin Dong; Ming Zhu; Hui Huang; Yu-huang Cui; Xiang Gao; Li-ping Liu (Environmental Science and Pollution Research, 2019)

Real-time monitoring and quantification of organic by-products and mechanism study of acetone decomposition in a dielectric barrier discharge reactor - Xueshuang Li; Teng Guo; Zhen Peng; Li Xu; Junguo Dong; Ping Cheng; Zhen Zhou (Environmental Science and Pollution Research, 2019)

Attribute recognition model for risk assessment of water inrush - Jing Wang; Shu-cai Li; Li-ping Li; Peng Lin; Zhen-hao Xu; Cheng-lu Gao (Bulletin of Engineering Geology and the Environment, 2019)

Correction to: Magnesium deficiency affects secondary lignification of the vascular system in Citrus sinensis seedlings - Jing-Hao Huang; Jing Xu; Xin Ye; Tu-Yan Luo; Li-Hua Ren; Guo-Cheng Fan; Yi-Ping Qi; Qiang Li; Rhuanito S. Ferrarezi; Li-Song Chen (Trees, 2019)

Magnesium deficiency affects secondary lignification of the vascular system in Citrus sinensis seedlings - Jing-Hao Huang; Jing Xu; Xin Ye; Tu-Yan Luo; Li-Hua Ren; Guo-Cheng Fan; Yi-Ping Qi; Qiang Li; Rhuanito S. Ferrarezi; Li-Song Chen (Trees, 2019)

Transcriptome Reveals Differentially Expressed Genes in Saccharum spontaneum GX83-10 Leaf Under Drought Stress - Kai-Chao Wu; Li-Ping Wei; Cheng-Mei Huang; Yuan-Wen Wei; Hui-Qing Cao; Lin Xu; Hai-Bin Luo; Sheng-Li Jiang; Zhi-Nian Deng; Yang-Rui Li (Sugar Tech, 2018)

Development and characterization of 27 SNP markers in the Mauremys mutica transcriptome - Zhang Xin-Cheng; Zhao Jian; Li Wei; Liu Yi-Hui; Wei Cheng-Qing; Wang Ya-Kun; Ye Zhao-Yang; Zhu Xin-Ping (Conservation Genetics Resources, 2018)

Chemical characteristics, source apportionment, and regional transport of marine fine particles toward offshore islands near the coastline of northwestern Taiwan Strait - Cheng-Chih Chang; Chung-shin Yuan; Tsung-Chang Li; Yen-Lung Su; Chuan Tong; Shui-Ping Wu (Environmental Science and Pollution Research, 2018)

Hazard zoning of trunk highway slope disasters: a case study in northern Shaanxi, China - Huan Zhao; Wei-Ping Tian; Jia-chun Li; Bao-Cheng Ma (Bulletin of Engineering Geology and the Environment, 2018)

Molecular characterization of two novel sub-sublineages of pigeon paramyxovirus type 1 in China - Tianchao Wei; Qiaomu Deng; Haiqiong Li; Chao Pan; Guosheng Zhai; Yadong Yuan; Ercai Cheng; Yuanqin Zhang; Meilan Mo; Teng Huang; Ping Wei (Archives of Virology, 2018)

Preparation and application of magnetic nitrogen-doped rGO for persulfate activation - Ya Pang; Kun Luo; Lin Tang; Xue Li; Yong Song; Cheng-yong Li; Li-ping Wang (Environmental Science and Pollution Research, 2018)

The complete mitochondrial genome of Pseudocrossocheilus bamaensis (Cypriniformes: Cyprinidae: Labeoninae) - Man Zhang; Bo-wen Liu; Guang-ping Cheng; Li Bian; Qi-jia Zhou; Wei-jie Yan; Wen-hong Li (Conservation Genetics Resources, 2018)

Effects of antiepileptic drugs on lipogenic gene regulation and hyperlipidemia risk in Taiwan: a nationwide population-based cohort study and supporting in vitro studies - Yi-Wen Li; Chung-Hsing Wang; Chao-Jung Chen; Charles C. N. Wang; Cheng-Li Lin; Wai-Kok Cheng; Hsin-Yi Shen; Yun-Ping Lim (Archives of Toxicology, 2018)

Design of a Displacement Monitoring System Based on Optical Grating and Numerical Verification in Geomechanical Model Test of Water Leakage of Tunnel - Shang-qu Sun; Shu-cai Li; Li-ping Li; Shao-shuai Shi; Zong-qing Zhou; Cheng-lu Gao (Geotechnical and Geological Engineering, 2018)

Repaglinide-irbesartan drug interaction: effects of SLCO1B1 polymorphism on repaglinide pharmacokinetics and pharmacodynamics in Chinese population - Qi Pei; Jun-Yan Liu; Ji-Ye Yin; Guo-Ping Yang; Shi-Kun Liu; Yi Zheng; Pan Xie; Cheng-Xian Guo; Mi Luo; Hong-Hao Zhou; Xi Li; Zhao-Qian Liu (European Journal of Clinical Pharmacology, 2018)

Collapse behavior and microstructural evolution of loess soils from the Loess Plateau of China - Wan-li Xie; Ping Li; Mao-sheng Zhang; Tian-e Cheng; Yong Wang (Journal of Mountain Science, 2018)

Genetic characterization of phenicol-resistant Escherichia coli and role of wild-type repressor/regulator gene (acrR) on phenicol resistance - Muhammad Yaqoob; Li Ping Wang; Jam Kashif; Javed Memon; Sajid Umar; Muhammad Farooq Iqbal; Muhammad Fiaz; Cheng-Ping Lu (Folia Microbiologica, 2018)

Joint structural and physiological control on the interannual variation in productivity in a temperate grassland: A data‐model comparison - Zhongmin Hu; Hao Shi; Kaili Cheng; Ying‐Ping Wang; Shilong Piao; Yue Li; Li Zhang; Jianyang Xia; Lei Zhou; Wenping Yuan; Steve Running; Longhui Li; et al. (Global Change Biology, 2018)
Given the important contributions of semiarid region to global land carbon cycle, accurate modeling of the interannual variability (IAV) of terrestrial gross primary productivity (GPP) is important but remains challenging. By decomposing GPP into leaf area index (LAI) and photosynthesis per leaf area (i.e., GPP_leaf), we investigated the IAV of GPP and the mechanisms responsible in a temperate grassland of northwestern China. We further assessed six ecosystem models for their capabilities in reproducing the observed IAV of GPP in a temperate grassland from 2004 to 2011 in China. We observed that the responses to LAI and GPP_leaf to soil water significantly contributed to IAV of GPP at the grassland ecosystem. Two of six models with prescribed LAI simulated of the observed IAV of GPP quite well, but still underestimated the variance of GPP_leaf, therefore the variance of GPP. In comparison, simulated pattern by the other four models with prognostic LAI differed significantly from the observed IAV of GPP. Only some models with prognostic LAI can capture the observed sharp decline of GPP in drought years. Further analysis indicated that accurately representing the responses of GPP_leaf and leaf stomatal conductance to soil moisture are critical for the models to reproduce the observed IAV of GPP_leaf. Our framework also identified that the contributions of LAI and GPP_leaf to the observed IAV of GPP were relatively independent. We conclude that our framework of decomposing GPP into LAI and GPP_leaf has a significant potential for facilitating future model intercomparison, benchmarking and optimization should be adopted for future data‐model comparisons.

Inhibition of KLF7-Targeting MicroRNA 146b Promotes Sciatic Nerve Regeneration - Wen-Yuan Li; Wei-Ting Zhang; Yong-Xia Cheng; Yan-Cui Liu; Feng-Guo Zhai; Ping Sun; Hui-Ting Li; Ling-Xiao Deng; Xiao-Feng Zhu; Ying Wang (Neuroscience Bulletin, 2018)

The Risk Assessment of Tunnels Based on Grey Correlation and Entropy Weight Method - Cheng-lu Gao; Shu-cai Li; Jing Wang; Li-ping Li; Peng Lin (Geotechnical and Geological Engineering, 2018)

Avian influenza viruses (AIVs) H9N2 are in the course of reassorting into novel AIVs - Hui-ping Chang; Li Peng; Liang Chen; Lu-fang Jiang; Zhi-jie Zhang; Cheng-long Xiong; Gen-ming Zhao; Yue Chen; Qing-wu Jiang (Journal of Zhejiang University-SCIENCE B, 2018)

Enhancement of the thermal and alkaline pH stability of Escherichia coli lysine decarboxylase for efficient cadaverine production - Fengyu Kou; Jing Zhao; Jiao Liu; Cunmin Sun; Yanmei Guo; Zijian Tan; Feng Cheng; Zhimin Li; Ping Zheng; Jibin Sun (Biotechnology Letters, 2018)

The complete mitogenome of Pelochelys cantorii (Guangning) and the comparative analysis of different habitats - Xin-cheng Zhang; Wei Li; Jian Zhao; Hai-gang Chen; Xin-ping Zhu (Conservation Genetics Resources, 2018)

Nonlinear analysis of the response of a single pile subjected to tension load using a hyperbolic model - Shuai Cheng; Qian-qing Zhang; Shu-cai Li; Li-ping Li; Shi-min Zhang; Kang Wang (European Journal of Environmental and Civil Engineering, 2018)

The role of complementarity and selection effects in P acquisition of intercropping systems - Xiao-Fei Li; Cheng-Bao Wang; Wei-Ping Zhang; Le-Hua Wang; Xiu-Li Tian; Si-Cun Yang; Wan-Li Jiang; Jasper van Ruijven; Long Li (Plant and Soil, 2018)

Correction to: Molecular characterization of a genetically divergent equine pegivirus strain identified in China - Gang Lu; Cheng Fu; Ji Huang; Haibin Xu; Peixin Wu; Xiaokun Ping; Shoujun Li (Archives of Virology, 2018)

Molecular characterization of a genetically divergent equine pegivirus strain identified in China - Gang Lu; Cheng Fu; Ji Huang; Haibin Xu; Peixin Wu; Xiaokun Ping; Shoujun Li (Archives of Virology, 2018)

Cross-neutralization of SARS coronavirus-specific antibodies against bat SARS-like coronaviruses - Lei-Ping Zeng; Xing-Yi Ge; Cheng Peng; Wanbo Tai; Shibo Jiang; Lanying Du; Zheng-Li Shi (Science China Life Sciences, 2017)

Cold-Inducible Protein RBM3 Protects UV Irradiation-Induced Apoptosis in Neuroblastoma Cells by Affecting p38 and JNK Pathways and Bcl2 Family Proteins - Rui-Juan Zhuang; Jian Ma; Xiang Shi; Fei Ju; Shuang-Ping Ma; Lei Wang; Bin-Feng Cheng; Yan-Wen Ma; Mian Wang; Tong Li; Zhi-Wei Feng; Hai-Jie Yang (Journal of Molecular Neuroscience, 2017)

Hydrogen Peroxide and Strigolactones Signaling Are Involved in Alleviation of Salt Stress Induced by Arbuscular Mycorrhizal Fungus in Sesbania cannabina Seedlings - Cun-Cui Kong; Cheng-Gang Ren; Run-Zhi Li; Zhi-Hong Xie; Ji-Ping Wang (Journal of Plant Growth Regulation, 2017)

Environmental change and raw material selection strategies at Taoshan: a terminal Late Pleistocene to Holocene site in north‐eastern China - Shi‐Xia Yang; Yu‐Xiu Zhang; You‐Qian Li; Chao Zhao; Xiao‐Qiang Li; Jian‐Ping Yue; Ya‐Mei Hou; Cheng‐Long Deng; Ri‐Xiang Zhu; Michael D. Petraglia (Journal of Quaternary Science, 2017)
The Lesser Khingan Mountains of north‐eastern China are heavily forested, making archaeological site identification difficult owing to poor ground surface visibility. Nevertheless, several prehistoric archaeological site discoveries have been made in recent years and a limited number of excavations have been initiated. One of the most important sites to emerge is Taoshan, which has yielded stratified stone tool assemblages dating from the Last Glacial Maximum (LGM) to the mid‐Holocene. Pollen profiles indicate significant changes in vegetation, fluctuating from steppe conditions during the LGM to forested conditions in the Bølling–Allerød interstadial (B–A) and the mid‐Holocene. The stone tool assemblages from Taoshan were primarily produced from varieties of volcanic tuff, rhyolite, hornfels and agate. Geological prospecting and petrological analyses were performed to document procurement sources and changes in raw material exploitation strategies. During the LGM, the predominant raw material was vitric tuff, available from a source ca. 5–10 km from Taoshan. In the B–A and mid‐Holocene layers, emphasis was on the exploitation of raw materials in gravel bars, although stone tool reduction techniques and raw material preferences changed considerably during this time interval. Diachronic changes in raw materials and exploitation strategies correspond to changes in vegetation and human adaptations.

LecRK-VII.1, a Lectin Receptor-Like Kinase, Mediates the Regulation of Salt Stress and Jasmonic Acid Response in Arabidopsis - Cheng Zhang; Jinyan Li; Xinhong Guo; Baode Zhu; Wenjun Xiao; Ping Wang; Miao Jiang; Shuai Hu; Xiutao Lu; Zhuang He; Ping Chen (Journal of Plant Growth Regulation, 2017)

Repellence of the main components from the essential oil of Glycosmis lucida Wall. ex Huang against two stored product insects - Shan-Shan Guo; Wen-Juan Zhang; Kai Yang; Jun-Yu Liang; Chun-Xue You; Cheng-Fang Wang; Yin-Ping Li; Zhu-Feng Geng; Zhi-Wei Deng; Shu-Shan Du (Natural Product Research, 2017)

Morphogenesis and Gene Mapping of deformed interior floral organ 1 (difo1), a Novel Mutant Associated with Floral Organ Development in Rice - Lianping P. Sun; Yingxin X. Zhang; Peipei P. Zhang; Zhengfu F. Yang; Xiaoxiao X. Zhou; Dandan D. Xuan; Md Habibur H. Rahman; Zihe H. Li; Weixun X. Wu; Xiaodeng D. Zhan; Xihong H. Shen; Ping Yu; et al. (Plant Molecular Biology Reporter, 2017)

Erratum to: Fine mapping and candidate gene analysis of qHD5, a novel major QTL with pleiotropism for yield-related traits in rice (Oryza sativa L.) - Bin Sun; Xiao-Deng Zhan; Ze-Chuan Lin; Wei-Xun Wu; Ping Yu; Ying-Xin Zhang; Lian-Ping Sun; Li-Yong Cao; Shi-Hua Cheng (Theoretical and Applied Genetics, 2017)

Fine mapping and candidate gene analysis of qHD5, a novel major QTL with pleiotropism for yield-related traits in rice (Oryza sativa L.) - Bin Sun; Xiao-Deng Zhan; Ze-Chuan Lin; Wei-Xun Wu; Ping Yu; Ying-Xin Zhang; Lian-Ping Sun; Li-Yong Cao; Shi-Hua Cheng (Theoretical and Applied Genetics, 2017)

Prolonged exposure to low-dose microcystin induces nonalcoholic steatohepatitis in mice: a systems toxicology study - Jun He; Guangyu Li; Jun Chen; Juan Lin; Cheng Zeng; Jing Chen; Junliang Deng; Ping Xie (Archives of Toxicology, 2017)

Beneficial Effect of Astragaloside on Alzheimer’s Disease Condition Using Cultured Primary Cortical Cells Under β-amyloid Exposure - Ching-Ping Chang; Yu-Fan Liu; Hung-Jung Lin; Chien-Chin Hsu; Bor-Chih Cheng; Wen-Pin Liu; Mao-Tsun Lin; Shu-Fen Hsu; Li-Sheng Chang; Kao-Chang Lin (Molecular Neurobiology, 2016)

Analgesic Effects of Danggui-Shaoyao-San on Various “Phenotypes” of Nociception and Inflammation in a Formalin Pain Model - Jun-Bin Yin; Ke-Cheng Zhou; Huang-Hui Wu; Wei Hu; Tan Ding; Ting Zhang; Li-Ying Wang; Jun-Ping Kou; Alan David Kaye; Wen Wang (Molecular Neurobiology, 2016)

Thrombospondin-4 Promotes Neuronal Differentiation of NG2 Cells via the ERK/MAPK Pathway - Hai Jie Yang; Shuang Ping Ma; Fei Ju; Ya Ping Zhang; Zhi Chao Li; Bin Bin Zhang; Jun Jiang Lian; Lei Wang; Bin Feng Cheng; Mian Wang; Zhi Wei Feng (Journal of Molecular Neuroscience, 2016)

Fine mapping of the Rsv1-h gene in the soybean cultivar Suweon 97 that confers resistance to two Chinese strains of the soybean mosaic virus - Fang-Fang Ma; Xiao-Yi Wu; Yun-Xia Chen; Ying-Na Liu; Zhu-Qing Shao; Ping Wu; Mian Wu; Cheng-Chen Liu; Wen-Ping Wu; Jia-Yin Yang; De-Xiao Li; Jian-Qun Chen; et al. (Theoretical and Applied Genetics, 2016)

The unique origin of orange carrot cultivars in China - Zhen-Guo Ma; Xiao-Ping Kong; Li-Jie Liu; Cheng-Gang Ou; Ting-Ting Sun; Zhi-Wei Zhao; Zeng-Jian Miao; Jun Rong; Fei-Yun Zhuang (Euphytica, 2016)

Se Enhances MLCK Activation by Regulating Selenoprotein T (SelT) in the Gastric Smooth Muscle of Rats - Jia-ping Li; Jing-xuan Zhou; Qi Wang; Gao-qin Gu; Shi-jin Yang; Cheng-ye Li; Chang-wei Qiu; Gan-zhen Deng; Meng-yao Guo (Biological Trace Element Research, 2016)

Expression and functional analysis of two NhaD type antiporters from the halotolerant and alkaliphilic Halomonas sp. Y2 - Yanbing Cui; Bin Cheng; Yiwei Meng; Chunfang Li; Huijia Yin; Ping Xu; Chunyu Yang (Extremophiles, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

Highly selective and efficient biotransformation of linarin to produce tilianin by naringinase - Pan Cui; Tong-Yi Dou; Shi-Yang Li; Jun-Xia Lu; Li-Wei Zou; Ping Wang; Yan-Ping Sun; Da-Cheng Hao; Guang-Bo Ge (Biotechnology Letters, 2016)

Male-Biased Capture in Light Traps in Spodoptera exigua (Lepidoptera: Noctuidae): Results from the Studies of Reproductive Activities - Wen-Jie Cheng; Xia-Lin Zheng; Pan Wang; Li-Lin Zhou; Sheng-Yun Si; Xiao-Ping Wang (Journal of Insect Behavior, 2016)

A novel short anionic antibacterial peptide isolated from the skin of Xenopus laevis with broad antibacterial activity and inhibitory activity against breast cancer cell - Siming Li; Linlin Hao; Wanguo Bao; Ping Zhang; Dan Su; Yunyun Cheng; Linyan Nie; Gang Wang; Feng Hou; Yang Yang (Archives of Microbiology, 2016)

The Effects of Molecular Properties on Ready Biodegradation of Aromatic Compounds in the OECD 301B CO2 Evolution Test - Mei He; Cheng-Fang Mei; Guo-Ping Sun; Hai-Bei Li; Lei Liu; Mei-Ying Xu (Archives of Environmental Contamination and Toxicology, 2016)

Chip-based visual detection of microRNA using DNA-functionalized gold nanoparticles - Ping Wang; Jianlong Zhao; Bin Hu; Zule Cheng; Yanan Bai; Qinghui Jin; Huiying Liu; Hongju Mao; Sanqiang Li; Jianlong Zhao (Science China Life Sciences, 2016)

Increasing the immune activity of exosomes: the effect of miRNA-depleted exosome proteins on activating dendritic cell/cytokine-induced killer cells against pancreatic cancer - Ri-sheng Que; Cheng Lin; Guo-ping Ding; Zheng-rong Wu; Li-ping Cao (Journal of Zhejiang University-SCIENCE B, 2016)

The use of food waste-based diets and Napier grass to culture grass carp: growth performance and contaminants contained in cultured fish - Zhang Cheng; Wing-Yin Mo; Xiang-Ping Nie; Kai-Bing Li; Wai-Ming Choi; Yu-Bon Man; Ming-Hung Wong (Environmental Science and Pollution Research, 2016)

Feeding ecology of the mud shrimp S olenocera melantho in the E ast C hina S ea - Hui Yu Li; Jian Zhong Ling; Li Ping Yan; Jia Hua Cheng; Fen Hu (Marine Ecology, 2016)
The feeding habits of the mud shrimp Solenocera melantho were studied in the East China Sea by analysing 720 stomach contents and comparing diet composition and prey diversity among seasons, sexes and size classes. Feeding activity was linked to season and ovarian condition. The stomach fullness was high during spring and summer and low in fall. Females with advanced ovaries also displayed low stomach fullness, which suggests that feeding activity is affected by the reproductive cycle. The diet of S. melantho consisted of 42 different prey categories, primarily smaller crustaceans, Foraminifera, polychaetes, mollusks and fishes (larvae and eggs). Crustacea,Foraminifera and polychaetes together constituted the dominant prey groups, accounting for 75% of total prey abundance and >50% of total prey occurrence. Diet composition differed among seasons between sexes and size classes. Females and males consumed the same prey items but with different orders of importance. In terms of body size, the small shrimps preferred relatively small food items, such as Foraminifera and algae, whereas larger shrimps preferred polychaetes and crustaceans. Trophic diversity varied among the seasons within both sexes and size classes, with the highest values being observed in fall. Niche overlap was high within both sexes and size classes among seasons (0.6051–0.8740).

Erratum to: Quantitatively evaluating detoxification of the hepatotoxic microcystin-LR through the glutathione (GSH) pathway in SD rats - Xiaochun Guo; Liang Chen; Jun Chen; Ping Xie; Shangchun Li; Jun He; Wei Li; Huihui Fan; Dezhao Yu; Cheng Zeng (Environmental Science and Pollution Research, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Global patterns and climate drivers of water‐use efficiency in terrestrial ecosystems deduced from satellite‐based datasets and carbon cycle models - Yan Sun; Shilong Piao; Mengtian Huang; Philippe Ciais; Zhenzhong Zeng; Lei Cheng; Xiran Li; Xinping Zhang; Jiafu Mao; Shushi Peng; Benjamin Poulter; Xiaoying Shi; et al. (Global Ecology and Biogeography, 2016)
Aim To investigate how ecosystem water‐use efficiency ( WUE ) varies spatially under different climate conditions, and how spatial variations in WUE differ from those of transpiration‐based water‐use efficiency ( WUE t ) and transpiration‐based inherent water‐use efficiency ( IWUE t ). Location Global terrestrial ecosystems. Methods We investigated spatial patterns of WUE using two datasets of gross primary productivity ( GPP ) and evapotranspiration ( ET ) and four biosphere model estimates of GPP and ET . Spatial relationships between WUE and climate variables were further explored through regression analyses. Results Global WUE estimated by two satellite‐based datasets is 1.9 ± 0.1 and 1.8 ± 0.6 g C m −2 mm −1 lower than the simulations from four process‐based models (2.0 ± 0.3 g C m −2 mm −1 ) but comparable within the uncertainty of both approaches. In both satellite‐based datasets and process models, precipitation is more strongly associated with spatial gradients of WUE for temperate and tropical regions, but temperature dominates north of 50° N . WUE also increases with increasing solar radiation at high latitudes. The values of WUE from datasets and process‐based models are systematically higher in wet regions (with higher GPP ) than in dry regions. WUE t shows a lower precipitation sensitivity than WUE , which is contrary to leaf‐ and plant‐level observations. IWUE t , the product of WUE t and water vapour deficit, is found to be rather conservative with spatially increasing precipitation, in agreement with leaf‐ and plant‐level measurements. Main conclusions WUE , WUE t and IWUE t produce different spatial relationships with climate variables. In dry ecosystems, water losses from evaporation from bare soil, uncorrelated with productivity, tend to make WUE lower than in wetter regions. Yet canopy conductance is intrinsically efficient in those ecosystems and maintains a higher IWUE t . This suggests that the responses of each component flux of evapotranspiration should be analysed separately when investigating regional gradients in WUE , its temporal variability and its trends.

A theoretical analysis of the bearing performance of vertically loaded large-diameter pipe pile groups - Xuanming Ding; Ting Zhang; Ping Li; Ke Cheng (Journal of Ocean University of China, 2016)

Gas desorption index of drill cuttings affected by magmatic sills for predicting outbursts in coal seams - Long-biao Cheng; Liang Wang; Yuan-ping Cheng; Kan Jin; Wei Zhao; Li-shuo Sun (Arabian Journal of Geosciences, 2016)

Quantitatively evaluating detoxification of the hepatotoxic microcystin-LR through the glutathione (GSH) pathway in SD rats - Xiaochun Guo; Liang Chen; Jun Chen; Ping Xie; Shangchun Li; Jun He; Wei Li; Huihui Fan; Dezhao Yu; Cheng Zeng (Environmental Science and Pollution Research, 2015)

Rice grassy stunt virus nonstructural protein p5 serves as a viral suppressor of RNA silencing and interacts with nonstructural protein p3 - Chao Zhang; Xiao-juan Liu; Kang-cheng Wu; Lu-Ping Zheng; Zuo-mei Ding; Fei Li; Peng Zou; Liang Yang; Jian-guo Wu; Zu-jian Wu (Archives of Virology, 2015)

Effects of pre-harvest chemical application on rice desiccation and seed quality - Yong-qi He; Jin-ping Cheng; Liang-feng Liu; Xiao-dan Li; Bin Yang; Hong-sheng Zhang; Zhou-fei Wang (Journal of Zhejiang University-SCIENCE B, 2015)

Cloning of the Aegiceras corniculatum class I chitinase gene (AcCHI I) and the response of AcCHI I mRNA expression to cadmium stress - Li-Ying Wang; You-Shao Wang; Hao Cheng; Jing-Ping Zhang; Foong Swee Yeok (Ecotoxicology, 2015)

Cutaneous Chromoblastomycosis Caused by Veronaea botryosa in a Patient with Pemphigus Vulgaris and Review of Published Reports - Cheng-Yao Zhu; Yan-Ping Yang; Ping Sheng; Wen Li; Wen-Ming Huang; Yi-Ming Fan (Mycopathologia, 2015)

Safety and efficacy study of lung cancer stem cell vaccine - Mao Lin; Shu-Ying Li; Ke-Cheng Xu; Zheng-Ping Liu; Feng Mu; Yuan-Ying Yuan; Xiao-Hua Wang; Ji-Bing Chen; Qiao Li (Immunologic Research, 2015)

Serine/Threonine-Protein Kinase PFTK1 Modulates Oligodendrocyte Differentiation via PI3K/AKT Pathway - Hai Jie Yang; Lei Wang; Mian Wang; Shuang Ping Ma; Bin Feng Cheng; Zhi Chao Li; Zhi Wei Feng (Journal of Molecular Neuroscience, 2015)

Exploring the Wnt Pathway-Associated LncRNAs and Genes Involved in Pancreatic Carcinogenesis Driven by Tp53 Mutation - Qi Wang; He Jiang; Chen Ping; Ruizhe Shen; Tingting Liu; Juanjuan Li; Yuting Qian; Yanping Tang; Shidan Cheng; Weiyan Yao; Lifu Wang (Pharmaceutical Research, 2015)

Host-Choice Behavior of Diaphorina citri Kuwayama (Hemiptera: Psyllidae) Under Laboratory Conditions - Chuan-Qing Ruan; David G. Hall; Bo Liu; Yong-Ping Duan; Tao Li; Han-Qing Hu; Guo-Cheng Fan (Journal of Insect Behavior, 2015)

Genetic diversity and evolution of two capsid protein genes of citrus tristeza virus isolates from China - Guan-Wei Wu; Min Tang; Guo-Ping Wang; Feng-Yin Jin; Zuo-Kun Yang; Li-Jing Cheng; Ni Hong (Archives of Virology, 2015)

Variable-coordinate forward modeling of irregular surface based on dual-variable grid - Jian-Ping Huang; Ying-Ming Qu; Qing-Yang Li; Zhen-Chun Li; Guo-Lei Li; Chang-Cheng Bu; Hou-Hua Teng (Applied Geophysics, 2015)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

Genome-wide discovery of novel and conserved microRNAs in white shrimp (Litopenaeus vannamei) - Qian-Yun Xi; Yuan-Yan Xiong; Yuan-Mei Wang; Xiao Cheng; Qi-En Qi; Gang Shu; Song-Bo Wang; Li-Na Wang; Ping Gao; Xiao-Tong Zhu; Qing-Yan Jiang; Yong-Liang Zhang; et al. (Molecular Biology Reports, 2015)

Gelsolin: Role of a Functional Protein in Mitigating Radiation Injury - Mingjuan Li; Fengmei Cui; Ying Cheng; Ling Han; Jia Wang; Ding Sun; Yu-long Liu; Ping-kun Zhou; Rui Min (Cell Biochemistry and Biophysics, 2015)

Optimal intervention time of vagal stimulation attenuating myocardial ischemia/reperfusion injury in rats - Qiang Wang; Rui-Ping Li; Fu-Shan Xue; Shi-Yu Wang; Xin-Long Cui; Yi Cheng; Gao-Pu Liu; Xu Liao (Inflammation Research, 2014)

ABI-like transcription factor gene TaABL1 from wheat improves multiple abiotic stress tolerances in transgenic plants - Dong-Bei Xu; Shi-Qing Gao; You-Zhi Ma; Zhao-Shi Xu; Chang-Ping Zhao; Yi-Miao Tang; Xue-Yin Li; Lian-Cheng Li; Yao-Feng Chen; Ming Chen (Functional & Integrative Genomics, 2014)

Identification of a potential novel type of influenza virus in Bovine in China - Wen-Ming Jiang; Su-Chun Wang; Cheng Peng; Jian-Min Yu; Qing-Ye Zhuang; Guang-Yu Hou; Shuo Liu; Jin-Ping Li; Ji-Ming Chen (Virus Genes, 2014)

The evolution of permeability and gas composition during remote protective longwall mining and stress-relief gas drainage: a case study of the underground Haishiwan Coal Mine - Wei Li; Yuan-ping Cheng; Pin-kun Guo; Feng-hua An; Ming-yi Chen (Geosciences Journal, 2014)

Carbamodithioate-Based Dual Functional Fluorescent Probe for Hg2+ and S2− - Xiaohong Cheng; Shuang Li; Zhicheng Zhong; Song Wang; Ping He (Journal of Fluorescence, 2014)

Expression and localization of transcription factors SNAIL and SLUG in mouse ovaries and pre-implantation embryos - Cui Guo; Xiaoqian Meng; Jing Bai; Cheng Chen; Tao Liu; Shuzhen Liu; Cong Zhang; Wei-Ping Li (Cell and Tissue Research, 2014)

Isolation and functional characterization of a novel rice constitutive promoter - Juan Li; Rong-Fang Xu; Rui-Ying Qin; Hui Ma; Hao Li; Ying-Ping Zhang; Li Li; Peng-Cheng Wei; Jian-Bo Yang (Plant Cell Reports, 2014)

PI3K/Akt/uncoupling protein 2 signaling pathway may be involved in cell senescence and apoptosis induced by angiotensin II in human vascular endothelial cells - Ping Li; Xin Guo; Pingping Lei; Shoujun Shi; Shike Luo; Xiaoshu Cheng (Molecular Biology Reports, 2014)

IL-17A promotes ventricular remodeling after myocardial infarction - Su-Feng Zhou; Jing Yuan; Meng-Yang Liao; Ni Xia; Ting-Ting Tang; Jing-Jing Li; Jiao Jiao; Wen-Yong Dong; Shao-Fang Nie; Zheng-Feng Zhu; Wen-Cai Zhang; Bing-Jie Lv; et al. (Journal of Molecular Medicine, 2014)

Biofilm Formation of Streptococcus equi ssp. zooepidemicus and Comparative Proteomic Analysis of Biofilm and Planktonic Cells - Li Yi; Yang Wang; Zhe Ma; Hui Zhang; Yue Li; Jun-xi Zheng; Yong-chun Yang; Hong-jie Fan; Cheng-ping Lu (Current Microbiology, 2014)

Mutations in Ralstonia solanacearum loci involved in lipopolysaccharide biogenesis, phospholipid trafficking and peptidoglycan recycling render bacteriophage infection - Yu-Hau Hong; Chi Huang; Kuan-Chung Wang; Tai-Hsiang Chu; Chien-Hui Li; Yu-Ju Chu; Chiu-Ping Cheng (Archives of Microbiology, 2014)

Early channel transurethral resection of the prostate for patients with urinary retention after brachytherapy - You-yun Zhang; Zhi-gen Zhang; Yan-lan Yu; Yi-cheng Chen; Kang-xin Ni; Ming-chao Wang; Wei-ping Zhao; Faisal Rehman; Shaw P. Wan; Gong-hui Li (Journal of Zhejiang University-SCIENCE B, 2014)

Profiles, sources, and transport of polycyclic aromatic hydrocarbons in soils affected by electronic waste recycling in Longtang, south China - De-Yin Huang; Chuan-Ping Liu; Fang-Bai Li; Tong-Xu Liu; Cheng-Shuai Liu; Liang Tao; Yan Wang (Environmental Monitoring and Assessment, 2014)

Bayesian uncertainty analysis in hydrological modeling associated with watershed subdivision level: a case study of SLURP model applied to the Xiangxi River watershed, China - Jing-Cheng Han; Guo-He Huang; Hua Zhang; Zhong Li; Yong-Ping Li (Stochastic Environmental Research and Risk Assessment, 2014)

Structure-based design, synthesis, and anticonvulsant activity of isatin-1-N-phenylacetamide derivatives - Chao Xie; Li-Ming Tang; Fu-Nan Li; Li-Ping Guan; Cheng-Yan Pan; Si-Hong Wang (Medicinal Chemistry Research, 2014)

A dwarfing mutant caused by deactivation function of alpha subunit of the heterotrimeric G-protein in rice - De-wei Yang; Xiang-hua Zheng; Chao-ping Cheng; Wen-da Wang; Deng-hui Xing; Li-bin Lu; Chen-de Liu; Ning Ye; Mei-juan Zeng; Xin-fu Ye (Euphytica, 2014)

Photosynthetic activity and efficiency of Bothriochloa ischaemum and Lespedeza davurica in mixtures across growth periods under water stress - Wei-Zhou Xu; Xi-Ping Deng; Bing-Cheng Xu; Zhi-Juan Gao; Wen-Li Ding (Acta Physiologiae Plantarum, 2014)

Characteristics of gas disaster in the Huaibei coalfield and its control and development technologies - Liang Wang; Yuan-ping Cheng; Feng-hua An; Hong-xing Zhou; Sheng-li Kong; Wei Wang (Natural Hazards, 2014)

Assessment of wheat variety stability using SSR markers - Li Xin Wang; Hong Bo Li; Tie Cheng Gu; Li Hua Liu; Bin Shuang Pang; Jun Qiu; Chang Ping Zhao (Euphytica, 2014)

Effects of watershed subdivision level on semi-distributed hydrological simulations: case study of the SLURP model applied to the Xiangxi River watershed, China - Jing-Cheng Han; Guo-He Huang; Hua Zhang; Zhong Li; Yong-Ping Li (Hydrological Sciences Journal, 2014)

Charlson comorbidity index helps predict the risk of mortality for patients with type 2 diabetic nephropathy - You-Qun Huang; Rong Gou; Yong-Shu Diao; Qing-Hua Yin; Wen-Xing Fan; Ya-Ping Liang; Yi Chen; Min Wu; Li Zang; Ling Li; Jing Zang; Lu Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Damage and Permeability Development in Coal During Unloading - Hai-Dong Chen; Cheng Yuan-Ping; Hong-Xing Zhou; Wei Li (Rock Mechanics and Rock Engineering, 2013)

The discovery of 3-(1-aminoethylidene)quinoline-2, 4(1H,3H)-dione derivatives as novel PSII electron transport inhibitors - Yu-Xiu Liu; Hua-Ping Zhao; Zi-Wen Wang; Yong-Hong Li; Hai-Bin Song; Hannah Riches; David Beattie; Yu-Cheng Gu; Qing-Min Wang (Molecular Diversity, 2013)

Identification of wheat-Secale africanum chromosome 2Rafr introgression lines with novel disease resistance and agronomic characteristics - Meng-Ping Lei; Guang-Rong Li; Li Zhou; Cheng-Hui Li; Cheng Liu; Zu-Jun Yang (Euphytica, 2013)

Cytochrome P450 2A6 deletion polymorphism and risk of lung cancer: a meta-analysis - Zheng-Bing Liu; Jun Shu; Li-Ping Wang; Cheng Jin; Zhi-Xia Lou (Molecular Biology Reports, 2013)

Stereoselective syntheses of functionalized spirocyclopenteneoxindoles via triphenylphosphine-catalyzed [3+2] cycloaddition reactions - Qing-Fa Zhou; Xue-Ping Chu; Fei-Fei Ge; Cheng Li; Tao Lu (Molecular Diversity, 2013)

Influence of serum adiponectin level and SNP +45 polymorphism of adiponectin gene on myocardial fibrosis - Cheng-jun Yan; Su-mei Li; Qiang Xiao; Yan Liu; Jian Hou; Ai-fang Chen; Li-ping Xia; Xiu-chang Li (Journal of Zhejiang University-SCIENCE B, 2013)

Continuous evolution of avian infectious bronchitis virus resulting in different variants co-circulating in southern China - Meng Li; Mei-Lan Mo; Bai-Cheng Huang; Wen-Sheng Fan; Zheng-Ji Wei; Tian-Chao Wei; Kang-Ran Li; Ping Wei (Archives of Virology, 2013)

New kaurene diterpenoid glycosides from fenugreek seeds - Xu Pang; Li-Ping Kang; He-Shui Yu; Yang Zhao; Cheng-Qi Xiong; Jie Zhang; Bai-Ping Ma (Natural Product Research, 2013)

Arsenic contamination in the freshwater fish ponds of Pearl River Delta: bioaccumulation and health risk assessment - Zhang Cheng; Kun-Ci Chen; Kai-Bin Li; Xiang-Ping Nie; Sheng Chun Wu; Chris Kong-Chu Wong; Ming-Hung Wong (Environmental Science and Pollution Research, 2013)

Warnstorfia exannulata, an aquatic moss in the Arctic: seasonal growth responses - Cai-Qing Guo; Ryszard Ochyra; Peng-Cheng Wu; Rodney D. Seppelt; Yi-Feng Yao; Lin-Gen Bian; Su-Ping Li; Cheng-Sen Li (Climatic Change, 2013)

A consensus envelope protein domain III can induce neutralizing antibody responses against serotype 2 of dengue virus in non-human primates - Hsin-Wei Chen; Shih-Jen Liu; Yi-Shiuan Li; Hsueh-Hung Liu; Jy-Ping Tsai; Chen-Yi Chiang; Mei-Yu Chen; Chyi-Sing Hwang; Chin-Cheng Huang; Hui-Mei Hu; Han-Hsuan Chung; Sze-Hsien Wu; et al. (Archives of Virology, 2013)

Finer resolution observation and monitoring of global land cover: first mapping results with Landsat TM and ETM+ data - Peng Gong; Jie Wang; Le Yu; Yongchao Zhao; Yuanyuan Zhao; Lu Liang; Zhenguo Niu; Xiaomeng Huang; Haohuan Fu; Shuang Liu; Congcong Li; Xueyan Li; et al. (International Journal of Remote Sensing, 2013)

A new furolactone-type lignan from Lycium chinense - Xing-Nuo Li; Chu Chu; Sheng-Qiang Tong; Dong-Ping Cheng; Ji-Zhong Yan (Natural Product Research, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Transforming growth factor-β1 induces matrix metalloproteinase-9 expression in rat vascular smooth muscle cells via ROS-dependent ERK–NF-κB pathways - Hao Zhang; Zhi-Wei Wang; Hong-Bing Wu; Zhi Li; Luo-Cheng Li; Xiao-Ping Hu; Zong-Li Ren; Bai-Jun Li; Zhi-Peng Hu (Molecular and Cellular Biochemistry, 2012)

Regulatory long non-coding RNA and its functions - Yong Huang; Ning Liu; Jian Ping Wang; Yu Qin Wang; Xue Li Yu; Zhan Bin Wang; Xiang Chao Cheng; Quan Zou (Journal of Physiology and Biochemistry, 2012)

Enhanced overall resistance to Fusarium seedling blight and Fusarium head blight in transgenic wheat by co-expression of anti-fungal peptides - Zheng-Wei Liu; He-Ping Li; Wei Cheng; Peng Yang; Jing-Bo Zhang; An-Dong Gong; Yan-Ni Feng; W. G. Dilantha Fernando; Yu-Cai Liao (European Journal of Plant Pathology, 2012)

Postconditioning with vagal stimulation attenuates local and systemic inflammatory responses to myocardial ischemia reperfusion injury in rats - Qiang Wang; Yi Cheng; Fu-Shan Xue; Yu-Jing Yuan; Jun Xiong; Rui-Ping Li; Xu Liao; Jian-Hua Liu (Inflammation Research, 2012)

Genome characterization of a novel porcine bocavirus - Wan-zhu Yang; Jie-mei Yu; Jin-song Li; Wei-xia Cheng; Can-ping Huang; Zhao-jun Duan (Archives of Virology, 2012)

Two phthalide dimers from the radix of Angelica sinensis - Xing-Nuo Li; Yuan-Yi Chen; Dong-Ping Cheng; Sheng-Qiang Tong; Hai-Bin Qu; Ji-Zhong Yan (Natural Product Research, 2012)

Genome sequence determination and analysis of a Chinese virulent strain, LMS, of Gallid herpesvirus type 2 - Yun Cheng; Feng Cong; Yan-ping Zhang; Zhi-jie Li; Na-na Xu; Guang-yu Hou; Chang-jun Liu (Virus Genes, 2012)

S-nitrosylation of c-Src via NMDAR-nNOS module promotes c-Src activation and NR2A phosphorylation in cerebral ischemia/reperfusion - Li-Juan Tang; Chong Li; Shu-Qun Hu; Yong-Ping Wu; Yan-Yan Zong; Chang-Cheng Sun; Fa Zhang; Guang-Yi Zhang (Molecular and Cellular Biochemistry, 2012)

Human anti-EGFL7 recombinant full-length antibodies selected from a mammalian cell-based antibody display library - Feng Li; Yan-Hong Liu; Yan-Wen Li; Qian Ju; Lin Chen; Ping-Li Xie; Yue-Hui Li; Guan-Cheng Li (Molecular and Cellular Biochemistry, 2012)

C/EBP-α ameliorates CCl4-induced liver fibrosis in mice through promoting apoptosis of hepatic stellate cells with little apoptotic effect on hepatocytes in vitro and in vivo - Li-Li Tao; Yuan-Yuan Cheng; Di Ding; Shuang Mei; Jia-Wen Xu; Juan Yu; Qi Ou-Yang; Long Deng; Qi Chen; Qing-Quan Li; Zu-De Xu; Xiu-Ping Liu (Apoptosis, 2012)

Proteomic Analysis of Osmotic Stress-Responsive Proteins in Sugarcane Leaves - Gui Zhou; Li-Tao Yang; Yang-Rui Li; Cheng-Lin Zou; Li-Ping Huang; Li-Hang Qiu; Xing Huang; Manoj Kumar Srivastava (Plant Molecular Biology Reporter, 2012)

Characterization of the expression profiles of calpastatin (CAST) gene in chicken - Zeng-Rong Zhang; Xiao-Song Jiang; Hua-Rui Du; Qing Zhu; Xiao-Cheng Li; Chao-Wu Yang; Yi-Ping Liu (Molecular Biology Reports, 2012)

Involvement of KATP/PI3K/AKT/Bcl-2 Pathway in Hydrogen Sulfide-induced Neuroprotection Against the Toxicity of 1-methy-4-phenylpyridinium Ion - Xiao-Qing Tang; Yuan-Yuan Zhuang; Li-Li Fan; Heng-Rong Fang; Cheng-Fang Zhou; Ping Zhang; Bi Hu (Journal of Molecular Neuroscience, 2012)

Type 17 T-helper cells might be a promising therapeutic target for osteoporosis - Feng-Lai Yuan; Xia Li; Wei-Guo Lu; Yi-Qing Zhao; Cheng-Wan Li; Jian-Ping Li; Jun-Ming Sun; Rui-Sheng Xu (Molecular Biology Reports, 2012)

Comparative full-length sequence analysis of Marek’s disease virus vaccine strain 814 - Feng Zhang; Chang-Jun Liu; Yan-Ping Zhang; Zhi-Jie Li; Ai-Ling Liu; Fu-Hai Yan; Feng Cong; Yun Cheng (Archives of Virology, 2012)

A new iridoid compound from Patrinia rupestris (Pall.) Juss. - Dong-Feng Qiu; Xiu-Ping Yang; Yang-Jun Xu; Xiao-Qing Liu; Hong-Li Liu; Cheng-Shan Yuan (Natural Product Research, 2011)

Physical and Mechanical Properties of Fine-Grained Soil in the Zhejiang-Fujian Coastal Area, China - Yuan-Qin Xu; Pei-Ying Li; Ping Li; Le-Jun Liu; Cheng-Xiao Cao; Xiu-Li Feng (Marine Georesources & Geotechnology, 2011)

Microsatellite DNA markers for mating systems analysis in the Leishan moustache toad (Vibrissaphora leishanensis) - Juan Wang; Jian Cheng; Rui-Ping Zhang; Yong-Zhen Wang; Chen-Liang Li; Hua Wu (Conservation Genetics Resources, 2011)

Microsatellite Analysis of Homozygosity Progression of Heterozygous Genotypes Segregating in the Rice Subspecies Cross Pei’ai64s/Nipponbare - Yong-shu Liang; Qi-jun Zhang; Shi-quan Wang; Li-yong Cao; Zhi-qiang Gao; Ping Li; Shi-hua Cheng (Biochemical Genetics, 2011)

Mercury Biomagnification in the Aquaculture Pond Ecosystem in the Pearl River Delta - Zhang Cheng; Peng Liang; Ding-Ding Shao; Sheng-Chun Wu; Xiang-Ping Nie; Kun-Ci Chen; Kai-Bin Li; Ming-Hung Wong (Archives of Environmental Contamination and Toxicology, 2011)

Occurrence and transmission of class 1 and 2 integrons among phenotypic highly ampicillin-resistant avian Escherichia coli isolates from Pakistan - Muhammad Yaqoob; Li Ping Wang; Tang Fang; Cheng-Ping Lu (World Journal of Microbiology and Biotechnology, 2011)

Induction of somatic embryogenesis from female flower buds of elite Schisandra chinensis - Jing Li Yang; Yu Da Niu; Chuan Ping Yang; Gui Feng Liu; Cheng Hao Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Fenvalerate induces germ cell apoptosis in mouse testes through the Fas/FasL signaling pathway - Xian-Feng Zhao; Qun Wang; Yan-Li Ji; Hua Wang; Ping Liu; Cheng Zhang; Ying Zhang; De-Xiang Xu (Archives of Toxicology, 2011)

Morphological and molecular evidences for a new species of Lignosus (Polyporales, Basidiomycota) from tropical China - Bao-Kai Cui; Li-Ping Tang; Yu-Cheng Dai (Mycological Progress, 2011)

Profile of Organochlorine Pesticides in Soil Cores from Some Hotspot Areas of Beijing, China - Hang-Xin Cheng; Xing-Hong Li; Ya-Ping Wang; Chuan-Dong Zhao; Ying-Han Liu; Hong-Han Chen; Xiao-Bai Xu (Bulletin of Environmental Contamination and Toxicology, 2011)

Interaction of green tea polyphenol epigallocatechin-3-gallate with sunitinib: potential risk of diminished sunitinib bioavailability - Jun Ge; Ben-Xu Tan; Ye Chen; Li Yang; Xing-Chen Peng; Hong-Ze Li; Hong-Jun Lin; Yu Zhao; Meng Wei; Ke Cheng; Long-Hao Li; Hang Dong; et al. (Journal of Molecular Medicine, 2011)

Trichodermanin A, a novel diterpenoid from endophytic fungus culture - Pei-Xin Sun; Cheng-Jian Zheng; Wen-Chao Li; Gui-Lin Jin; Fang Huang; Lu-Ping Qin (Journal of Natural Medicines, 2011)

An improved Markov chain model based on autocorrelation and entropy techniques and its application to state prediction of water resources - Ping Zhou; Yuliang Zhou; Juliang Jin; Li Liu; Zongzhi Wang; Liang Cheng; Libing Zhang (Chinese Geographical Science, 2011)

Targeting interleukin-21 in rheumatoid arthritis - Feng-Lai Yuan; Wei Hu; Wei-Guo Lu; Xia Li; Jian-Ping Li; Rui-Sheng Xu; Cheng-Wan Li; Fei-Hu Chen; Cheng Jin (Molecular Biology Reports, 2011)

Prevention of cerebral ischemia-induced memory deficits by inhibition of phosphodiesterase-4 in rats - Ling-Xia Li; Yu-Fang Cheng; Huan-Bing Lin; Chuang Wang; Jiang-Ping Xu; Han-Ting Zhang (Metabolic Brain Disease, 2011)

Abnormal expression and dysfunction of novel SGLT2 mutations identified in familial renal glucosuria patients - Lei Yu; Ji-Cheng Lv; Xu-jie Zhou; Li Zhu; Ping Hou; Hong Zhang (Human Genetics, 2011)

Studies on reproductive characteristics of an interspecific chimera between Brassica juncea and Brassica oleracea - Yan Wang; Qi Cheng; Xue-Yun Zhu; Li-Ping Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Adenovirus-mediated delivery of shRNA against bFGF mRNA suppresses growth of cultured human primary prostatic stromal cells - Kai Wang; Linfeng Cheng; Yinghong Liang; Donghui Liu; Kai Li; Ping Wang (Molecular Biology Reports, 2011)

Single-step chromatography for simultaneous purification of C-phycocyanin and allophycocyanin with high purity and recovery from Spirulina (Arthrospira) platensis - Shi-Gan Yan; Li-Ping Zhu; Hai-Nan Su; Xi-Ying Zhang; Xiu-Lan Chen; Bai-Cheng Zhou; Yu-Zhong Zhang (Journal of Applied Phycology, 2011)

Localization and Characterization of GTP-Binding Protein CT703 in the Chlamydia trachomatis-Infected Cells - Kun Du; FuYan Wang; Zhi Huo; Jie Wang; Wen Cheng; Ming Li; Ping Yu (Current Microbiology, 2011)

Molecular cytogenetic identification of a new wheat-Thinopyrum substitution line with stripe rust resistance - Li-Jun Hu; Guang-Rong Li; Zi-Xian Zeng; Zhi-Jian Chang; Cheng Liu; Jian-Ping Zhou; Zu-Jun Yang (Euphytica, 2011)

Inhibition of acid-sensing ion channels in articular chondrocytes by amiloride attenuates articular cartilage destruction in rats with adjuvant arthritis - Feng-Lai Yuan; Fei-Hu Chen; Wei-Guo Lu; Xia Li; Jian-ping Li; Cheng-Wan Li; Rui-Sheng Xu; Fan-Rong Wu; Wei Hu; Teng-Yue Zhang (Inflammation Research, 2010)

Inhibition of phosphodiesterase-4 reverses memory deficits produced by Aβ25–35 or Aβ1–40 peptide in rats - Yu-Fang Cheng; Chuang Wang; Huan-Bing Lin; Yun-Feng Li; Ying Huang; Jiang-Ping Xu; Han-Ting Zhang (Psychopharmacology, 2010)

Ectopic expression of an EAR motif deletion mutant of SlERF3 enhances tolerance to salt stress and Ralstonia solanacearum in tomato - I-Chun Pan; Chia-Wen Li; Ruey-Chih Su; Chiu-Ping Cheng; Choun-Sea Lin; Ming-Tsair Chan (Planta, 2010)

The vacuolar ATPase in bone cells: a potential therapeutic target in osteoporosis - Feng-Lai Yuan; Xia Li; Wei-Guo Lu; Cheng-Wan Li; Jian-Ping Li; Yu Wang (Molecular Biology Reports, 2010)

High-frequency somatic embryogenesis from germinated zygotic embryos of Schisandra chinensis and evaluation of the effects of medium strength, sucrose, GA3, and BA on somatic embryo development - Ai Hua Chen; Jing Li Yang; Yu Da Niu; Chuan Ping Yang; Gui Feng Liu; Chang Yeon Yu; Cheng Hao Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

Cloning, Heterologous Expression, and Functional Characterization of a Chitinase Gene, Lbchi32, from Limonium bicolor - Zhi Hua Liu; Chuan Ping Yang; Xiao Tian Qi; Li Li Xiu; Yu Cheng Wang (Biochemical Genetics, 2010)

Acid-sensing ion channel 1a mediates acid-induced increases in intracellular calcium in rat articular chondrocytes - Feng-Lai Yuan; Fei-Hu Chen; Wei-Guo Lu; Xia Li; Fan-Rong Wu; Jian-Ping Li; Cheng-Wan Li; Yu Wang; Teng-Yue Zhang; Wei Hu (Molecular and Cellular Biochemistry, 2010)

A Comprehensive Study of Deep Catalytic Oxidation of Benzene, Toluene, Ethyl Acetate, and their Mixtures over Pd/ZSM-5 Catalyst: Mutual Effects and Kinetics - Chi He; Peng Li; Jie Cheng; Zheng-Ping Hao; Zhi-Ping Xu (Water, Air, & Soil Pollution, 2010)

Association Analysis of the RET Proto-Oncogene with Hirschsprung Disease in the Han Chinese Population of Southeastern China - Cui-Ping Liu; Qian-Qian Tang; Jin-Tu Lou; Chun-Fen Luo; Xue-Wu Zhou; Dong-Mei Li; Fei Chen; Xiang Li; Ji-Cheng Li (Biochemical Genetics, 2010)

A tomato bZIP transcription factor, SlAREB, is involved in water deficit and salt stress response - Tsai-Hung Hsieh; Chia-Wen Li; Ruey-Chih Su; Chiu-Ping Cheng; Sanjaya; Yi-Chien Tsai; Ming-Tsair Chan (Planta, 2010)

Chloroplast transformation of rapeseed (Brassica napus) by particle bombardment of cotyledons - Lin Cheng; He-Ping Li; Bo Qu; Tao Huang; Jin-Xing Tu; Ting-Dong Fu; Yu-Cai Liao (Plant Cell Reports, 2010)

The interaction between interferon-induced protein with tetratricopeptide repeats-1 and eukaryotic elongation factor-1A - Hong-Tao Li; Yong-Ping Su; Tian-Min Cheng; Jian-Ming Xu; Jie Liao; Ji-Chuan Chen; Chang-You Ji; Guo-Ping Ai; Jun-Ping Wang (Molecular and Cellular Biochemistry, 2010)

Early Paleocene vegetation and climate in Jiayin, NE China - Hui Hao; David K. Ferguson; Guang-Ping Feng; Albert Ablaev; Yu-Fei Wang; Cheng-Sen Li (Climatic Change, 2010)

ThPOD3, a truncated polypeptide from Tamarix hispida, conferred drought tolerance in Escherichia coli - Xiao-Hong Guo; Jing Jiang; Bai-Chen Wang; Hui-Yu Li; Yu-Cheng Wang; Chuan-Ping Yang; Gui-Feng Liu (Molecular Biology Reports, 2010)

Enhanced salt tolerance of transgenic poplar plants expressing a manganese superoxide dismutase from Tamarix androssowii - Yu Cheng Wang; Guan Zheng Qu; Hong Yan Li; Ying Jie Wu; Chao Wang; Gui Feng Liu; Chuan Ping Yang (Molecular Biology Reports, 2010)

Rejecting strictly allopatric speciation on a continental island: prolonged postdivergence gene flow between Taiwan ( Leucodioptron taewanus , Passeriformes Timaliidae) and Chinese ( L. canorum canorum ) hwameis - JING-WEN LI; CAROL K. L. YEUNG; PI-WEN TSAI; RONG-CHIEN LIN; CHIA-FEN YEH; CHENG-TE YAO; LIANXIAN HAN; LE MANH HUNG; PING DING; QISHAN WANG; SHOU-HSIEN LI (Molecular Ecology, 2010)

Viral infection of tobacco plants improves performance of Bemisia tabaci but more so for an invasive than for an indigenous biotype of the whitefly - Jian Liu; Meng Li; Jun-min Li; Chang-jun Huang; Xue-ping Zhou; Fang-cheng Xu; Shu-sheng Liu (Journal of Zhejiang University-SCIENCE B, 2010)

Erratum to: Cypermethrin exposure during puberty disrupts testosterone synthesis via downregulating StAR in mouse testes - Hua Wang; Qun Wang; Xian-Feng Zhao; Ping Liu; Xiu-Hong Meng; Tao Yu; Yan-Li Ji; Heng Zhang; Cheng Zhang; Ying Zhang; De-Xiang Xu (Archives of Toxicology, 2010)

Cypermethrin exposure during puberty disrupts testosterone synthesis via downregulating StAR in mouse testes - Hua Wang; Qun Wang; Xian-Feng Zhao; Ping Liu; Xiu-Hong Meng; Tao Yu; Yan-Li Ji; Heng Zhang; Cheng Zhang; Ying Zhang; De-Xiang Xu (Archives of Toxicology, 2010)

Drepanocladus longifolius (Amblystegiaceae), an addition to the moss flora of King George Island, South Shetland Islands, with a review of Antarctic benthic mosses - Su-Ping Li; Ryszard Ochyra; Peng-Cheng Wu; Rodney D. Seppelt; Ming-Hong Cai; Hai-Ying Wang; Cheng-Sen Li (Polar Biology, 2009)

Blockade of HERG K+ channel by isoquinoline alkaloid neferine in the stable transfected HEK293 cells - Dong-fang Gu; Xue-lian Li; Zhi-ping Qi; Sha-shan Shi; Mei-qin Hu; Dong-min Liu; Cheng-bai She; Yan-jie Lv; Bao-xin Li; Bao-feng Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Memory deficits and neurochemical changes induced by C-reactive protein in rats: implication in Alzheimer’s disease - Huan-Bing Lin; Xue-Mei Yang; Tie-Jun Li; Yu-Fang Cheng; Han-Ting Zhang; Jiang-Ping Xu (Psychopharmacology, 2009)

Intercellular adhesion molecule-1 gene K469E polymorphism and ischemic stroke: a case-control study in a Chinese population - Xiao Xia Li; Jian Ping Liu; Jin Quan Cheng; Sheng Hong Han; Yi Jie Geng; Sheng Wei; Shi Tong Gao; Da Na Huang; Shao Fa Nie (Molecular Biology Reports, 2009)

A new screening method based on yeast-expressed human dipeptidyl peptidase IV and discovery of novel inhibitors - Chen-Xi Hu; Hui Huang; Li Zhang; You Huang; Zhu-Fang Shen; Ke-Di Cheng; Guan-Hua Du; Ping Zhu (Biotechnology Letters, 2009)

Association of polymorphisms at restriction enzyme recognition sites of apolipoprotein B and E gene with dyslipidemia in children undergoing primary nephrotic syndrome - Peng Hu; Yuan Han Qin; Cheng Xue Jing; Feng Ying Lei; Ping Chen; Ming Fang Li (Molecular Biology Reports, 2009)

Isolation and Characteristics of the CN Gene, a Tobacco Mosaic Virus Resistance N Gene Homolog, from Tobacco - Gai-Yun Zhang; Ming Chen; Jia-Ming Guo; Tong-Wen Xu; Lian-Cheng Li; Zhao-Shi Xu; You-Zhi Ma; Xue-Ping Chen (Biochemical Genetics, 2009)

Cloning and Characterization of the SSB-1 and SSB-4 Genes Expressed in Zebrafish Gonads - Jian-Zhen Li; Ya-Ping Zhou; Yan Zhen; Yan Xu; Peng-Xiang Cheng; Huan-Nan Wang; Feng-Jiao Deng (Biochemical Genetics, 2009)

Infectivity and propagation of attenuated infectious bursal disease virus in the chicken B-lymphocyte cell line DT40 - Jun Luo; Gai-Ping Zhang; Jian-Ming Fan; Man Teng; Lei-Ming You; Ling Zhou; Rui-Guang Deng; Xuan-Nian Wang; Yan-Yan Yang; Li Wang; Guang-Xu Xing; Na Cheng (Archives of Virology, 2009)

A cotton (Gossypium hirsutum) DRE-binding transcription factor gene, GhDREB, confers enhanced tolerance to drought, high salt, and freezing stresses in transgenic wheat - Shi-Qing Gao; Ming Chen; Lian-Qin Xia; Hui-Jun Xiu; Zhao-Shi Xu; Lian-Cheng Li; Chang-Ping Zhao; Xian-Guo Cheng; You-Zhi Ma (Plant Cell Reports, 2009)

Identification of α-gliadin genes in Dasypyrum in relation to evolution and breeding - Guang-Rong Li; Cheng Liu; Zi-Xian Zeng; Ju-Qing Jia; Tao Zhang; Jian-Ping Zhou; Zheng-Long Ren; Zu-Jun Yang (Euphytica, 2009)

Identification, expression and tissue distribution of a renalase homologue from mouse - Jian Wang; Shaoling Qi; Wei Cheng; Li Li; Fu Wang; Ying-Zi Li; Shu-Ping Zhang (Molecular Biology Reports, 2008)

Distribution, sources, and potential risk of polycyclic aromatic hydrocarbons (PAHs) in drinking water resources from Henan Province in middle of China - Ying-ge Ma; Jin-ping Cheng; Fei Jiao; Ke-xin Duo; Zheng Rong; Ming Li; Wen-hua Wang (Environmental Monitoring and Assessment, 2008)

Fluorescent co-localization of PTS1 and PTS2 and its application in analysis of the gene function and the peroxisomal dynamic in Magnaporthe oryzae - Jiao-yu Wang; Xiao-yan Wu; Zhen Zhang; Xin-fa Du; Rong-yao Chai; Xiao-hong Liu; Xue-qin Mao; Hai-ping Qiu; Yan-li Wang; Fu-cheng Lin; Guo-chang Sun (Journal of Zhejiang University-SCIENCE B, 2008)

Isolation and characterization of microsatellite loci in Pedicularis verticillata L. using PCR-based isolation of microsatellite arrays (PIMA) - Tsurng-Juhn Huang; Yi-Yen Chen; Yen-Ping Li; Cheng-Yu Hung; Tzen-Yuh Chiang; Chang-Hung Chou (Conservation Genetics, 2008)

Magnaporthe oryzae MTP1 gene encodes a type III transmembrane protein involved in conidiation and conidial germination - Qin Lu; Jian-ping Lu; Xiao-dong Li; Xiao-hong Liu; Hang Min; Fu-cheng Lin (Journal of Zhejiang University-SCIENCE B, 2008)

Nitrogen losses from integrated rice–duck and rice–fish ecosystems in southern China - Li Cheng-fang; Cao Cou-gui; Wang Jin-ping; Zhan Ming; Yuan Wei-ling; Shahrear Ahmad (Plant and Soil, 2008)

Localization of a novel gene for congenital nonsyndromic simple microphthalmia to chromosome 2q11-14 - Hui Li; Jia-Xin Wang; Cheng-Ye Wang; Ping Yu; Qiang Zhou; Yong-Gang Chen; Lu-Hang Zhao; Ya-Ping Zhang (Human Genetics, 2008)

Isolation of a new repetitive DNA sequence from Secale africanum enables targeting of Secale chromatin in wheat background - Cheng Liu; Zu-Jun Yang; Guang-Rong Li; Zi-Xian Zeng; Yong Zhang; Jian-Ping Zhou; Zhao-Hui Liu; Zheng-Long Ren (Euphytica, 2008)

Genetic Analysis of RET, EDNRB, and EDN3 Genes and Three SNPs in MCS + 9.7 in Chinese Patients with Isolated Hirschsprung Disease - Xian-Ning Zhang; Miao-Ni Zhou; Yun-Qing Qiu; Shi-Ping Ding; Ming Qi; Ji-Cheng Li (Biochemical Genetics, 2007)

Effect of lead on ERK activity and the protective function of bFGF in rat primary culture astroglia - Ying Zhang; Li-ping Ye; Biao Wang; Shi-cheng Cao; Li-guang Sun (Journal of Zhejiang University-SCIENCE B, 2007)

Fine mapping of the Pc locus of Sorghum bicolor, a gene controlling the reaction to a fungal pathogen and its host-selective toxin - Ervin D. Nagy; Tso-Ching Lee; Wusirika Ramakrishna; Zijun Xu; Patricia E. Klein; Phillip SanMiguel; Chiu-Ping Cheng; Jingling Li; Katrien M. Devos; Keith Schertz; Larry Dunkle; Jeffrey L. Bennetzen (Theoretical and Applied Genetics, 2007)

Phenotypic plasticity rather than locally adapted ecotypes allows the invasive alligator weed to colonize a wide range of habitats - Yu-Peng Geng; Xiao-Yun Pan; Cheng-Yuan Xu; Wen-Ju Zhang; Bo Li; Jia-Kuan Chen; Bao-Rong Lu; Zhi-Ping Song (Biological Invasions, 2007)

Variation in two PPO genes associated with polyphenol oxidase activity in seeds of common wheat - Cheng Chang; Hai-Ping Zhang; Jie Xu; Ming-Shan You; Bao-Yun Li; Guang-Tian Liu (Euphytica, 2007)

Soil erosion and vegetation succession in alpine Kobresia steppe meadow caused by plateau pika—A case study of Nagqu County, Tibet - Xinghu Wei; Sen Li; Ping Yang; Huaishun Cheng (Chinese Geographical Science, 2007)

Identification of poly-reactive natural IgM antibody that recognizes late apoptotic cells and promotes phagocytosis of the cells - Meng Fu; Ping-shen Fan; Wei Li; Cheng-xin Li; Ying Xing; Jing-gang An; Gang Wang; Xue-li Fan; Tian-wen Gao; Yu-feng Liu; Shigaku Ikeda (Apoptosis, 2007)

Haplotype Frequency Distribution and Linkage Disequilibrium Analysis of Single Nucleotide Polymorphisms at the Human FMO3 Gene Locus - Da-Cheng Hao; Jie Sun; Bjarte Furnes; Daniel Schlenk; Zhen-Fang Hou; Ya-Ping Zhang; Sheng-Li Yang; Ling Yang (Biochemical Genetics, 2006)

Apoptotic and anti-proliferative effects of 17β-estradiol and 17β-estradiol-like compounds in the Hep3B cell line - Erh-Jung Huang; Cheng-Chung Wu; Hsien-Ping Huang; Jer-Yuh Liu; Chung-Sheng Lin; Yan-Zin Chang; James A. Lin; Jaung-Geng Lin; Li-Mien Chen; Shin-Da Lee; Wei-Wen Kuo; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2006)

Studies on the Interaction of Tricyclazole with β-cyclodextrin and human Serum Albumin by Spectroscopy - Hua-Xin Zhang; Xing Huang; Ping Mei; Ke-Hua Li; Cheng-Nong Yan (Journal of Fluorescence, 2006)

Streptomyces daliensis sp. nov. from soil - Ping Xu; Wen-Jun Li; Shu-Kun Tang; Hui-Ying Gao; Li-Hua Xu; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2006)

Transgenic tomato plants expressing an Arabidopsis thionin (Thi2.1) driven by fruit-inactive promoter battle against phytopathogenic attack - Yuan-Li Chan; Venkatesh Prasad; Sanjaya; Kuei Hung Chen; Po Chang Liu; Ming-Tsair Chan; Chiu-Ping Cheng (Planta, 2005)

Streptomyces nanningensis sp. nov. a novel Streptomycete from forest soil - Yi Jiang; Wen-Jun Li; Ping Xu; Ming-Gang Li; Meng-Liang Wen; Guan-Hua Du; Li-Hua Xu; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2005)

Cloning and Characterization of the First Cnidarian ADP-Ribosylation Factor, and Its Involvement in the Aiptasia-Symbiodinum Endosymbiosis - Ming-Chyuan Chen; Ying-Min Cheng; Li-Hsueh Wang; Chorng-Horng Lin; Xing-Yan Huang; Ming-Chin Liu; Ping-Jyun Sung; Lee-Shing Fang (Marine Biotechnology, 2004)

Minimizing phenol pollution in sugarcane stem apical meristem culture - Cheng-Mei Huang; Yang-Rui Li; Yan-Ping Ye (Sugar Tech, 2003)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)